Effects of surgical implantation of electronic tags in fishes: a review and meta-analysis - Mitchell B. Shorgan; Graham D. Raby; Amber L. Fedus; Bradley E. Howell; Laura S. E. Haniford; Leah C. Howitt; Natalie V. Klinard; Jordan K. Matley; Jacob W. Brownscombe; Steven J. Cooke; Aaron T. Fisk (Reviews in Fish Biology and Fisheries, 2026)

Removing cost barriers may increase feline culture rates but has limited impact on antibiogram representativeness - Joshua Glass; Casey L. Cazer; Maryam Maqsood Ahmed; Sarah Robbins; Anam Waseem; Robert Goggs; Patrick K. Mitchell; Rebecca J. Franklin-Guild; Melissa Aprea; Cassandra Guarino; Kevin J. Cummings; Craig Altier; et al. (Preventive Veterinary Medicine, 2026)

Sediment response to stream restoration in an agricultural watershed - John W. Clune; Gregory B. Noe; Matthew Cashman; Jessica D. DeWitt; Joseph M. Bell; Mitchell R. Weaver; James E. Colgin; Thomas R. Doody; Eliza L. Gross; Victor S. Cortes (Ecological Engineering, 2026)

Application of the Total Nutrient Index as a Precision Nutrition Tool to Address Dietary Recommendations Across the Life Course - Alexandra E. Cowan-Pyle; Janet A. Tooze; Lindsay M. Reynolds; Jaime J. Gahche; Johanna T. Dwyer; Diane C. Mitchell; Raymond J. Carroll; Bani K. Mallick; Regan L. Bailey (Journal of the Academy of Nutrition and Dietetics, 2026)

Using fracture scarp intersection lineations as kinematic indicators on active normal fault scarps - Billy J. Andrews; Zoë K. Mildon; Manuel L. Diercks; Sam Mitchell; Gerald P. Roberts; Constanza Rodriguez Piceda; Jenni Robertson (Journal of Structural Geology, 2026)

Patterns of pesticide use and potential health risks among men and women farmers in Rwanda: Practices, behaviors, and knowledge in Eastern Province - Cynthia L. Curl; Emmanuel Irimaso; Concorde Rwibutso; Therese Nyirahabimana; Liberata Mukamana; Stephanie Mitchell; Dawn Zimmerman; Sabrina B. Sholts (International Journal of Hygiene and Environmental Health, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Mechanical jamming in pseudotachylyte-hosted breccias - David P. Dobson; Charlotte L. Bays; Thomas M. Mitchell (Tectonophysics, 2026)

Caledochytrium aldermanii gen. Et sp. nov.; a new Labyrinthulomycete displaying a novel reproductive strategy - Jane L. Polglase; Peter C. Morris; Stephen W. Feist; Wilfrid J. Mitchell; Fiona Strachan; Kirsty A. Fraser; James R. Iremonger; Elisabeth A. Dyrynda; Alastair R. Lyndon; Lydia A. Brown (Protist, 2026)

Ancestry informative genetic variants associated with tobacco metabolic and detoxification capacity measured by 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) among smokers - Oladimeji Lanade; Zhongxuan He; Yan Zhou; Elizabeth Blackman; Denise Gibbs; Sharon Harrison; Karthik Devarajan; Mark Andrake; Roland L. Dunbrack; Gerald Nkogbu; Aditi Wagh; Michael Slifker; et al. (Archives of Toxicology, 2026)
Tobacco use remains the leading preventable cause of cancer mortality worldwide, with marked disparities in cancer incidence and outcomes across racial and ethnic groups. This study investigates the genetic determinants of tobacco carcinogen metabolism among smokers, focusing on ancestry-informative markers (AIMs) near genes involved in metabolic activation (Phase I), detoxification (Phase II), and transport (Phase III) of tobacco-specific carcinogens. Using data from 274 smokers recruited in the United States and the Caribbean, we measured urinary NNAL (a metabolite of NNK) to classify metabolic phenotypes and performed genotyping with a customized array enriched for AIMs. Most participants (94%) were classified as poor metabolizers of NNAL, with a higher prevalence among Black/African American smokers. Multivariable analyses, after adjusting for age, sex, assay batch, and number of cigarettes smoked per day, identified 14 AIMs near Phase I, II, and III pathway genes significantly associated with NNAL metabolizer phenotype, with African ancestry alleles conferring increased odds of poor metabolism. Functional annotation revealed that most significant AIMs overlapped regulatory regions, and the CYP3A5 rs776746 variant demonstrated structural disruption likely to impair enzymatic activity. Majority of participants had high African ancestry and were poor NNAL metabolizers, consistent with the observed association between African ancestry and poor NNAL metabolism. These findings highlight the biological basis for tobacco-related cancer disparities and underscore the importance of integrating genetic ancestry and metabolic phenotyping in risk assessment and personalized prevention strategies for tobacco-associated cancers.

Adolescent prefrontal and amygdala molecular signatures of perinatal morphine versus buprenorphine exposure in mice - Brittany L. Smith; Grace Winstel; Brandon Brooks-Patton; Anna G. Makela; Boluwatife Osifalujo; Noah Raleigh; Bolaji Akindiose; Claire Mitchell; Maria E. Taylor; Kyle L. Cosby (NeuroToxicology, 2026)

Prospective categorisation of maternal care style in Thoroughbred broodmares - Alexandra L. Moss; Orlagh O’Reilly; Amy Rand; Amy R. Holtby; Siobhan Mullan; Katharyn Mitchell; Emmeline W. Hill; Michael Salter-Townshend; Lisa M. Katz (Applied Animal Behaviour Science, 2026)

The Effects of Land‐Use Dynamics on Avian Phylogenetic Diversity Across Island Ecosystems - Halvina G. Saiya; David P. Edwards; Matthew J. Struebig; David J. I. Seaman; Robby Butarbutar; Nurul L. Winarni; Simon L. Mitchell; Jatna Supriatna; Rob W. Martin; Adi Karya; Robert P. Freckleton (Journal of Biogeography, 2026)
Aim To test whether forest extent and recent forest‐cover change are associated with avian phylogenetic diversity and community‐level evolutionary value across islands. Location Seven islands spanning Borneo and Wallacea in the Malay Archipelago. Taxon Terrestrial birds. Methods We sampled 1410 sites (2010–2022). We calculated phylogenetic diversity (PD), mean phylogenetic distance (MPD), mean nearest taxon distance (MNTD) and their standardised effect sizes (SES), as well as community‐level EDGE (Evolutionarily Distinct and Globally Endangered). Responses to (i) average forest proportion (250‐m radius) and (ii) recent forest‐cover change were analysed with spatial linear mixed‐effects. Results Observed PD showed a negative visual trend with increasing forest proportion, whereas SES PD declined. MPD showed only a weak positive visual trend with forest proportion, whereas SES MPD showed no clear response. Although observed MNTD appeared to increase in the binned visual summaries, both observed MNTD and SES MNTD showed significant negative associations with forest cover in the spatial models, indicating stronger nearest‐neighbour phylogenetic clustering in more forested sites. Effects of recent forest loss (2010–2022) on SES metrics were generally weak and inconsistent. Although PD also declined with decreasing rates of forest change, community‐level EDGE was higher where forest cover was greater, indicating higher average evolutionary distinctiveness and extinction risk. Main Conclusions In this archipelagic system, forest amount is a key correlate of phylogenetic structure and the retention of evolutionarily distinctive, high‐risk lineages. By contrast, recent forest‐cover change showed weaker and more context‐dependent associations. Conserving intact forests remains crucial for safeguarding the evolutionary legacy of island bird communities.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Crop mixtures: yield responses to climate and management and impacts on seed and soil chemical composition in a Scottish-based study - R. Brooker; R. J. Pakeman; R. L. Hewison; C. Mitchell; A. C. Newton; R. Neilson; S. Raubach; P. D. Shaw; S. Verrall; A. J. Karley (Plant and Soil, 2026)
Introduction Crop mixtures can be an important part of the toolkit for maintaining crop production while addressing the climate and nature crises. However, uncertainties around some issues may prevent their uptake. Research question This study addressed several uncertainties, specifically the response of mixture yields to climate and management, and the impacts of mixed cropping on seed chemical composition, soil carbon and nutrients. Materials and methods We undertook 32 intercropping trials between 2020 and 2022 on both commercial and research farms. These varied in design, management and crop combinations, with mixture choice often determined by farmers. We assessed multiple responses including yield, weed cover, and seed and soil chemical composition. Results and conclusions When compared to monocultures, yield gains from growing a crop mixture were roughly 20% based on Crop Performance Ratio (CPR). We found limited impacts of mixture diversity and composition on seed chemical composition, influences of management on weed control, and enhanced crop mixture performance under cooler conditions with lower rainfall. We also found varying mixture performance depending on mixture composition. Importantly, irrespective of management, climate, and composition effects, crop mixtures always performed at least as well as expectations based on monocultures. Even without further refinement from, for example, targeted breeding, crop mixtures provide reliable crops without yield losses or (for parameters tested) substantial changes in seed chemistry. However, detected reductions in organic matter in upper soil layers indicate a priority for future research is understanding crop mixture impacts on soil carbon dynamics in both shallow and deep soils.

Warming influences nutrient removal in mesocosms across different substrates - Abagael N. Pruitt; Jennifer L. Tank; Caroline G. T. Anscombe; Mitchell J. Liddick; Elise D. Snyder; Emma M. Thrift‐Cahall; Erik M. Curtis; Anna E. S. Vincent (Limnology and Oceanography, 2026)
Climate change is increasing stream temperatures globally, likely impacting stream ecosystem processes. We conducted a stream warming experiment at the Notre Dame Experimental Mesocosm Facility using N = 24 recirculating mesocosms to examine the effect of warming on biofilm colonization of organic and inorganic substrata and rates of nutrient removal. We conducted an experiment with three temperature treatments (20°C, 23°C, and 26°C) in mesocosms containing either decomposing sugar maple ( Acer saccharum ) leaves or cobble substrate under shaded and unshaded conditions, respectively. We measured biofilm chlorophyll a (Chl a ) on cobble, community respiration on leaf disks, and removal of ammonium (NH 4 + ‐N) and soluble reactive phosphorus weekly for 21 d. Warming did not significantly alter Chl a or community respiration (generalized linear mixed model, p > 0.05). For nutrients, however, warming increased NH 4 + ‐N removal for both leaves and cobble. For cobble, NH 4 + ‐N removal was higher at 26°C (mean = 3.5 h −1 with a 75% credible interval of [3.1, 4.0]) compared to 20°C (2.3 h −1 [1.9, 2.7]; Bayesian regression model). For leaves, NH 4 + ‐N removal was also higher at 26°C (1.1 h −1 [1.0, 1.2]) compared to 20°C (0.5 h −1 [0.4, 0.6]). In contrast, warming only altered soluble reactive phosphorus removal for cobble; removal was higher at 26°C at 1.9 h −1 [1.7, 2.2] compared to 20°C (1.1 h −1 [0.8, 1.3]). Warming did not alter soluble reactive phosphorus removal for leaves. We show that warming‐induced changes in nutrient removal are mediated by substrate, and that NH 4 + ‐N removal may be more sensitive to elevated temperatures than soluble reactive phosphorus removal, with implications for altered nutrient cycling under a warmer future.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Millennial-scale fire and climate dynamics in the world's largest tropical wetland show emerging fire threat to flooded ecosystems - Bronwen S. Whitney; Danilo M. Neves; Nicholas J.D. Loughlin; Carlos D'Apolito; Carla Coblinski Tavares; Emma P. Hocking; Francis E. Mayle; Mitchell J. Power; Aguinaldo Silva; Mario L. Assine (Global and Planetary Change, 2026)

SuperTIGER galactic cosmic-ray source abundances for the charge interval 16 ⩽ Z ⩽ 56 - N.E. Osborn; N.E. Walsh; Q. Abarr; Y. Akaike; W.R. Binns; R.G. Bose; T.J. Brandt; D.L. Braun; N.W. Cannady; R.M. Crabill; P.F. Dowkontt; S.P. Fitzsimmons; et al. (Advances in Space Research, 2026)

SuperTIGER ultra-heavy galactic cosmic ray atmospheric corrections using Geant4 simulations - N.E. Osborn; Q. Abarr; Y. Akaike; W.R. Binns; R.G. Bose; T.J. Brandt; D.L. Braun; N.W. Cannady; R.M. Crabill; P.F. Dowkontt; S.P. Fitzsimmons; T. Hams; et al. (Advances in Space Research, 2026)

Pre- and postnatal exposure to PM2.5 and NO2 and blood pressure in children: Results from the ECHO Cohort - Yu Ni; Andrew Law; Xingyu Gao; Adam A. Szpiro; Christine T. Loftus; Miranda Jones; Logan C. Dearborn; Marnie F. Hazlehurst; Allison R. Sherris; Sindana Ilango; Kaja Z. LeWinn; Nicole R. Bush; et al. (Environmental Research, 2026)

Gestational fine particulate matter exposure and perinatal outcomes in the ECHO cohort: Associations across pregnancy windows - Adaeze W. Nzegwu; Aisha S. Dickerson; Kristin Miller; Adam Szpiro; Alison E. Hipwell; Amy J. Elliot; Amy M. Padula; Anne L. Dunlop; Anne P. Starling; Assiamira Ferrara; Carrie V. Breton; Christine T. Loftus; et al. (Environmental Research, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Top-down Control by Ribbed Mussels (Geukensia demissa) on Plankton Communities in Southeastern U.S. Salt Marshes - Sydney L. Williams; Donovan Mitchell; Edward J. Phlips; Rachel Guy; Nikki Dix; Christine Angelini (Estuaries and Coasts, 2026)
Benthic grazers and suspension feeders, such as oysters and mussels, may play a disproportionate role in controlling algal biomass and plankton community composition in estuarine systems. Nonetheless, their effects on plankton communities remain poorly understood across environmental contexts, in part from a paucity of in situ measurements. Here, we conducted in situ manipulative field experiments to evaluate the effects of the Atlantic ribbed mussel, Geukensia demissa , on bulk chlorophyll a (µg L − 1 ); absolute cell abundance (individuals mL − 1 ) of plankton groups > 10 μm in diameter (i.e., pennate and centric diatoms, dinoflagellates, and heterotrophic nano- and microzooplankton); and relative cell abundance (%) of plankton trophic levels (i.e., auto-, mixo-, and heterotrophic) across three salt marsh sites in the southeastern U.S. (Georgia and Florida). Mussel grazing reduced both chlorophyll a concentrations and total absolute cell abundances by 120–150% compared to cordgrass only plots and the ambient water column. Mussel effects on plankton groups were consistently strong and negative, ranging from − 1.12 to − 2.51. At two of the three sites, mussels reduced pennate and centric diatoms to a greater extent (> 155%) than dinoflagellates (~ 100%). This selective grazing likely shifted plankton community composition toward a more mixotrophic structure, whereby the relative contribution of autotrophic diatoms declined from roughly 80% and 65% in ambient waters to 70% and 45% in mussel plots, respectively, while the relative abundance of dinoflagellates increased. Given the essential role of the plankton community in mediating the ecological and geochemical functioning of estuaries, our results highlight that, within natural salt marshes, mussels play a significant role each tidal cycle in modifying such functions through their prolific and selective grazing on this community.

Peptide-functionalized nanoparticles for brain-targeted therapeutics - Sophia Tang; Emily L. Han; Michael J. Mitchell (Drug Delivery and Translational Research, 2026)
Despite the rapid development of nanoparticle (NP)-based drug delivery systems, intravenous delivery of drugs to the brain remains a major challenge due to various biological barriers. To achieve therapeutic effects, NP-encapsulated drugs must avoid accumulation in off-target organs and selectively deliver to the brain, successfully cross the blood–brain barrier (BBB), and reach the target cells in the brain. Conjugating receptor-specific ligands to the surface of NPs is a promising technique for engineering NPs to overcome these barriers. Specifically, peptides as brain-targeting ligands have been of increasing interest given their ease of synthesis, low cytotoxicity, and strong affinity to target proteins. The success of peptides as targeting ligands is largely due to the diverse strategies of designing and modifying peptides with favorable properties, including membrane permeability and multi-receptor targeting. Here, we review the design and implementation of peptide-functionalized NP systems for neurological disease applications. We also explore advances in rational peptide design strategies for brain targeting, including using generative deep-learning models to computationally design new peptides. Graphical Abstract

How would Australian women and people with a cervix like to access self-collection for cervical screening? Screening preferences from a national survey - Claire Bavor; Chloe Jennett; Emily Phillips; Louise Mitchell; Tessa Saunders; Lisa Whop; Angela Kelly-Hanku; Deborah Bateson; Julia M. L. Brotherton; Megan A. Smith; Claire Nightingale (Cancer Causes & Control, 2026)
Purpose In Australia, cervical screening is usually offered face-to-face through primary care. As self-collection offers flexibility in how and where screening can be accessed, we assessed participant preferences for flexible screening models. Methods We recruited women and people with a cervix aged 24–74 years into a national survey (December 2023–April 2024) via a paid Meta campaign and community networks. Sociodemographic factors associated with a preference for appointment- or non-appointment-based models were assessed using logistic regression, stratified by age, < 50 and ≥ 50 years. Results Among 9,586 respondents, the median age was 41 years, 67.9% lived in a major city, 82.5% were born in Australia, and 62.6% screened regularly. Most (82.6%) viewed flexible options for accessing screening as very important/important. Respondents favored non-appointment-based compared to appointment-based models, with 53.5% of those < 50 ( n = 4,842) and 49.5% of those ≥ 50 ( n = 1,257) preferring to receive a swab in the mail when due. Non-appointment-based models were preferred by participants aged < 50 and ≥ 50 years who were never-screened (adjOR = 1.52, 95% CI = 1.18–1.96, p = 0.001; adjOR = 2.91, 95% CI = 1.67–5.09, p < 0.001), irregular screeners (adjOR = 1.58, 95% CI = 1.36–1.85, p < 0.001; adjOR = 1.52, 95% CI = 1.17–1.98, p = 0.002) and recently eligible for screening (adjOR = 1.64, 95% CI = 1.08–2.50, p = 0.02) compared to regular screeners. Convenience was the most common reason for participants’ preferred screening model (87.4% non-appointment-based; 55.1% appointment-based). Conclusion Flexibility in how cervical screening can be accessed appeals to many screen-eligible people. Further research trialing different models assessing screening uptake and clinical pathways to follow-up care is needed.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

Minimizing use of nonhuman primates to inform risk to fertility and of adverse pregnancy outcomes with pharmaceuticals - Christopher J. Bowman; Ann Baker; Diann L. Blanset; Kimberly C. Brannen; Gary J. Chellman; Brian Enright; Wendy Halpern; Bethany R. Hannas; Kazushige Maki; Fumito Mikashima; Shermaine Mitchell-Ryan; Eve Mylchreest; et al. (Regulatory Toxicology and Pharmacology, 2026)

Retrospective evaluation of the use of non-human primates for fertility assessment of pharmaceuticals submitted for marketing approval in the EU - Puck Roos; Diann L. Blanset; Peter JK. van Meer; Shermaine Mitchell-Ryan; Peter T. Theunissen; Katie J. Turner; Ronald L. Wange; Christopher J. Bowman (Regulatory Toxicology and Pharmacology, 2026)

Large-scale field experiments on enhancing In-Situ burning with fire whirls - Wuquan Cui; Joseph L. Dowling; Mohammadhadi Hajilou; Mitchell Huffman; Bhushan Pawar; Johanna Aurell; Qingsheng Wang; Elaine Oran; Karen N. Stone; Michael J. Gollner (Fuel, 2026)

Pining for diversity: Does greater tree species diversity enhance the resilience of associated biodiversity and ecosystem functioning in Pinus sylvestris forests? - R.J. Mitchell; S.D. Albon; P.E. Bellamy; C. Cameron; L. Cocks; C.J. Ellis; N.G. Hodgetts; C. Johnstone; C. Nichols; J.A. Stockan; A.F.S. Taylor (Forest Ecology and Management, 2026)

The Peripheral Epigenome Predicts White Matter Volume Contingent on Developmental Stage: An ECHO Study - Taena Hanson; Sophie Spencer; Samantha A. Harker; Fatoumata Barry; Jennifer Beauchemin; B. Blair Braden; Phoebe Burton; Viren D’sa; Daphne Koinis-Mitchell; Sarah E. Mennenga; Sean C. L. Deoni; Candace R. Lewis (Molecular Neurobiology, 2026)

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

Mapping blue carbon ecosystems from Earth observations at a national scale for Papua New Guinea - Christopher J. Owers; Richard M. Lucas; Carole Planque; Daniel Clewley; Matt Paget; Chloe Fitzpatrick; Annette Burke; Freddie Alei; Mitchell B. Lyons; Andrew D. L. Steven (Frontiers in Marine Science, 2025)
National maps are essential to support the conservation, restoration, and sustainable management of blue carbon ecosystems (BCE). This is particularly important for nations in the Indo-Pacific region, including Papua New Guinea (PNG), that aspire to integrate these ecosystems into their nationally determined contributions (NDCs) for ecosystem accounting. This study focussed on mapping the extent of BCEs in PNG using Earth observation data for the year 2020 and reporting on biomass and carbon storage services. Land cover categories were generated using the Living Earth framework for the 15 coastal provinces of PNG. The total BCE area in PNG (14,353 km²) comprised 30% mangrove, 65% lowland peat swamp forest, 3% saltmarsh, and 2% seagrass. Lowland peat swamp forests contribute the greatest biomass (137.94 ± 67.10 Tg) followed by mangroves (71.79 ± 27.16 Tg), with a total biomass of 212.99 ± 95.89 Tg. Across PNG, a total of 710.46 ± 362.75 Tg C were estimated for belowground carbon of BCEs (reporting to 1 m depth), almost seven times more than that of aboveground carbon (102.14 ± 45.97 Tg C). This study highlights the need for a consistent and standardised framework for mapping BCEs, which can support coordinated management of coastal landscapes across provinces that contribute to national policies and NDC reporting. This case study can be used as a demonstration for other nations where similar opportunities and challenges may exist for mapping BCE using Earth observations, with a framework that can be compared and adapted to user requirements.

Bridging the Gap: Enhancing Prostate Cancer Survivorship and Advocacy Among Ethnically Diverse Black Men Through Community Town Halls - Motolani E. Ogunsanya; Ernest Kaninjing; Sara M. DeForge; Daniel J. Morton; Perry Cole; Patrick Beckford; Donald Reese; Thomas Mitchell; Everett Montgomery; Roland Odeleye; Erick Y. Miró-Rivera; Kaitlin Roberts; et al. (Journal of Cancer Education, 2025)
We present findings from town hall meetings held with ethnically diverse Black prostate cancer (CaP) survivors in 2022 and 2023. Four town halls (total participants, N = 265) focused on diagnosis, treatment, psychosocial support, and overall survivorship. Moderated by a long-term CaP survivor, each session featured a panel that included medical providers (urologic oncologists and clinical psychologists), as well as CaP survivors of American, Caribbean, and African origin and their spouses. Surveys captured demographic data, clinical information, CaP-specific details (for survivors only), and perceptions of the town halls. The meetings highlighted three interrelated themesinfluencing decision-making: access to comprehensive information, the strength of support networks, and the availability of culturally competent care. These town halls revealed important educational and support opportunities for ethnically diverse Black men with CaP, promoting informed decision-making throughout the cancer journey and improving quality of life while reducing decisional regret during survivorship.

Full-length mRNA sequencing resolves novel variation in 5′ UTR length for genes expressed during human CD4 T-cell activation - Cassandra R. Woolley; Julia H. Chariker; Eric C. Rouchka; Easton E. Ford; Elizabeth Hudson; Kamille M. Rasche; Caleb S. Whitley; Zachary Vanwinkle; Carolyn R. Casella; Melissa L. Smith; Thomas C. Mitchell (Immunogenetics, 2025)

A standardized nontargeted metabolomics method for cross-laboratory comparison of food profiles - Melanie T. Odenkirk; Cole Michel; Katrina A. Doenges; Katrina L. Leaptrot; Stacy D. Sherrod; Jody C. May; Margaret L. Read; Jacqueline M. Chaparro; Nathan Montgomery; Sarah Brinkley; Arpana Vaniya; Susan B. Mitchell; et al. (Food Chemistry, 2025)

Effect of β-blockade on measures and reproducibility of heart rate, oxygen uptake and work rate across repeated bouts of short-duration, RPE-regulated exercise - Braden L. Mitchell; Kade Davison; Gaynor Parfitt; Roger G. Eston (European Journal of Applied Physiology, 2025)
Purpose We examined the effect of β-blockade on measures and reproducibility of heart rate (HR), oxygen uptake ( $${\dot{\rm{V}}}{\rm{O}}_{2}$$ V ˙ O 2 ) and work rate (WR) across repeated bouts of short-duration, RPE-regulated exercise. Methods Participants completed an RPE-regulated, interval-based exercise session under control and β-blockade conditions with six 3-min bouts alternating between RPE 13 and RPE 15, separated by 2-min active recovery periods. Participants adjusted treadmill speed/grade to meet the target RPE. Linear mixed effects models assessed the effect β-blockade on exercise responses for each RPE, while intraclass correlation coefficients (ICC) and coefficients of variation (CV) evaluated reproducibility across bouts. Results β-Blockade significantly reduced HR (− 36.5 beat min −1 , p < 0.001), $${\dot{\rm{V}}}{\rm{O}}_{2}$$ V ˙ O 2 (− 4.2 mL kg −1 min −1 , p < 0.001) and work rate (− 0.6 METs, p = 0.022) during exercise. Differences between conditions remained significant for %HR peak ( p < 0.001) but not % $${\dot{\rm{V}}}$$ V ˙ O 2peak or %WR peak ( p > 0.05). Exercise responses were consistently higher at RPE 15 than RPE 13 (all p < 0.001). A significant interaction showed greater HR reduction at RPE 15 (45.5 beat min −1 ) than RPE 13 (40.0 beat min −1 ) under β-blockade ( p = 0.041). ICC values indicated good to excellent reproducibility across bouts, with no significant difference between conditions. Variability across bouts was low (mean CV = 2–8%) and unaffected by β-blockade. Conclusion Our findings suggest that despite significant reductions in absolute responses, β-blockade does not affect relative measures of $${\dot{\rm{V}}}$$ V ˙ O 2 or work rate. RPE-regulated exercise may facilitate highly reproducible exercise intensities, making it particularly valuable for populations where β-blocker use is prevalent.

A critical review of research concerning the gut microbiome in dogs and its relationship with behaviour - Agnese Crisante; Fiona Newberry; Simon R. Clegg; Gabriella L. Mitchell; Thomas W. Pike; Vicky Ratcliffe; Adele Spain; Anna Wilkinson; Helen Zulch; Daniel S. Mills (Applied Animal Behaviour Science, 2025)

Predator exposure and gene flow as tools to preserve antipredator traits in havened populations: behavioural observations of quenda - Natasha D. Harrison; Nicola J. Mitchell; Harriet Mills; Anna J.M. Hopkins; Ben L. Phillips (Animal Behaviour, 2025)

New approach methodologies for assessing developmental toxicity of pharmaceuticals: Case examples and future directions - Nicola Powles-Glover; Allen R. Kaczor; Steven Van Cruchten; Christopher J. Bowman; Kimberly C. Brannen; Claudia Demarta-Gatsi; Isabelle LeConte; Amer Jamalpoor; Fumito Mikashima; Shermaine Mitchell-Ryan; Dinesh Stanislaus; Peter Theunissen; et al. (Reproductive Toxicology, 2025)

Dietetics and Nursing Students Affirmatively Report the Likelihood of Recommending Predominantly Plant-based Diets for Non-communicable Disease Management - P. Dyett; L. Foster-Nicholas; C. Mitchell; V. Jones-Oyefeso; V. Sealey-Tobias; A. Adams-Robinson; P. Valley-Thom; D. Balfour (Journal of the Academy of Nutrition and Dietetics, 2025)

The Fundamentals of the Analysis of Cascade Impactor Data for the Characterization of Aerodynamic Particle Size Distributions (APSDs) in the Testing of Orally Inhaled Drug Products (OIPs) - Daryl L. Roberts; Jolyon P. Mitchell (AAPS PharmSciTech, 2025)

The associations between playing a musical instrument and grey matter in older adults at risk for dementia: a whole-brain VBM analysis - Nicole Espinosa; Marshall A. Dalton; Hannes Almgren; Andrew C. McKinnon; Helen F. Mitchell; Zoe Menczel Schrire; Sharon L. Naismith (GeroScience, 2025)

Novel primers for the detection and differentiation of S. zooepidemicus and S. equi by PCR - Tanya Mikaiel; Andrew Waller; Alastair Foote; Jacqueline M Cardwell; Judy Mitchell; Simon L. Priestnall (Research in Veterinary Science, 2025)

GMFOLD: Subgraph matching for high-throughput DNA-aptamer secondary structure classification and machine learning interpretability - Paolo Climaco; Noelle M. Mitchell; Matthew J. Tyler; Kyungae Yang; Anne M. Andrews; Andrea L. Bertozzi (Mathematical Biosciences, 2025)

Animal farming and the oral microbiome in the Agricultural Health Study - Vicky C. Chang; Vaishnavi Purandare; Shilan Li; Gabriella Andreotti; Xing Hua; Yunhu Wan; Casey L. Dagnall; Kristine Jones; Belynda D. Hicks; Amy Hutchinson; Yukiko Yano; Kathryn R. Dalton; et al. (Environmental Research, 2025)

Nanoscale dynamics in model phospholipid biomembranes probed by muon spin resonance spectroscopy: The effects of membrane composition and temperature on acyl chain and cholesterol motion - Iain McKenzie; Mitchell DiPasquale; Maksymilian Dziura; Thomas Gutberlet; Nathan A. Hartwig; Victoria L. Karner; Robert Scheuermann; Drew Marquardt (Chemistry and Physics of Lipids, 2025)

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

Coexistence, Extinction and Survival—The Evolutionary History of Bison Species in Western Eurasia - Bastien Llamas; Ayla L. van Loenen; Kieren J. Mitchell; Emilia Hofman‐Kamińska; Hervé Bocherens; Holly Heiniger; Martina Pacher; Daniel Makowiecki; Giedrė Piličiauskienė; Dorothée G. Drucker; David Brown; Zoe A. Thomas; et al. (Global Change Biology, 2025)
European bison ( Bison bonasus ) are one of the few European megafaunal species to survive the Late Pleistocene mass megafaunal extinction. Current conservation management efforts have proceeded in the absence of information about their evolutionary history, which has been obscured by recent severe population bottlenecks. We characterized mitochondrial genomes from 135 ancient bison samples spanning > 50,000 years (> 50 ka) across the Eurasian continent and detected three distinct phylogenetic groups: two distinct clades of European bison and the extinct steppe bison ( Bison priscus ). The geographical distributions and dietary/ecological signatures of the three groups overlapped during the Late Pleistocene climate cycles and tracked environmental changes including vegetation cover and human impacts. The abundance of European bison specimens responded negatively to the extent of forest cover, including Holocene cycles of abrupt atmospheric‐ocean circulation changes originating in the North Atlantic. European bison remain preferentially adapted to an open environment, but with today's anthropogenic landscapes, are now largely restricted to forest habitats with negative implications under scenarios of future environmental change.

Cyclosiloxane artifacts explain reported Henry’s law constants for nonvolatile fluorotelomer sulfonates - Sophia K. Nelson; Mitchell L. Kim-Fu; Mohammad Azizian; Jennifer A. Field (Journal of Hazardous Materials, 2025)

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16-hydroxyestradiol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2025)

Climate and Emissions Benefits of Renewable Diesel: In-Use Testing of a Tier 2 Commercial Harbor Craft - Julia A. Billington; Bo Yang; Wayne Sobieralski; Christian Fehrenbacher; Gavin M. Hoch; Andrew L. Damiano; Razieh Nadafianshahamabadi; Alexander R. Mitchell; David C. Quiros (Emission Control Science and Technology, 2025)

Nanoengineered cellulose for sustainable selective separation of precious metals from electronic waste - Roya Koshani; Shang-Lin Yeh; Mica L. Pitcher; Lucas Lawrence Franz; Mitchell Robert Davis; Min Ju Park; Said Khalifa Ahmed Al Qassabi; Joelson Patricio Manuel Alves; Younes Shekarian; Hevapathiranage Chandima Sudantha Subasinghe; Sarma V. Pisupati; Mohammad Rezaee; et al. (Chemical Engineering Journal, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Evaluating models of expert judgment to inform assessment of ecosystem viability and collapse - Josh Dorrough; Samantha K. Travers; James Val; Mitchell L. Scott; Claudine J. Moutou; Ian Oliver (Conservation Biology, 2025)
Expert judgment underpins assessment of threatened ecosystems. However, experts are often narrowly defined, and variability in their judgments may be substantial. Models built from structured elicitation with large diverse expert panels can contribute to more consistent and transparent decision‐making. We conducted a structured elicitation under a broad definition of expertise to examine variation in judgments of ecosystem viability and collapse in a critically endangered ecosystem. We explored whether variation in judgments among 83 experts was related to affiliation and management expertise and assessed performance of an average model based on common ecosystem indicators. There were systematic differences among individuals, much of which were not explained by affiliation or expertise. However, of the individuals affiliated with government, those in conservation and environmental departments were more likely to determine a patch was viable than those in agriculture and rural land management. Classification errors from an average model, in which all individuals were weighted equally, were highest among government agriculture experts (27%) and lowest among government conservation experts (12%). Differences were mostly cases in which the average model predicted a patch was viable but the individual thought it was not. These differences arose primarily for areas that were grazed or cleared of mature trees. These areas are often the target of restoration, but they are also valuable for agriculture. These results highlight the potential for conflicting advice and disagreement about policies and actions for conserving and restoring threatened ecosystems. Although adoption of an average model can improve consistency of ecosystem assessment, it can fail to capture and convey diverse opinions held by experts. Structured elicitation and models of ecosystem viability play an important role in providing data‐driven evidence of where differences arise among experts to support engagement and discussion among stakeholders and decision makers and to improve the management of threatened ecosystems.

Ocean color anomaly detection to estimate surface Calanus finmarchicus concentration in the Gulf of Maine - Rebekah Shunmugapandi; Cait L. McCarry; David McKee; Catherine Mitchell (Frontiers in Marine Science, 2025)
The planktonic copepod, Calanus finmarchicus , plays a pivotal role in the Gulf of Maine (GoM) pelagic food web as a primary food source for many species, including the critically endangered North Atlantic right whale (NARW). Thus, observing C. finmarchicus on a Gulf-wide scale via satellite could be beneficial for understanding changes in the migration patterns of the NARW. This study investigated the application of ocean color remote sensing to detect the surface population levels of C. finmarchicus in the GoM. Using remote sensing reflectance data from the MODIS Aqua sensor, we processed enhanced RGB (eRGB) imagery to detect and quantify the presence of C. finmarchicus , which is identifiable by its red astaxanthin pigment. This study employed a refined approach from the method originally developed off the coast of Norway, which integrates eRGB imagery and radiative transfer modeling to generate optical anomaly maps that are used for quantifying surface C. finmarchicus concentrations in the GoM. We detected surface swarms of C. finmarchicus in the ocean color imagery and estimated their concentrations. However, due to the method’s reliance on astaxanthin/red pigment-based detection, other astaxanthin-rich red/brown plankton were misidentified as C. finmarchicus . While the approach presented is effective for identifying astaxanthin anomalies in ocean color and holds potential for quantifying the surface populations of C. finmarchicus , it requires local knowledge to accurately quantify the C. finmarchicus abundances.

Temperament and state-dependent behaviours in large herbivores - Heather N. Abernathy; Rebecca L. Levine; Yasaman N. Shakeri; Jaron T. Kolek; Brittany L. Wagler; Rachel A. Smiley; Rhiannon P. Jakopak; Mitchell J. Brunet; Rebekah T. Rafferty; Seth T. Rankins; Katey S. Huggler; Brandon Scurlock; et al. (Animal Behaviour, 2025)

Beyond nutrition: Exploring immune proteins, bioactive peptides, and allergens in cow and Arabian camel milk - Manujaya W. Jayamanna Mohottige; Angéla Juhász; Mitchell G. Nye-Wood; Katherine A. Farquharson; Utpal Bose; Michelle L. Colgrave (Food Chemistry, 2025)

A proposed screening strategy for evaluating the genotoxicity potential of botanicals and botanical extracts - Kristine L. Witt; Jan van Benthem; Tetyana Kobets; Guosheng Chen; Olaf Kelber; Julie Krzykwa; James T. MacGregor; Nan Mei; Constance A. Mitchell; Ivonne Rietjens; Zehra Sarigol-Kilic; Stephanie L. Smith-Roe; et al. (Food and Chemical Toxicology, 2025)

Narrow Margins: Aerobic Performance and Temperature Tolerance of Coral Reef Fishes Facing Extreme Thermal Variability - Grace O. Vaughan; Daniel M. Ripley; Matthew D. Mitchell; Dain McParland; Jacob L. Johansen; Holly A. Shiels; John A. Burt (Global Change Biology, 2025)
Climate change is driving rising average sea temperatures and the intensification of thermal variability. Tropical coral reef fishes have evolved under thermally stable conditions to function optimally within a narrow temperature range, with many currently living close to their upper thermal limits. However, recent work has demonstrated that some species possess additional capacity, such as reductions in basal metabolic rates (i.e., ‘plastic floors’), to compensate for the acute effects of thermal challenges when assessed over multigenerational timeframes. In this study, we use the ‘plastic floors and concrete ceilings’ hypothesis to generate and then test predictions regarding the thermal physiology of reef fishes in the world's hottest and most thermally variable coral reef ecosystem (southern Arabian/Persian Gulf). By comparing three species of reef fishes ( Scolopsis ghanam , Ecsenius pulcher and Cheilodipterus novemstriatus ) from the southern Arabian/Persian Gulf, with an annual temperature range of 18.0°C–36.5°C, to conspecifics from nearby but more thermally benign (~21.0°C–32.0°C) reefs in the Gulf of Oman, we find enhanced upper thermal limits and a broadening of the temperature performance curves for aerobic scope in the Arabian/Persian Gulf, but no evidence for changes in basal metabolic rates (‘plastic floors’). Despite these conserved increases in temperature tolerance, the summer thermal safety margins of Arabian/Persian Gulf fishes were 1.47°C lower than those of conspecifics from the Gulf of Oman, demonstrating that while the temperature tolerance of tropical coral reef fishes is somewhat plastic over multigenerational timeframes, its rate of change is likely insufficient to keep pace with the rising average temperatures and growing thermal variability expected under climate change.

Disease epidemics and species interactions: A manipulation of seasonal establishment of fungal diseases in an old field - Rita L. Grunberg; Fletcher W. Halliday; Kayleigh R. O'Keeffe; Brooklynn N. Joyner; Robert W. Heckman; Charles E. Mitchell (Ecology, 2025)
Many disease epidemics recur seasonally, and such seasonal epidemics can be shaped by species interactions among parasites, pathogens, or other microbes. Field experiments are a classic approach for understanding species interactions but are rarely used to study seasonal epidemics. Our research objective was to help fill this gap by manipulating the seasonal timing of the establishment of infectious diseases while tracking epidemics and other ecological responses. To do this, we conducted a multiyear field experiment in an old field in the Piedmont of North Carolina, USA, dominated by the grass species tall fescue ( Lolium arundinaceum (Schreb). Darbysh). In the field, tall fescue experienced seasonal epidemics of multiple foliar fungal diseases: anthracnose in spring, brown patch in mid‐summer, and crown rust in late summer to fall. In a fully randomized design, we applied four fungicide treatments to replicate plots of intact vegetation in specific seasons to manipulate the timing of disease epidemics. One treatment was designed to delay the establishment of anthracnose until mid‐summer, and another to delay the establishment of both anthracnose and brown patch until fall. In a third treatment, fungicide was applied year‐round, and, in a fourth treatment, fungicide was never applied. The experiment comprised 64 plots, each 2 m × 2 m, surveyed from May 2017 to February 2020. Here, we report a dataset documenting responses in the community structure of both plants and foliar fungi. To track disease prevalence in the host population across seasons and years, this dataset includes monthly leaf‐level observations of the disease status of over 100,000 leaves. To quantify transmission and investigate within‐host pathogen interactions, we longitudinally surveyed disease status in host individuals of known age at least weekly over two growing seasons. Finally, the dataset includes annual data on infection prevalence of the systemic fungal endophyte Epichloë coenophiala , community‐level aboveground plant biomass, and plant community cover. These data can be used for meta‐analyses, comparisons, and syntheses across systems as ecologists seek to predict and mechanistically understand seasonal disease epidemics. There are no copyrights on the dataset, and we request that users of this dataset cite this paper in all publications resulting from its use.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

In situ staining with antibodies cross-reactive in pigs, cattle, and white-tailed deer facilitates understanding of biological tissue status and immunopathology - Jayne E. Wiarda; Eraldo L. Zanella; Adrienne L. Shircliff; Eric D. Cassmann; Crystal L. Loving; Alexandra C. Buckley; Mitchell V. Palmer (Veterinary Immunology and Immunopathology, 2025)

Using Community Composition and Successional Theory to Guide Site‐Specific Coral Reef Management - Orion S. McCarthy; Emily L. A. Kelly; Anela K. Akiona; Samantha M. Clements; Tatiana Martinez; Nicole E. Pedersen; Cole Peralto; Sarah L. Romero; Mitchell H. Smelser; Kristy Wong Stone; Russell T. Sparks; Jennifer E. Smith (Global Change Biology, 2025)
High spatial or temporal variability in community composition makes it challenging for natural resource managers to predict ecosystem trajectories at scales relevant to management. This is commonly the case in nearshore marine environments, where the frequency and intensity of disturbance events vary at the sub‐kilometer to meter scale, creating a patchwork of successional stages within a single ecosystem. The successional stage of a community impacts its stability, recovery potential, and trajectory over time in predictable ways. Here we demonstrate the value of successional theory for interpreting fine‐scale community heterogeneity using Hawaiian coral reefs as a case study. We tracked benthic community dynamics on 36 forereefs over a 6‐year period (2017–2023) that captures impacts from high surf events, a marine heatwave, and unprecedented shifts in human behavior due to the COVID‐19 pandemic. We document high spatial variation in benthic community composition that was only partially explained by island and environmental regime. Through hierarchical clustering, we identify three distinct community types that appear to represent different successional stages of reef development. Reefs belonging to the same community type exhibited similar rates of change in coral cover and structural complexity over time, more so than reefs located on the same island. Importantly, communities that were indicative of early succession (low coral cover reefs dominated by stress‐tolerant corals) were most likely to experience an increase in coral cover over time, while later‐stage successional communities were more likely to experience coral decline. Our findings highlight the influence of life history and successional stage on community trajectories. Accounting for these factors, not simply overall coral cover, is essential for designing effective management interventions. Site‐specific management that accounts for a community's unique composition and history of disturbance is needed to effectively conserve these important ecosystems.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Helicopter parenting: local-scale environment determines hiding and supervision in neonatal ungulates - Mitchell J. Brunet; Katey S. Huggler; Patrick W. Burke; Kevin L. Monteith (Animal Behaviour, 2024)

Reply to Beltaos (2024). Letter to the Editor regarding “Paleofloodscapes: Application of sediment source fingerprinting to track flood regime change over space and time at the Peace-Athabasca Delta, Canada” by Kay et al. (2024), Sci. Total Environ. 912 169538 - Mitchell L. Kay; Lauren A. MacDonald; Johan A. Wiklund; Cory A.M. Girard; Brent B. Wolfe; Roland I. Hall (Science of The Total Environment, 2024)

Inferences based on diatom compositions improve estimates of nutrient concentrations in streams - Lester L. Yuan; Richard M. Mitchell; Erik M. Pilgrim; Nathan J. Smucker (Science of The Total Environment, 2024)

Optimizing the detection of N-nitrosamine mutagenicity in the Ames test - Robert H. Heflich; Michelle E. Bishop; Roberta A. Mittelstaedt; Jian Yan; Sharon K. Guerrero; Audrey M. Sims; Kamela Mitchell; Nyosha Moore; Xilin Li; Nan Mei; Rosalie K. Elespuru; Sruthi T. King; et al. (Regulatory Toxicology and Pharmacology, 2024)

Botanical-induced toxicity: Liver injury and botanical-drug interactions. A report on a society of Toxicology Annual Meeting symposium - Igor Koturbash; R. Philip Yeager; Constance A. Mitchell; Stephen Ferguson; Victor J. Navarro; Mary F. Paine; Amy L. Roe (Regulatory Toxicology and Pharmacology, 2024)

Testing triple oxygen isotope preservation in the new OPEnS totalizer against conventional monthly rainfall collectors - L. Nicole Arellano; Emily J. Beverly; John S. Selker; Mitchell Nelke; Gurpreet Singh; Cara Walter (Chemical Geology, 2024)

The Calorimetric Electron Telescope (CALET) on the International Space Station: Results from the first eight years on orbit - Y. Akaike; O. Adriani; K. Asano; Y. Asaoka; E. Berti; G. Bigongiari; W.R. Binns; M. Bongi; P. Brogi; A. Bruno; N. Cannady; G. Castellini; et al. (Advances in Space Research, 2024)

Direct measurements of cosmic – Ray iron and nickel with CALET on the International Space Station - O. Adriani; Y. Akaike; K. Asano; Y. Asaoka; E. Berti; G. Bigongiari; W.R. Binns; M. Bongi; P. Brogi; A. Bruno; N. Cannady; G. Castellini; et al. (Advances in Space Research, 2024)

The effect of rhizosphere pH on removal of naphthenic acid fraction compounds from oil sands process-affected water in a willow hydroponic system - Mitchell E. Alberts; Ralph Hindle; Camryn Charriere; Amanda L. Schoonmaker; Heather Kaminsky; Douglas G. Muench (Science of The Total Environment, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The whole venom spectra: Venom evolution to bio-applications - Michela L. Mitchell (Toxicon, 2024)

Large structural estuaries: Their global distribution and morphology - Mitchell P. Baum; David M. Kennedy; Sarah L. McSweeney (Geomorphology, 2024)

A framework for national-scale coastal storm hazards early warning - Ian L. Turner; Christopher K. Leaman; Mitchell D. Harley; Mandi C. Thran; Daniel R. David; Kristen D. Splinter; Nashwan Matheen; Jeff E. Hansen; Michael V.W. Cuttler; Diana J.M. Greenslade; Stefan Zieger; Ryan J. Lowe (Coastal Engineering, 2024)

Using DNA metabarcoding to characterize national scale diatom-environment relationships and to develop indicators in streams and rivers of the United States - Nathan J. Smucker; Erik M. Pilgrim; Christopher T. Nietch; Leslie Gains-Germain; Charlie Carpenter; John A. Darling; Lester L. Yuan; Richard M. Mitchell; Amina I. Pollard (Science of The Total Environment, 2024)

Review of dose setting for the extended one-generation reproductive toxicity studies (OECD TG 443): Considerations on ECHA's dose level selection recommendations - Manon Beekhuijzen; Emily Richmond; Jason Manton; Pragati S. Coder; Katy Goyak; Rashin Ghaffari; Susan L. Makris; Steven Van Cruchten; Leah Zorrilla; Shermaine Mitchell-Ryan (Regulatory Toxicology and Pharmacology, 2024)

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16‑hydroxyestriol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Nisi Jiang; Catherine C. Kaczorowski; Navasuja Kumar; et al. (GeroScience, 2024)

Advancing Understanding of Chemical Exposures and Maternal-child Health Through the U.S. Environmental Influences on Child Health Outcomes (ECHO) Program: A Scoping Review - Emily S. Barrett; Jennifer L. Ames; Stephanie M. Eick; Alicia K. Peterson; Zorimar Rivera-Núñez; Anne P. Starling; Jessie P. Buckley; Barbara O‟Brien; Lisa Peterson; Patrick Parsons; Kannan Kurunthacalam; Manish Arora; et al. (Current Environmental Health Reports, 2024)
Purpose of Review Environmental chemical exposures may disrupt child development, with long-lasting health impacts. To date, U.S. studies of early environmental exposures have been limited in size and diversity, hindering power and generalizability. With harmonized data from over 60,000 participants representing 69 pregnancy cohorts, the National Institutes of Health’s Environmental influences on Child Health Outcomes (ECHO) Program is the largest study of U.S. children’s health. Here, we: (1) review ECHO-wide studies of chemical exposures and maternal-child health; and (2) outline opportunities for future research using ECHO data. Recent Findings As of early 2024, in addition to over 200 single-cohort (or award) papers on chemical exposures supported by ECHO, ten collaborative multi-cohort papers have been made possible by ECHO data harmonization and new data collection. Multi-cohort papers have examined prenatal exposure to per- and polyfluoroalkyl substances (PFAS), phthalates, phenols and parabens, organophosphate esters (OPEs), metals, melamine and aromatic amines, and emerging contaminants. They have primarily focused on describing patterns of maternal exposure or examining associations with maternal and infant outcomes; fewer studies have examined later child outcomes (e.g., autism) although follow up of enrolled ECHO children continues. The NICHD’s Data and Specimen Hub (DASH) database houses extensive ECHO data including over 470,000 chemical assay results and complementary data on priority outcome areas (pre, peri-, and postnatal, airway, obesity, neurodevelopment, and positive health), making it a rich resource for future analyses. Summary ECHO’s extensive data repository, including biomarkers of chemical exposures, can be used to advance our understanding of environmental influences on children’s health. Although few published studies have capitalized on these unique harmonized data to date, many analyses are underway with data now widely available.

Parental perceptions of body weight and appetite in infants and toddlers with cystic fibrosis - Sarah Ann Duck; Elena Jansen; Afroditi Papantoni; Aerial Sheltry; Daphne Koinis-Mitchell; Viren D’Sa; Sean Deoni; Timothy H. Moran; Robert L. Findling; Peter J. Mogayzel; Susan Carnell (Appetite, 2024)

Biological lags and market dynamics in vertically coordinated food supply chains: HPAI impacts on U.S. egg prices - James L. Mitchell; Jada M. Thompson; Trey Malone (Food Policy, 2024)

Benefits of calorie restriction in mice are mediated via energy imbalance, not absolute energy or protein intake - Daniel L. Smith; Sharon E. Mitchell; Maria S. Johnson; Victoria K. Gibbs; Stephanie Dickinson; Beate Henschel; Rui Li; Kathryn A. Kaiser; Daniella E. Chusyd; Andrew W. Brown; David B. Allison; John R. Speakman; et al. (GeroScience, 2024)
Caloric restriction (CR) results in reduced energy and protein intake, raising questions about protein restriction’s contribution to CR longevity benefits. We kept ad libitum ( AL )–fed male C57BL/6J mice at 27°C (AL27) and pair-fed (PF) mice at 22°C (22(PF27)). The 22(PF27) group was fed to match AL27 while restricted for calories due to cold-induced metabolism. The 22(PF27) mice had significantly lower body weight, lean mass, fat mass, leptin, IGF-1, and TNF-α levels than AL27 mice ( p <0.001 for all). Manipulations over ~11 weeks resulted in significant differences in body temperature, physical activity, and expression of key genes linked to hunger in the hypothalamus. Survival was significantly greater in 22(PF27) compared to AL27 overall ( p <0.001). CR in the context of equivalent energy and protein intake resulted in hormonal, metabolic, and physiological benefits and extended longevity. Hence, energy imbalance, rather than low energy or protein intake per se, mediates the benefits of CR.

Methane flux from transplanted soil monoliths depends on moisture, but not origin - Kendalynn A. Morris; Mitchell Smith; Vanessa L. Bailey; Roberta Bittencourt-Peixoto; Donnie J. Day; Nora Hamovit; Anya M. Hopple; Jaehyun Lee; Kaizad F. Patel; Peter Regier; Stephanie J. Wilson; Stephanie A. Yarwood; et al. (Soil Biology and Biochemistry, 2024)

Multistate outbreak of Salmonella Oranienburg infections linked to bulb onions imported from Mexico – United States, 2021 - Marvin R. Mitchell; Margaret Kirchner; Ben Schneider; Monica McClure; Karen P. Neil; Asma Madad; Temesgen Jemaneh; Mary Tijerina; Kurt Nolte; Allison Wellman; Daniel Neises; Arthur Pightling; et al. (Food Control, 2024)

The murine metastatic microenvironment of experimental brain metastases of breast cancer differs by host age in vivo: a proteomic study - Allison L. Hunt; Imran Khan; Alex M. L. Wu; Sasha C. Makohon-Moore; Brian L. Hood; Kelly A. Conrads; Tamara Abulez; Jonathan Ogata; Dave Mitchell; Glenn Gist; Julie Oliver; Debbie Wei; et al. (Clinical & Experimental Metastasis, 2024)

Lifespan effects in male UM-HET3 mice treated with sodium thiosulfate, 16-hydroxyestriol, and late-start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2024)

The influence of micro-scale thermal habitat on the movements of juvenile white sharks in their Southern California aggregation sites - Emily Spurgeon; Marten L. Thompson; Mitchell D. Alexander; James M. Anderson; Patrick T. Rex; Brian Stirling; Kevin Abbott; Christopher G. Lowe (Frontiers in Marine Science, 2024)
While juvenile white sharks (JWS) can display regional endothermy, the need to maintain internal temperatures within an energetically favorable range likely drives thermoregulatory movements to maximize growth and foraging efficiency. Many JWS from the northeastern Pacific population aggregate seasonally in nearshore nursery habitats throughout the Southern California Bight and historic data show that inter-seasonal movement patterns may be heavily dependent on ambient water temperature. However, the degree to which micro-scale (e.g., ~10 m 2 ) water temperature heterogeneity influences JWS three-dimensional movement within nearshore aggregation sites is unknown. High-resolution temperature and passive acoustic-telemetry geo-positional data were used to quantify how temperature and vertical thermal stratification influenced JWS movement using several modeling approaches. JWS selected for water temperatures between 16 – 22°C and depths shallower than 2 m. Sharks occupied deeper waters during dawn and dusk periods, and their distance from the seafloor and spatial orientation of their depth distribution was significantly related to the thermal structure of the water column across the monitored area. Tagged sharks remained above a 16°C thermal threshold and altered their horizontal and vertical distributions accordingly. While high-resolution movement and environmental data provide improved predictability of micro-scale habitat use and distribution, other variables such as prey distribution, behavior, and competition would further improve habitat use models for this highly mobile species.

Mission Monarch: engaging the Canadian public for the conservation of a species at risk - André-Philippe Drapeau Picard; Alessandro Dieni; Agathe Moreau; Greg W. Mitchell; Marian L. MacNair; Nicolas Casajus; Sonya Charest; Maxim Larrivée (Journal of Insect Conservation, 2024)

(R)-(+)-γ-Decalactone is Conserved in North America as a Pheromone Component of Osmoderma eremicola (Coleoptera: Scarabaeidae) and a Kairomone of Elater abruptus (Coleoptera: Elateridae) - Geryd L. Steffek; Anna S. Grommes; Lawrence M. Hanks; Robert F. Mitchell (Journal of Chemical Ecology, 2024)

The distinctive weathering crust habitat of a High Arctic glacier comprises discrete microbial micro‐habitats - Sara M. E. Rassner; Joseph M. Cook; Andrew C. Mitchell; Ian T. Stevens; Tristram D. L. Irvine‐Fynn; Andrew J. Hodson; Arwyn Edwards (Environmental Microbiology, 2024)
Sunlight penetrates the ice surfaces of glaciers and ice sheets, forming a water‐bearing porous ice matrix known as the weathering crust. This crust is home to a significant microbial community. Despite the potential implications of microbial processes in the weathering crust for glacial melting, biogeochemical cycles, and downstream ecosystems, there have been few explorations of its microbial communities. In our study, we used 16S rRNA gene sequencing and shotgun metagenomics of a Svalbard glacier surface catchment to characterise the microbial communities within the weathering crust, their origins and destinies, and the functional potential of the weathering crust metagenome. Our findings reveal that the bacterial community in the weathering crust is distinct from those in upstream and downstream habitats. However, it comprises two separate micro‐habitats, each with different taxa and functional categories. The interstitial porewater is dominated by Polaromonas , influenced by the transfer of snowmelt, and exported via meltwater channels. In contrast, the ice matrix is dominated by Hymenobacter , and its metagenome exhibits a diverse range of functional adaptations. Given that the global weathering crust area and the subsequent release of microbes from it are strongly responsive to climate projections for the rest of the century, our results underscore the pressing need to integrate the microbiome of the weathering crust with other communities and processes in glacial ecosystems.

Evaluating top‐down, bottom‐up, and environmental drivers of pelagic food web dynamics along an estuarine gradient - Tanya L. Rogers; Samuel M. Bashevkin; Christina E. Burdi; Denise D. Colombano; Peter N. Dudley; Brian Mahardja; Lara Mitchell; Sarah Perry; Parsa Saffarinia (Ecology, 2024)
Identification of the key biotic and abiotic drivers within food webs is important for understanding species abundance changes in ecosystems, particularly across ecotones where there may be strong variation in interaction strengths. Using structural equation models (SEMs) and four decades of integrated data from the San Francisco Estuary, we investigated the relative effects of top‐down, bottom‐up, and environmental drivers on multiple trophic levels of the pelagic food web along an estuarine salinity gradient and at both annual and monthly temporal resolutions. We found that interactions varied across the estuarine gradient and that the detectability of different interactions depended on timescale. For example, for zooplankton and estuarine fishes, bottom‐up effects appeared to be stronger in the freshwater upstream regions, while top‐down effects were stronger in the brackish downstream regions. Some relationships (e.g., bottom‐up effects of phytoplankton on zooplankton) were seen primarily at annual timescales, whereas others (e.g., temperature effects) were only observed at monthly timescales. We also found that the net effect of environmental drivers was similar to or greater than bottom‐up and top‐down effects for all food web components. These findings can help identify which trophic levels or environmental factors could be targeted by management actions to have the greatest impact on estuarine forage fishes and the spatial and temporal scale at which responses might be observed. More broadly, this study highlights how environmental gradients can structure community interactions and how long‐term data sets can be leveraged to generate insights across multiple scales.

Where the leatherbacks roam: movement behavior analyses reveal novel foraging locations along the Northwest Atlantic shelf - Mitchell J. Rider; Larisa Avens; Heather L. Haas; Joshua M. Hatch; Samir H. Patel; Christopher R. Sasso (Frontiers in Marine Science, 2024)
Leatherback sea turtles ( Dermochelys coriacea ) migrate along the east coast of the United States, traversing the South and Mid-Atlantic Bights (SAB and MAB) while traveling to and from well-known northern foraging areas off Southern New England (SNE) and Nova Scotia. However, there is limited information on leatherback movement behavior in these regions. To identify leatherback movement patterns, we fit hidden Markov models (HMMs) to satellite transmitter data from 52 leatherbacks tagged between 2017 and 2022 off the coasts of Massachusetts and North Carolina to estimate locations of area restricted searching (ARS) and transient behaviors. Depth-temperature profiles were then paired to locations associated with ARS behavior to understand the vertical use of the water column. We observed leatherbacks displaying ARS behavior in SNE as expected, but also in the MAB and SAB. The HMM results indicated that leatherbacks were primarily foraging in SNE between Nantucket and Long Island Sound and depth-temperature plots from ARS behavior on Nantucket Shoals implied turtles foraging throughout the entire water column. In the MAB, ARS behavior was concentrated between Cape Hatteras, North Carolina, and the mouth of Delaware Bay during the summer. Turtles were closely associated with a well-defined thermocline, but still appeared to dive to deeper cooler waters, which may be a sign of thermoregulatory behavior. There was evidence of foraging in the SAB along the coast as well as along the continental shelf edge. The ARS behavior we documented within the MAB and SAB is the first published empirical evidence that both areas may be important foraging grounds. Our results lay a path for future research to understand how leatherbacks use these areas and the potential anthropogenic threats encountered while moving through these regions.

‘Paleofloodscapes’: Application of sediment source fingerprinting to track flood regime change over space and time at the Peace-Athabasca Delta, Canada - Mitchell L. Kay; Lauren A. MacDonald; Johan A. Wiklund; Cory A.M. Girard; Brent B. Wolfe; Roland I. Hall (Science of The Total Environment, 2024)

Holocene fire dynamics and their climatic controls on the southern Cape coast of South Africa - A 7.2 ka multi-proxy record from the peatland Vankervelsvlei - Paul Strobel; Theresa Henning; Marcel Bliedtner; Stella G. Mosher; Humay Rahimova; Torsten Haberzettl; Kelly L. Kirsten; Eva Lehndorff; Mitchell J. Power; Michael Zech; Roland Zech (Quaternary Science Reviews, 2024)

Application of a Geochemically Informed Leak Detection (GILD) Model to CO2 Injection Sites on the United States Gulf Coast - Jiaan Wang; Wei Xiong; Mitchell J. Small; James B. Gardiner; Brian W. Stewart; R. Burt Thomas; J. Alexandra Hakala; Christina L. Lopano (International Journal of Greenhouse Gas Control, 2024)

From grain to malt: Tracking changes of ultra-low-gluten barley storage proteins after malting - Mahya Bahmani; Angéla Juhász; Utpal Bose; Mitchell G. Nye-Wood; Malcolm Blundell; Crispin A. Howitt; Michelle L. Colgrave (Food Chemistry, 2024)

Combining multiple investigative approaches to unravel functional responses to global change in the understorey of temperate forests - Dries Landuyt; Michael P. Perring; Haben Blondeel; Emiel De Lombaerde; Leen Depauw; Eline Lorer; Sybryn L. Maes; Lander Baeten; Laurent Bergès; Markus Bernhardt‐Römermann; Guntis Brūmelis; Jörg Brunet; et al. (Global Change Biology, 2024)
Plant communities are being exposed to changing environmental conditions all around the globe, leading to alterations in plant diversity, community composition, and ecosystem functioning. For herbaceous understorey communities in temperate forests, responses to global change are postulated to be complex, due to the presence of a tree layer that modulates understorey responses to external pressures such as climate change and changes in atmospheric nitrogen deposition rates. Multiple investigative approaches have been put forward as tools to detect, quantify and predict understorey responses to these global‐change drivers, including, among others, distributed resurvey studies and manipulative experiments. These investigative approaches are generally designed and reported upon in isolation, while integration across investigative approaches is rarely considered. In this study, we integrate three investigative approaches (two complementary resurvey approaches and one experimental approach) to investigate how climate warming and changes in nitrogen deposition affect the functional composition of the understorey and how functional responses in the understorey are modulated by canopy disturbance, that is, changes in overstorey canopy openness over time. Our resurvey data reveal that most changes in understorey functional characteristics represent responses to changes in canopy openness with shifts in macroclimate temperature and aerial nitrogen deposition playing secondary roles. Contrary to expectations, we found little evidence that these drivers interact. In addition, experimental findings deviated from the observational findings, suggesting that the forces driving understorey change at the regional scale differ from those driving change at the forest floor (i.e., the experimental treatments). Our study demonstrates that different approaches need to be integrated to acquire a full picture of how understorey communities respond to global change.

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Astaxanthin and meclizine extend lifespan in UM-HET3 male mice; fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate do not significantly affect lifespan in either sex at the doses and schedules used - David E. Harrison; Randy Strong; Peter Reifsnyder; Nadia Rosenthal; Ron Korstanje; Elizabeth Fernandez; Kevin Flurkey; Brett C. Ginsburg; Meredith D. Murrell; Martin A. Javors; Marisa Lopez-Cruzan; James F. Nelson; et al. (GeroScience, 2023)
In genetically heterogeneous (UM-HET3) mice produced by the CByB6F1 × C3D2F1 cross, the Nrf2 activator astaxanthin (Asta) extended the median male lifespan by 12% ( p = 0.003, log-rank test), while meclizine (Mec), an mTORC1 inhibitor, extended the male lifespan by 8% ( p = 0.03). Asta was fed at 1840 ± 520 (9) ppm and Mec at 544 ± 48 (9) ppm, stated as mean ± SE ( n ) of independent diet preparations. Both were started at 12 months of age. The 90th percentile lifespan for both treatments was extended in absolute value by 6% in males, but neither was significant by the Wang–Allison test. Five other new agents were also tested as follows: fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate. None of these increased lifespan significantly at the dose and method of administration tested in either sex. Amounts of dimethyl fumarate in the diet averaged 35% of the target dose, which may explain the absence of lifespan effects. Body weight was not significantly affected in males by any of the test agents. Late life weights were lower in females fed Asta and Mec, but lifespan was not significantly affected in these females. The male-specific lifespan benefits from Asta and Mec may provide insights into sex-specific aspects of aging.

Justice and injustice in “Modular, Adaptive and Decentralized” (MAD) water systems - Anais Delilah Roque; Amber Wutich; Sameer H. Shah; Cassandra L. Workman; Linda E. Méndez-Barrientos; Yasmina Choueiri; Lucas Belury; Charlayne Mitchell (Water Security, 2023)

The importance of expert selection when identifying threatened ecosystems - Samantha K. Travers; Josh Dorrough; Ian Shannon; James Val; Mitchell L. Scott; Claudine J. Moutou; Ian Oliver (Conservation Biology, 2023)
Identifying threatened ecosystem types is fundamental to conservation and management decision‐making. When identification relies on expert judgment, decisions are vulnerable to inconsistent outcomes and can lack transparency. We elicited judgements of the occurrence of a widespread, critically endangered Australian ecosystem from a diverse pool of 83 experts. We asked 4 questions. First, how many experts are required to reliably conclude that the ecosystem is present? Second, how many experts are required to build a reliable model for predicting ecosystem presence? Third, given expert selection can narrow the range opinions, if enough experts are selected, do selection strategies affect model predictions? Finally, does a diverse selection of experts provide better model predictions? We used power and sample size calculations with a finite population of 200 experts to calculate the number of experts required to reliably assess ecosystem presence in a theoretical scenario. We then used boosted regression trees to model expert elicitation of 122 plots based on real‐world data. For a reliable consensus (90% probability of correctly identifying presence and absence) in a relatively certain scenario (85% probability of occurrence), at least 17 experts were required. More experts were required when occurrence was less certain, and fewer were needed if permissible error rates were relaxed. In comparison, only ∼20 experts were required for a reliable model that could predict for a range of scenarios. Expert selection strategies changed modeled outcomes, often overpredicting presence and underestimating uncertainty. However, smaller but diverse pools of experts produced outcomes similar to a model built from all contributing experts. Combining elicited judgements from a diverse pool of experts in a model‐based decision support tool provided an efficient aggregation of a broad range of expertise. Such models can improve the transparency and consistency of conservation and management decision‐making, especially when ecosystems are defined based on complex criteria.

Conventional solid-state fermentation impacts the white lupin proteome reducing the abundance of allergenic peptides - Arineh Tahmasian; Roger Drew; James A. Broadbent; Angéla Juhász; Mitchell Nye-Wood; Michelle L. Colgrave (Food Chemistry, 2023)

Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

Immune cell composition varies by age, sex and exposure to social adversity in free-ranging Rhesus Macaques - Mitchell R. Sanchez Rosado; Nicole Marzan-Rivera; Marina M. Watowich; Andrea D. Negron-Del Valle; Petraleigh Pantoja; Melissa A. Pavez-Fox; Erin R. Siracusa; Eve B. Cooper; Josue E. Negron-Del Valle; Daniel Phillips; Angelina Ruiz-Lambides; Melween I. Martinez; et al. (GeroScience, 2023)

Parascaris spp. eggs shedding patterns in juvenile horses - Nichol E. Ripley; Holli S. Gravatte; Leah N. Britton; Sarah M. Davis; Grace M. Perrin; Shaelin Mitchell; Elizabeth K. Rexroat; Abigail L. Vetter; Emily E.S. Maron; Constance A. Finnerty; Victoria Stanton; Martin K. Nielsen (Veterinary Parasitology, 2023)

Life cycle cost, energy, and carbon emissions of molds for precast concrete: Exploring the impacts of material choices and additive manufacturing - Kristina O. Armstrong; Dipti Kamath; Xianhui Zhao; Mitchell L. Rencheck; Halil Tekinalp; Matthew Korey; Diana Hun; Soydan Ozcan (Resources, Conservation and Recycling, 2023)

Improving the rigor and utility of botanical toxicity studies: Recommended resources - Deval Patel; Barbara C. Sorkin; Constance A. Mitchell; Michelle R. Embry; Sharline Rina-Kong; Rebecca E. Adams; Emily R. DeTemple; Aalekhya Reddam; Stefan Gafner; Olaf Kelber; Cynthia V. Rider; Hellen Oketch-Rabah; et al. (Regulatory Toxicology and Pharmacology, 2023)

Evaluating Participant Recipe Changes in a Healthy Meal Kit Intervention for Families with Low Income - E. McNulty; K. Chambers; R. Zambrano; I. Ramirez; A. Mitchell; L. House; A. Mathews; K. Shelnutt (Journal of the Academy of Nutrition and Dietetics, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Maximizing soil organic carbon stocks under cover cropping: insights from long-term agricultural experiments in North America - Yajun Peng; Elizabeth L. Rieke; Inderjot Chahal; Charlotte E. Norris; Ken Janovicek; Jeffrey P. Mitchell; Kraig L. Roozeboom; Zachary D. Hayden; Jeffrey S. Strock; Stephen Machado; Virginia R. Sykes; Bill Deen; et al. (Agriculture, Ecosystems & Environment, 2023)

Trace element, rare earth element and trace carbon compounds in Subglacial Lake Whillans, West Antarctica - Clara Turetta; Elena Barbaro; Mark L. Skidmore; Andrea Gambaro; Alexander B. Michaud; Andrew C. Mitchell; Trista J. Vick-Majors; John C. Priscu; Carlo Barbante (Science of The Total Environment, 2023)

Forces, electric fields and currents at the subsolar martian MPB: MAVEN observations and multifluid MHD simulation - G. Boscoboinik; C. Bertucci; D. Gomez; C. Dong; L. Regoli; C. Mazelle; J. Halekas; J. Espley; C.M. Fowler; D. Mitchell; L. Andersson (Icarus, 2023)

Food web structure and energy flux dynamics, but not taxonomic richness, influence microbial ecosystem functions in a Sphagnum-dominated peatland - Vincent E.J. Jassey; Owen L. Petchey; Philippe Binet; Alexandre Buttler; Geneviève Chiapusio; Frédéric Delarue; Fatima Laggoun-Défarge; Daniel Gilbert; Edward A.D. Mitchell; Janna M. Barel (European Journal of Soil Biology, 2023)

“We’re always an afterthought”- Designing tobacco control campaigns for dissemination with and to LGBTQ +—serving community organizations: a thematic analysis - Shoba Ramanadhan; Meg Salvia; Elaine Hanby; Anna C. Revette; Madison K. Rivard; N. F. N. Scout; Julia Applegate; Bob Gordon; Ana Machado; Mitchell R. Lunn; Juno Obedin-Maliver; Jennifer Potter; et al. (Cancer Causes & Control, 2023)
Purpose Evidence-based health communication campaigns can support tobacco control and address tobacco-related inequities among lesbian, gay, bisexual, transgender, and queer (LGBTQ +) populations. Community organizations focused on LGBTQ + health (e.g., nonprofits, community centers, and community health centers) can be prime channels for delivering evidence-based health communication campaigns. However, it is unclear how to balance the goals of a) designing campaigns to support broad adoption/uptake and b) adaptation addressing the needs of diverse communities and contexts. As part of an effort to support “designing for dissemination,” we explored the key challenges and opportunities staff and leaders of LGBTQ + -serving community organizations encounter when adopting or adapting evidence-based health communication campaigns. Methods A team of researchers and advisory committee members conducted this study, many of whom have lived, research, and/or practice experience with LGBTQ + health. We interviewed 22 staff members and leaders of community organizations serving LGBTQ + populations in the US in early 2021. We used a team-based, reflexive thematic analysis approach. Results The findings highlight the challenges of attempting to use health communication campaigns misaligned with the assets and needs of organizations and community members. The three major themes identified were as follows: (1) available evidence-based health communication campaigns typically do not sufficiently center LGBTQ + communities, (2) negotiation regarding campaign utilization places additional burden on practitioners who have to act as “gatekeepers,” and (3) processes of using health communication campaigns often conflict with organizational efforts to engage community members in adoption and adaptation activities. Conclusions We offer a set of considerations to support collaborative design and dissemination of health communication campaigns to organizations serving LGBTQ + communities: (1) develop campaigns with and for LGBTQ + populations, (2) attend to the broader structural forces impacting campaign recipients, (3) support in-house testing and adaptations, and (4) increase access to granular data for community organizations.

A geochemically informed leak detection (GILD) model for CO2 injection sites - Jiaan Wang; Wei Xiong; James B. Gardiner; Brandon C. McAdams; Brian W. Stewart; R. Burt Thomas; J. Alexandra Hakala; Christina L. Lopano; Mitchell J. Small (Applied Geochemistry, 2023)

Interannual variability in dominant shoreline behaviour at an embayed beach - Raimundo Ibaceta; Mitchell D. Harley; Ian L. Turner; Kristen D. Splinter (Geomorphology, 2023)

Solar wind driven influences on the Martian oxygen corona: Constraints on atmospheric sputtering from a synthesis of MAVEN measurements during solar minimum - Robin Ramstad; David A. Brain; Yaxue Dong; Jasper S. Halekas; James M. McFadden; David L. Mitchell; Jared Espley; Francis G. Eparvier; Bruce M. Jakosky (Icarus, 2023)

A pair of cadmium-exposed zebrafish affect social behavior of the un-exposed majority - Delia S. Shelton; Zoe M. Dinges; Anuj Khemka; Delawrence J. Sykes; Piyumika S. Suriyampola; Dolores E.P. Shelton; Ploypenmas Boyd; Jeffrey R. Kelly; Myra Bower; Halima Amro; Stephen P. Glaholt; Mitchell B. Latta; et al. (Environmental Toxicology and Pharmacology, 2023)

Machine Learning–Based Identification of Target Groups for Thrombectomy in Acute Stroke - Fanny Quandt; Fabian Flottmann; Vince I. Madai; Anna Alegiani; Clemens Küpper; Lars Kellert; Adam Hilbert; Dietmar Frey; Thomas Liebig; Jens Fiehler; Mayank Goyal; Jeffrey L. Saver; et al. (Translational Stroke Research, 2023)
Whether endovascular thrombectomy (EVT) improves functional outcome in patients with large-vessel occlusion (LVO) stroke that do not comply with inclusion criteria of randomized controlled trials (RCTs) but that are considered for EVT in clinical practice is uncertain. We aimed to systematically identify patients with LVO stroke underrepresented in RCTs who might benefit from EVT. Following the premises that (i) patients without reperfusion after EVT represent a non-treated control group and (ii) the level of reperfusion affects outcome in patients with benefit from EVT but not in patients without treatment benefit, we systematically assessed the importance of reperfusion level on functional outcome prediction using machine learning in patients with LVO stroke treated with EVT in clinical practice ( N = 5235, German-Stroke-Registry) and in patients treated with EVT or best medical management from RCTs ( N = 1488, Virtual-International-Stroke-Trials-Archive). The importance of reperfusion level on outcome prediction in an RCT-like real-world cohort equaled the importance of EVT treatment allocation for outcome prediction in RCT data and was higher compared to an unselected real-world population. The importance of reperfusion level was magnified in patient groups underrepresented in RCTs, including patients with lower NIHSS scores (0–10), M2 occlusions, and lower ASPECTS (0–5 and 6–8). Reperfusion level was equally important in patients with vertebrobasilar as with anterior LVO stroke. The importance of reperfusion level for outcome prediction identifies patient target groups who likely benefit from EVT, including vertebrobasilar stroke patients and among patients underrepresented in RCT patients with low NIHSS scores, low ASPECTS, and M2 occlusions.

Shark depredation: future directions in research and management - J. D. Mitchell; J. M. Drymon; J. Vardon; P. G. Coulson; C. A. Simpfendorfer; S. B. Scyphers; S. M. Kajiura; K. Hoel; S. Williams; K. L. Ryan; A. Barnett; M. R. Heupel; et al. (Reviews in Fish Biology and Fisheries, 2023)
Shark depredation is a complex social-ecological issue that affects a range of fisheries worldwide. Increasing concern about the impacts of shark depredation, and how it intersects with the broader context of fisheries management, has driven recent research in this area, especially in Australia and the United States. This review synthesises these recent advances and provides strategic guidance for researchers aiming to characterise the occurrence of depredation, identify the shark species responsible, and test deterrent and management approaches to reduce its impacts. Specifically, the review covers the application of social science approaches, as well as advances in video camera and genetic methods for identifying depredating species. The practicalities and considerations for testing magnetic, electrical, and acoustic deterrent devices are discussed in light of recent research. Key concepts for the management of shark depredation are reviewed, with recommendations made to guide future research and policy development. Specific management responses to address shark depredation are lacking, and this review emphasizes that a “silver bullet” approach for mitigating depredation does not yet exist. Rather, future efforts to manage shark depredation must rely on a diverse range of integrated approaches involving those in the fishery (fishers, scientists and fishery managers), social scientists, educators, and other stakeholders.

Biomass Quality Responses to Selection for Increased Biomass Yield in Perennial Energy Grasses - Michael D. Casler; DoKyoung Lee; Robert B. Mitchell; Kenneth J. Moore; Paul R. Adler; R. Mark Sulc; Keith D. Johnson; Robert L. Kallenbach; Arvid R. Boe; Russell D. Mathison; Kim A. Cassida; Doohong Min; et al. (BioEnergy Research, 2023)

Uranus ring occultation observations: 1977–2006 - Richard G. French; Colleen A. McGhee-French; Mitchell Gordon; Richard L. Baron; Amanda S. Bosh; Marc W. Buie; Nancy Chanover; Mary Ann Clark; Edward W. Dunham; Linda M. French; Ian S. Glass; Jay D. Goguen; et al. (Icarus, 2023)

Ocean carbon from space: Current status and priorities for the next decade - Robert J.W. Brewin; Shubha Sathyendranath; Gemma Kulk; Marie-Hélène Rio; Javier A. Concha; Thomas G. Bell; Astrid Bracher; Cédric Fichot; Thomas L. Frölicher; Martí Galí; Dennis Arthur Hansell; Tihomir S. Kostadinov; et al. (Earth-Science Reviews, 2023)

Perverse outcomes from fencing fauna: Loss of antipredator traits in a havened mammal population - Natasha D. Harrison; Ben L. Phillips; Nicola J. Mitchell; Julia C. Wayne; Marika A. Maxwell; Colin G. Ward; Adrian F. Wayne (Biological Conservation, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Measuring the immeasurable: A structural equation modeling approach to assessing soil health - Tai McClellan Maaz; Ronald H. Heck; Christine Tallamy Glazer; Mitchell K. Loo; Johanie Rivera Zayas; Aleric Krenz; Tanner Beckstrom; Susan E. Crow; Jonathan L. Deenik (Science of The Total Environment, 2023)

Carabid specialists respond differently to nonnative plant invasion in urban forests - J. Christina Mitchell; Vincent D’Amico; Tara L. E. Trammell; Steven D. Frank (Urban Ecosystems, 2023)

Toward Collaborative Adaptation: Assessing Impacts of Coastal Flooding at the Watershed Scale - Allison Mitchell; Anamaria Bukvic; Yang Shao; Jennifer L. Irish; Daniel L. McLaughlin (Environmental Management, 2023)

The morphology, functionality, and longevity of a novel all human hepatic cell-based tri-culture system - Jessica R. Weaver; Justin J. Odanga; Kristina K. Wolf; Stephanie Piekos; Mercedes Biven; Mitchell Taub; Jessica LaRocca; Cody Thomas; Alexander Byer-Alcorace; Jingsong Chen; Jung Bok Lee; Edward L. LeCluyse (Toxicology in Vitro, 2023)

An age-depth model and revised stratigraphy of vertebrate-bearing units in Natural Trap Cave, Wyoming - David M. Lovelace; Cory M. Redman; Thomas A. Minckley; Blaine W. Schubert; Shannon Mahan; John R. Wood; Jenny L. McGuire; Juan Laden; Kathleen Bitterman; Holly Heiniger; Lindsey Fenderson; Alan Cooper; et al. (Quaternary International, 2023)

Neither myonuclear accretion nor a myonuclear domain size ceiling is a feature of the attenuated hypertrophic potential of aged human skeletal muscle - Matthew S. Brook; Daniel J. Wilkinson; Janelle Tarum; Kyle W. Mitchell; Jonathan L. Lund; Bethan E. Phillips; Nathaniel J. Szewczyk; Fawzi Kadi; Paul L. Greenhaff; Ken Smith; Philip J. Atherton (GeroScience, 2023)
Ageing limits growth capacity of skeletal muscle (e.g. in response to resistance exercise), but the role of satellite cell (SC) function in driving this phenomenon is poorly defined. Younger (Y) (~ 23 years) and older (O) men (~ 69 years) (normal-weight BMI) underwent 6 weeks of unilateral resistance exercise training (RET). Muscle biopsies were taken at baseline and after 3-/6-week training. We determined muscle size by fibre CSA (and type), SC number, myonuclei counts and DNA synthesis (via D 2 O ingestion). At baseline, there were no significant differences in fibre areas between Y and O. RET increased type I fibre area in Y from baseline at both 3 weeks and 6 weeks (baseline: 4509 ± 534 µm 2 , 3 weeks; 5497 ± 510 µm 2 P < 0.05, 6 weeks; 5402 ± 352 µm 2 P < 0.05), whilst O increased from baseline at 6 weeks only (baseline 5120 ± 403 µm 2 , 3 weeks; 5606 ± 620 µm 2 , 6 weeks; 6017 ± 482 µm 2 P < 0.05). However, type II fibre area increased from baseline in Y at both 3 weeks and 6 weeks (baseline: 4949 ± 459 µm 2 , 3 weeks; 6145 ± 484 µm 2 ( P < 0.01), 6 weeks; 5992 ± 491 µm 2 ( P < 0.01), whilst O showed no change (baseline 5210 ± 410 µm 2 , 3 weeks; 5356 ± 535 µm 2 ( P = 0.9), 6 weeks; 5857 ± 478 µm 2 ( P = 0.1). At baseline, there were no differences in fibre myonuclei number between Y and O. RET increased type I fibre myonuclei number from baseline in both Y and O at 3 weeks and 6 weeks with RET (younger: baseline 2.47 ± 0.16, 3 weeks; 3.19 ± 0.16 ( P < 0.001), 6 weeks; 3.70 ± 0.29 ( P < 0.0001); older: baseline 2.29 ± 0.09, 3 weeks; 3.01 ± 0.09 ( P < 0.001), 6 weeks; 3.65 ± 0.18 ( P < 0.0001)). Similarly, type II fibre myonuclei number increased from baseline in both Y and O at 3 weeks and 6 weeks (younger: baseline 2.49 ± 0.14, 3 weeks; 3.31 ± 0.21 ( P < 0.001), 6 weeks; 3.86 ± 0.29 ( P < 0.0001); older: baseline 2.43 ± 0.12, 3 weeks; 3.37 ± 0.12 ( P < 0.001), 6 weeks; 3.81 ± 0.15 ( P < 0.0001)). DNA synthesis rates %.d −1 exhibited a main effect of training but no age discrimination. Declines in myonuclei addition do not underlie impaired muscle growth capacity in older humans, supporting ribosomal and proteostasis impairments as we have previously reported.

Development of an enzyme-linked immunosorbent assay for the diagnosis of feline tuberculosis - Jordan L. Mitchell; Chris Wilson; Janet E. Alexander; Shelley G. Rhodes; Danièlle A. Gunn-Moore; Jayne C. Hope (Veterinary Immunology and Immunopathology, 2023)

Paleolimnological evaluation of metal(loid) enrichment from oil sands and gold mining operations in northwestern Canada - Mitchell L. Kay; Izabela Jasiak; Wynona H. Klemt; Johan A. Wiklund; Jelle A. Faber; Lauren A. MacDonald; James V.K. Telford; Cory A.M. Savage; Colin A. Cooke; Brent B. Wolfe; Roland I. Hall (Environmental Research, 2023)

Mainstreaming germline genetic testing for patients with pancreatic cancer increases uptake - Mitchell L. Ramsey; Jewel Tomlinson; Rachel Pearlman; Laith Abushahin; Amber Aeilts; Hui-Zi Chen; Yan Chen; Ashley Compton; Rifat Elkhatib; Levi Geiger; John Hays; Joanne Jeter; et al. (Familial Cancer, 2023)

Improving multi-decadal coastal shoreline change predictions by including model parameter non-stationarity - Raimundo Ibaceta; Kristen D. Splinter; Mitchell D. Harley; Ian L. Turner (Frontiers in Marine Science, 2022)
Our ability to predict sandy shoreline evolution resulting from future changes in regional wave climates is critical for the sustainable management of coastlines worldwide. To this end, the present generation of simple and efficient semi-empirical shoreline change models have shown good skill at predicting shoreline changes from seasons up to several years at a number of diverse sites around the world. However, a key limitation of these existing approaches is that they rely on time-invariant model parameters, and assume that beaches will evolve within constrained envelopes of variability based on past observations. This raises an interesting challenge because the expected future variability in key meteocean and hydrodynamic drivers of shoreline change are likely to violate this ‘stationary’ approach to longer-term shoreline change prediction. Using a newly available, multi-decadal (28-year) dataset of satellite-derived shorelines at the Gold Coast, Australia, this contribution presents the first attempt to improve multi-decadal shoreline change predictions by allowing the magnitude of the shoreline model parameters to vary in time. A data assimilation technique (Ensemble Kalman Filter, EnKF) embedded within the well-established ShoreFor shoreline change model is first applied to a 14-year training period of approximately fortnightly shoreline observations, to explore temporal variability in model parameters. Then, the magnitudes of these observed non-stationary parameters are modelled as a function of selected wave climate covariates, representing the underlying seasonal to interannual variability in wave forcing. These modelled time-varying parameters are then incorporated into the shoreline change model and tested over the complete 28-year dataset. This new inclusion of non-stationary model parameters that are directly modelled as a function of the underlying wave forcing and corresponding time scales of beach response, is shown to outperform the multi-decadal predictions obtained by applying the conventional stationary approach (RMSE non-stationary = 11.1 m; RMSE stationary = 254.3 m). Based on these results, it is proposed that a non-stationary approach to shoreline change modelling can reduce the uncertainty associated with the misspecification of physical processes driving shoreline change and should be considered for future shoreline change predictions.

Streptomyces spiramenti sp. nov., isolated from a deep-sea microbial mat - Rachel M. Loughran; Caitlin M. Diefendorf; Jassmine R. Reill-VanSise; Edward A. Mitchell; Oliver B. Vining; David A. Gallegos; Gregory Miller; Marc J. Koyack; David K. Oline; Orion S. Rivers; Blake Ushijima; Jimmy H. Saw; et al. (Archives of Microbiology, 2022)

Breeding oat for resistance to the crown rust pathogen Puccinia coronata f. sp. avenae: achievements and prospects - R. F. Park; W. H. P. Boshoff; A. L. Cabral; J. Chong; J. A. Martinelli; M. S. McMullen; J. W. Mitchell Fetch; E. Paczos-Grzęda; E. Prats; J. Roake; S. Sowa; L. Ziems; et al. (Theoretical and Applied Genetics, 2022)
Crown rust, caused by Puccinia coronata f. sp. avenae ( Pca ), is a significant impediment to global oat production. Some 98 alleles at 92 loci conferring resistance to Pca in Avena have been designated; however, allelic relationships and chromosomal locations of many of these are unknown. Long-term monitoring of Pca in Australia, North America and elsewhere has shown that it is highly variable even in the absence of sexual recombination, likely due to large pathogen populations that cycle between wild oat communities and oat crops. Efforts to develop cultivars with genetic resistance to Pca began in the 1950s. Based almost solely on all all-stage resistance, this has had temporary benefits but very limited success. The inability to eradicate wild oats, and their common occurrence in many oat growing regions, means that future strategies to control Pca must be based on the assumption of a large and variable prevailing pathogen population with high evolutionary potential, even if cultivars with durable resistance are deployed and grown widely. The presence of minor gene, additive APR to Pca in hexaploid oat germplasm opens the possibility of pyramiding several such genes to give high levels of resistance. The recent availability of reference genomes for diploid and hexaploid oat will undoubtedly accelerate efforts to discover, characterise and develop high throughput diagnostic markers to introgress and pyramid resistance to Pca in high yielding adapted oat germplasm.

The distribution of mycosporine-like amino acids in phytoplankton across a Southern Ocean transect - Elliot L. Weiss; Mattias Rolf Cape; B. Jack Pan; Maria Vernet; Chase C. James; Tim J. Smyth; Sun-Yong Ha; José L. Iriarte; B. Greg Mitchell (Frontiers in Marine Science, 2022)
Interactions between phytoplankton and ultraviolet radiation (UVR: 280 – 400 nm) are undergoing changes dictated by variability in ocean temperature, the depth of mixed layers, nutrient availability, and the thickness of the ozone layer. There are a variety of mechanisms for phytoplankton to cope with UVR stress, one of the most prevalent being the presence of mycosporine-like amino acids (MAAs). Despite the importance of these molecules to phytoplankton fitness under UVR stress, knowledge of the diversity and distribution of these molecules in the world’s oceans is relatively limited. Here, the composition and distribution of MAAs in phytoplankton were examined in a transect across the Southern Ocean, crossing multiple fronts, from eastern New Zealand to the West Antarctic Peninsula in March and April of 2018. The highest concentration of MAAs (> 0.2 μg/L) was found between 50 and 60°S, as well as along a longitudinal gradient between 137.47 and 144.78°W. A strong correlation was found between a model of the preceding month’s UVR dosage experienced in the mixed layer and the ratio of MAAs to chlorophyll-a across the transect, indicating a relationship between the integrated history of light exposure and phytoplankton physiology. Haptophytes accounted for the majority of biomass north of the polar front (PF) and were strongly correlated with a diversity of MAAs. South of the PF a transition to a community dominated by diatoms was observed, with community composition changes strongly correlated to porphyra-334 concentrations. The data presented here provide a baseline for MAA abundance and association with specific phytoplankton taxa across the Southern Ocean amid a changing climate.

How Machine Learning is Powering Neuroimaging to Improve Brain Health - Nalini M. Singh; Jordan B. Harrod; Sandya Subramanian; Mitchell Robinson; Ken Chang; Suheyla Cetin-Karayumak; Adrian Vasile Dalca; Simon Eickhoff; Michael Fox; Loraine Franke; Polina Golland; Daniel Haehn; et al. (Neuroinformatics, 2022)
This report presents an overview of how machine learning is rapidly advancing clinical translational imaging in ways that will aid in the early detection, prediction, and treatment of diseases that threaten brain health. Towards this goal, we aresharing the information presented at a symposium, “Neuroimaging Indicators of Brain Structure and Function - Closing the Gap Between Research and Clinical Application”, co-hosted by the McCance Center for Brain Health at Mass General Hospital and the MIT HST Neuroimaging Training Program on February 12, 2021. The symposium focused on the potential for machine learning approaches, applied to increasingly large-scale neuroimaging datasets, to transform healthcare delivery and change the trajectory of brain health by addressing brain care earlier in the lifespan. While not exhaustive, this overview uniquely addresses many of the technical challenges from image formation, to analysis and visualization, to synthesis and incorporation into the clinical workflow. Some of the ethical challenges inherent to this work are also explored, as are some of the regulatory requirements for implementation. We seek to educate, motivate, and inspire graduate students, postdoctoral fellows, and early career investigators to contribute to a future where neuroimaging meaningfully contributes to the maintenance of brain health.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

The genetic basis for panicle trait variation in switchgrass (Panicum virgatum) - Li Zhang; Alice MacQueen; Xiaoyu Weng; Kathrine D. Behrman; Jason Bonnette; John L. Reilley; Francis M. Rouquette; Philip A. Fay; Yanqi Wu; Felix B. Fritschi; Robert B. Mitchell; David B. Lowry; et al. (Theoretical and Applied Genetics, 2022)
Key message We investigate the genetic basis of panicle architecture in switchgrass in two mapping populations across a latitudinal gradient, and find many stable, repeatable genetic effects and limited genetic interactions with the environment. Abstract Grass species exhibit large diversity in panicle architecture influenced by genes, the environment, and their interaction. The genetic study of panicle architecture in perennial grasses is limited. In this study, we evaluate the genetic basis of panicle architecture including panicle length, primary branching number, and secondary branching number in an outcrossed switchgrass QTL population grown across ten field sites in the central USA through multi-environment mixed QTL analysis. We also evaluate genetic effects in a diversity panel of switchgrass grown at three of the ten field sites using genome-wide association (GWAS) and multivariate adaptive shrinkage. Furthermore, we search for candidate genes underlying panicle traits in both of these independent mapping populations. Overall, 18 QTL were detected in the QTL mapping population for the three panicle traits, and 146 unlinked genomic regions in the diversity panel affected one or more panicle trait. Twelve of the QTL exhibited consistent effects (i.e., no QTL by environment interactions or no QTL × E), and most (four of six) of the effects with QTL × E exhibited site-specific effects. Most (59.3%) significant partially linked diversity panel SNPs had significant effects in all panicle traits and all field sites and showed pervasive pleiotropy and limited environment interactions. Panicle QTL co-localized with significant SNPs found using GWAS, providing additional power to distinguish between true and false associations in the diversity panel.

Quality of Life Changes Following the Onset of Cerebellar Ataxia: Symptoms and Concerns Self-reported by Ataxia Patients and Informants - Michelle R. Joyce; Prianca A. Nadkarni; Sharif I. Kronemer; Michael J. Margron; Mitchell B. Slapik; Owen P. Morgan; Liana S. Rosenthal; Chiadi U. Onyike; Cherie L. Marvel (The Cerebellum, 2022)

Novel Fusarium wilt resistance genes uncovered in natural and cultivated strawberry populations are found on three non-homoeologous chromosomes - Dominique D. A. Pincot; Mitchell J. Feldmann; Michael A. Hardigan; Mishi V. Vachev; Peter M. Henry; Thomas R. Gordon; Marta Bjornson; Alan Rodriguez; Nicolas Cobo; Randi A. Famula; Glenn S. Cole; Gitta L. Coaker; et al. (Theoretical and Applied Genetics, 2022)
Key Message Several Fusarium wilt resistance genes were discovered, genetically and physically mapped, and rapidly deployed via marker-assisted selection to develop cultivars resistant to Fusarium oxysporum f. sp. fragariae , a devastating soil-borne pathogen of strawberry . Abstract Fusarium wilt, a soilborne disease caused by Fusarium oxysporum f. sp. fragariae , poses a significant threat to strawberry ( Fragaria $$×$$ × ananassa ) production in many parts of the world. This pathogen causes wilting, collapse, and death in susceptible genotypes. We previously identified a dominant gene ( FW1 ) on chromosome 2B that confers resistance to race 1 of the pathogen, and hypothesized that gene-for-gene resistance to Fusarium wilt was widespread in strawberry. To explore this, a genetically diverse collection of heirloom and modern cultivars and octoploid ecotypes were screened for resistance to Fusarium wilt races 1 and 2. Here, we show that resistance to both races is widespread in natural and domesticated populations and that resistance to race 1 is conferred by partially to completely dominant alleles among loci ( FW1 , FW2 , FW3 , FW4 , and FW5 ) found on three non-homoeologous chromosomes (1A, 2B, and 6B). The underlying genes have not yet been cloned and functionally characterized; however, plausible candidates were identified that encode pattern recognition receptors or other proteins known to confer gene-for-gene resistance in plants. High-throughput genotyping assays for SNPs in linkage disequilibrium with FW1 - FW5 were developed to facilitate marker-assisted selection and accelerate the development of race 1 resistant cultivars. This study laid the foundation for identifying the genes encoded by FW1-FW5 , in addition to exploring the genetics of resistance to race 2 and other races of the pathogen, as a precaution to averting a Fusarium wilt pandemic.

FDA Approaches in Monitoring Drug Quality, Forces Impacting the Drug Quality, and Recent Alternative Strategies to Assess Quality in the US Drug Supply - Philip J. Almeter; James T. Isaacs; Aaron N. Hunter; Bradley S. Henderson; Thomas Platt; Billie J. Mitchell; David Do; Alyssa B. Brainard; Joshua E. Brown; Rachael M. Stone; Bao-Han Nguyen; Matthew F. Warren; et al. (Journal of Pharmaceutical Innovation, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Rastogi; Sunny Nguyen; et al. (GeroScience, 2022)

Behavior of potentially toxic elements from stoker-boiler fly ash in Interior Alaska: paired batch leaching and solid-phase characterization - Kyle P. Milke; Kiana L. Mitchell; Sarah M. Hayes; Carlin J. Green; Jennifer J. Guerard (Environmental Science and Pollution Research, 2022)
Despite significant investigation of fly ash spills and mineralogical controls on the release of potentially toxic elements (PTEs) from fly ash, interactions with the surficial environment remain relatively poorly understood. We conducted 90-day batch leaching studies with paired analysis of supernatant and solid-phase mineralogy to assess the elemental release and transformation of fly ash upon reaction with aquatic media (18 MΩ cm −1 water and simulated rainwater). The fly ash in this study, collected from the University of Alaska Fairbanks stoker-boiler power plant, is high in unburned carbon (~20% LOI) and highly enriched in several PTEs relative to the upper continental crust. Supernatant concentrations of oxyanion-forming elements (e.g., As, Se, Mo, Sb) remained relatively low and constant, suggesting equilibrium with the solid phase, possibly ettringite [Ca 6 Al 2 (SO 4 ) 3 (OH) 12 •26H 2 O], which is known to incorporate and sorb oxyanion-forming PTEs and was identified by X-ray diffraction. Synthetic precipitation leaching procedure (SPLP) results failed to capture important temporal trends. Lead and Ba supernatant concentrations consistently exceeded drinking water standards, as well as others upon exposure to simulated physiological solutions. Seven-day experiments with dissolved organic matter-isolate solutions indicated that for certain elements, liberation was influenced by carbon concentration and/or the identity of the isolate. Overall, this paired approach can serve as a model for future studies, bridging existing gaps between batch leaching and single-element mineralogical, sorption, or speciation studies.

Genomic evidence of an ancient inland temperate rainforest in the Pacific Northwest of North America - Megan Ruffley; Megan L. Smith; Anahí Espíndola; Daniel F. Turck; Niels Mitchell; Bryan Carstens; Jack Sullivan; David C. Tank (Molecular Ecology, 2022)
The disjunct temperate rainforests of the Pacific Northwest of North America (PNW) are characterized by late‐successional dominant tree species Thuja plicata (western redcedar) and Tsuga heterophylla (western hemlock). The demographic histories of these species, along with the PNW rainforest ecosystem in its entirety, have been heavily impacted by geological and climatic changes the PNW has experienced over the last 5 million years, including mountain orogeny and repeated Pleistocene glaciations. These environmental events have ultimately shaped the history of these species, with inland populations potentially being extirpated during the Pleistocene glaciations. Here, we collect genomic data for both species across their ranges to test multiple demographic models, each reflecting a different phylogeographical hypothesis on how the ecosystem‐dominating species may have responded to dramatic climatic change. Our results indicate that inland and coastal populations in both species diverged ~2.5 million years ago in the early Pleistocene and experienced decreases in population size during glacial cycles, with subsequent population expansion. Importantly, we found evidence for gene flow between coastal and inland populations during the mid‐Holocene. It is likely that intermittent migration in these species during this time has prevented allopatric speciation via genetic drift alone. In conclusion, our results from combining genomic data and demographic inference procedures establish that populations of the ecosystem dominants Thuja plicata and Tsuga heterophylla persisted in refugia located in both the coastal and inland regions of the PNW throughout the Pleistocene, with populations expanding and contracting in response to glacial cycles with occasional gene flow.

Perceptions of and barriers to cancer screening by the sexual and gender minority community: a glimpse into the health care disparity - Joseph Lombardo; Kevin Ko; Ayako Shimada; Nicolas Nelson; Christopher Wright; Jerry Chen; Alisha Maity; Marissa L. Ruggiero; Scott Richard; Dimitrios Papanagnou; Edith Mitchell; Amy Leader; et al. (Cancer Causes & Control, 2022)

Description of two new bird species from the Meratus Mountains of southeast Borneo, Indonesia - Mohammad Irham; Tri Haryoko; Subir B. Shakya; Simon L. Mitchell; Ryan C. Burner; Carlos Bocos; James A. Eaton; Frank E. Rheindt; Suparno Suparno; Frederick H. Sheldon; Dewi M. Prawiradilaga (Journal of Ornithology, 2022)

Ocean warming alters the distributional range, migratory timing, and spatial protections of an apex predator, the tiger shark ( Galeocerdo cuvier ) - Neil Hammerschlag; Laura H. McDonnell; Mitchell J. Rider; Garrett M. Street; Elliott L. Hazen; Lisa J. Natanson; Camilla T. McCandless; Melanie R. Boudreau; Austin J. Gallagher; Malin L. Pinsky; Ben Kirtman (Global Change Biology, 2022)
Given climate change threats to ecosystems, it is critical to understand the responses of species to warming. This is especially important in the case of apex predators since they exhibit relatively high extinction risk, and changes to their distribution could impact predator–prey interactions that can initiate trophic cascades. Here we used a combined analysis of animal tracking, remotely sensed environmental data, habitat modeling, and capture data to evaluate the effects of climate variability and change on the distributional range and migratory phenology of an ectothermic apex predator, the tiger shark ( Galeocerdo cuvier ). Tiger sharks satellite tracked in the western North Atlantic between 2010 and 2019 revealed significant annual variability in the geographic extent and timing of their migrations to northern latitudes from ocean warming. Specifically, tiger shark migrations have extended farther poleward and arrival times to northern latitudes have occurred earlier in the year during periods with anomalously high sea‐surface temperatures. A complementary analysis of nearly 40 years of tiger shark captures in the region revealed decadal‐scale changes in the distribution and timing of shark captures in parallel with long‐term ocean warming. Specifically, areas of highest catch densities have progressively increased poleward and catches have occurred earlier in the year off the North American shelf. During periods of anomalously high sea‐surface temperatures, movements of tracked sharks shifted beyond spatial management zones that had been affording them protection from commercial fishing and bycatch. Taken together, these study results have implications for fisheries management, human–wildlife conflict, and ecosystem functioning.

Can a key boreal Calanus copepod species now complete its life-cycle in the Arctic? Evidence and implications for Arctic food-webs - Geraint A. Tarling; Jennifer J. Freer; Neil S. Banas; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn B. Cook; Finlo R. Cottier; Malin Daase; Magnus L. Johnson; Kim S. Last; Penelope K. Lindeque; et al. (Ambio, 2022)
The changing Arctic environment is affecting zooplankton that support its abundant wildlife. We examined how these changes are influencing a key zooplankton species, Calanus finmarchicus , principally found in the North Atlantic but expatriated to the Arctic. Close to the ice-edge in the Fram Strait, we identified areas that, since the 1980s, are increasingly favourable to C. finmarchicus . Field-sampling revealed part of the population there to be capable of amassing enough reserves to overwinter. Early developmental stages were also present in early summer, suggesting successful local recruitment. This extension to suitable C. finmarchicus habitat is most likely facilitated by the long-term retreat of the ice-edge, allowing phytoplankton to bloom earlier and for longer and through higher temperatures increasing copepod developmental rates. The increased capacity for this species to complete its life-cycle and prosper in the Fram Strait can change community structure, with large consequences to regional food-webs.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Diet of nestling Barn Swallows in an agroecosystem: insights from fecal DNA barcoding and feather stable isotopes (δ13C, δ15N) - Jackson W. Kusack; Greg W. Mitchell; Dean R. Evans; Michael D. Cadman; Jenny L. McCune; Keith A. Hobson (Journal of Ornithology, 2022)

Standing variation rather than recent adaptive introgression probably underlies differentiation of the texanus subspecies of Helianthus annuus - Gregory L. Owens; Marco Todesco; Natalia Bercovich; Jean‐Sébastien Légaré; Nora Mitchell; Kenneth D. Whitney; Loren H. Rieseberg (Molecular Ecology, 2021)
The origins of geographic races in wide‐ranging species are poorly understood. In Texas, the texanus subspecies of Helianthus annuus has long been thought to have acquired its defining phenotypic traits via introgression from a local congener, H. debilis , but previous tests of this hypothesis were inconclusive. Here, we explore the origins of H. a. texanus using whole genome sequencing data from across the entire range of H. annuus and possible donor species, as well as phenotypic data from a common garden study. We found that although it is morphologically convergent with H. debilis , H. a. texanus has conflicting signals of introgression. Genome wide tests (Patterson's D and TreeMix ) only found evidence of introgression from H. argophyllus (sister species to H. annuus and also sympatric), but not H. debilis , with the exception of one individual of 109 analysed. We further scanned the genome for localized signals of introgression using PCAdmix and found minimal but nonzero introgression from H. debilis and significant introgression from H. argophyllus in some populations. Given the paucity of introgression from H. debilis , we argue that the morphological convergence observed in Texas is probably from standing genetic variation. We also found that genomic differentiation in H. a. texanus is mostly driven by large segregating inversions, several of which have signatures of natural selection based on haplotype frequencies.

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

Sediment Transport and Morphological Response to Nearshore Nourishment Projects on Wave-Dominated Coasts - Cody L. Johnson; Brian C. McFall; Douglas R. Krafft; Mitchell E. Brown (Journal of Marine Science and Engineering, 2021)
Nearshore nourishments are constructed for shoreline protection from waves, to provide sediment nourishment to the beach profile, and to beneficially use dredged sediment from navigation channel maintenance. However, it is poorly understood how placement morphology and depth influence nearshore processes operated on wave-dominated coasts. This study investigates the wave fields, sediment transport, and morphological response to three common nearshore nourishment shapes, nearshore berm (elongated bar), undulated nearshore berm, and small discrete mounds, with numerical experiments utilizing the Coastal Modeling System. The nourishments are placed in depths between 3 m and 7 m with a volume of approximately 100,000 m3 and between 400 m and 1000 m in alongshore length. Numerical experiments are carried out in three distinct coastal settings with representative wave climates and geomorphology. Simulation results indicate that shallower, more continuous berms attenuate the most wave energy, while deeper, more diffuse placements retain more sediment. Results from this study improve the understanding of nearshore nourishment shapes and can support decision makers identifying the most appropriate construction technique for future nearshore nourishment projects.

Field testing cellulose-water oxygen isotope relations in periphyton for paleohydrological reconstructions - Cory A. M. Savage; Casey R. Remmer; James V. Telford; Mitchell L. Kay; Eva Mehler; Brent B. Wolfe; Roland I. Hall (Journal of Paleolimnology, 2021)

Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Ragosti; Sunny Nguyen; et al. (GeroScience, 2021)

Components of metabolic syndrome associated with lower neurocognitive performance in youth with perinatally acquired HIV and youth who are HIV-exposed uninfected - Stephanie Shiau; Wendy Yu; Denise L. Jacobson; Sharon Nichols; Elizabeth J. McFarland; Janet S. Chen; Sahera Dirajlal-Fargo; Karen Surowiec; Mitchell E. Geffner; Jennifer Jao (Journal of NeuroVirology, 2021)

Bathymetric Data Requirements for Operational Coastal Erosion Forecasting Using XBeach - Nashwan Matheen; Mitchell D. Harley; Ian L. Turner; Kristen D. Splinter; Joshua A. Simmons; Mandi C. Thran (Journal of Marine Science and Engineering, 2021)
There is an increasing interest in the broad-scale implementation of coastal erosion early warning systems (EWS) with the goal of enhancing community preparedness to extreme coastal storm wave events. These emerging systems typically rely on process-based models to predict the storm-induced morphological change. A key challenge with incorporating these models in EWSs is the need for up-to-date nearshore and surf zone bathymetry data, which is difficult to measure routinely, but potentially important for accurate erosion forecasting. This study evaluates the degree to which up-to-date bathymetry is required for accurate coastal erosion predictions using the morphodynamic model XBeach and, subsequently, whether a range of “representative” and/or “synthetic” bathymetries can be used for the bottom boundary, when a survey of the immediate pre-storm bathymetry is not available. Twelve storm events at two contrasting sites were modelled using six different bathymetry scenarios, including the expected “best case” bathymetry surveyed immediately pre-storm. These results indicate that alternative bathymetries can be used to obtain sub-aerial erosion predictions that are similar (and in some cases better) than those resulting from the use of an immediately pre-storm surveyed bathymetry, provided that rigorous model calibration is undertaken prior. This generalized finding is attributed to specific parametrizations in the XBeach model structure that are optimized during the calibration process to match the particular bottom boundary condition used. This study provides practical guidance for the selection of suitable nearshore bathymetry for use in operational coastal erosion EWSs.

Pleistocene origins, western ghost lineages, and the emerging phylogeographic history of the red wolf and coyote - Benjamin N. Sacks; Kieren J. Mitchell; Cate B. Quinn; Lauren M. Hennelly; Mikkel‐Holger S. Sinding; Mark J. Statham; Sophie Preckler‐Quisquater; Steven R. Fain; Logan Kistler; Stevi L. Vanderzwan; Julie A. Meachen; Elaine A. Ostrander; et al. (Molecular Ecology, 2021)
The red wolf ( Canis rufus ) of the eastern US was driven to near‐extinction by colonial‐era persecution and habitat conversion, which facilitated coyote ( C . latrans ) range expansion and widespread hybridization with red wolves. The observation of some grey wolf ( C . lupus ) ancestry within red wolves sparked controversy over whether it was historically a subspecies of grey wolf with its predominant “coyote‐like” ancestry obtained from post‐colonial coyote hybridization (2‐species hypothesis) versus a distinct species closely related to the coyote that hybridized with grey wolf (3‐species hypothesis). We analysed mitogenomes sourced from before the 20th century bottleneck and coyote invasion, along with hundreds of modern amplicons, which led us to reject the 2‐species model and to investigate a broader phylogeographic 3‐species model suggested by the fossil record. Our findings broadly support this model, in which red wolves ranged the width of the American continent prior to arrival of the grey wolf to the mid‐continent 60–80 ka; red wolves subsequently disappeared from the mid‐continent, relegated to California and the eastern forests, which ushered in emergence of the coyote in their place (50–30 ka); by the early Holocene (12–10 ka), coyotes had expanded into California, where they admixed with and phenotypically replaced western red wolves in a process analogous to the 20th century coyote invasion of the eastern forests. Findings indicate that the red wolf pre‐dated not only European colonization but human, and possibly coyote, presence in North America. These findings highlight the urgency of expanding conservation efforts for the red wolf.

Disturbance type and species life history predict mammal responses to humans - Justin P. Suraci; Kaitlyn M. Gaynor; Maximilian L. Allen; Peter Alexander; Justin S. Brashares; Sara Cendejas‐Zarelli; Kevin Crooks; L. Mark Elbroch; Tavis Forrester; Austin M. Green; Jeffrey Haight; Nyeema C. Harris; et al. (Global Change Biology, 2021)
Human activity and land use change impact every landscape on Earth, driving declines in many animal species while benefiting others. Species ecological and life history traits may predict success in human‐dominated landscapes such that only species with “winning” combinations of traits will persist in disturbed environments. However, this link between species traits and successful coexistence with humans remains obscured by the complexity of anthropogenic disturbances and variability among study systems. We compiled detection data for 24 mammal species from 61 populations across North America to quantify the effects of (1) the direct presence of people and (2) the human footprint (landscape modification) on mammal occurrence and activity levels. Thirty‐three percent of mammal species exhibited a net negative response (i.e., reduced occurrence or activity) to increasing human presence and/or footprint across populations, whereas 58% of species were positively associated with increasing disturbance. However, apparent benefits of human presence and footprint tended to decrease or disappear at higher disturbance levels, indicative of thresholds in mammal species’ capacity to tolerate disturbance or exploit human‐dominated landscapes. Species ecological and life history traits were strong predictors of their responses to human footprint, with increasing footprint favoring smaller, less carnivorous, faster‐reproducing species. The positive and negative effects of human presence were distributed more randomly with respect to species trait values, with apparent winners and losers across a range of body sizes and dietary guilds. Differential responses by some species to human presence and human footprint highlight the importance of considering these two forms of human disturbance separately when estimating anthropogenic impacts on wildlife. Our approach provides insights into the complex mechanisms through which human activities shape mammal communities globally, revealing the drivers of the loss of larger predators in human‐modified landscapes.

Machine learning-based estimation of cognitive performance using regional brain MRI markers: the Northern Manhattan Study - Michelle R. Caunca; Lily Wang; Ying Kuen Cheung; Noam Alperin; Sang H. Lee; Mitchell S. V. Elkind; Ralph L. Sacco; Clinton B. Wright; Tatjana Rundek (Brain Imaging and Behavior, 2021)

The Cerebellum and Implicit Sequencing: Evidence from Cerebellar Ataxia - Owen P. Morgan; Mitchell B. Slapik; Katherine G. Iannuzzelli; Stephen M. LaConte; Jonathan M. Lisinski; Peg C. Nopoulos; Ashley M. Cochran; Sharif I. Kronemer; Liana S. Rosenthal; Cherie L. Marvel (The Cerebellum, 2021)

Neuropsychiatric Symptoms as a Reliable Phenomenology of Cerebellar Ataxia - Sharif I. Kronemer; Mitchell B. Slapik; Jessica R. Pietrowski; Michael J. Margron; Owen P. Morgan; Catherine C. Bakker; Liana S. Rosenthal; Chiadi U. Onyike; Cherie L. Marvel (The Cerebellum, 2021)

Uniparental isodisomy of chromosome 2 causing MRPL44-related multisystem mitochondrial disease - Alejandro Horga; Andreea Manole; Alice L. Mitchell; Enrico Bugiardini; Iain P. Hargreaves; Walied Mowafi; Conceição Bettencourt; Emma L. Blakely; Langping He; James M. Polke; Catherine E. Woodward; Ilaria Dalla Rosa; et al. (Molecular Biology Reports, 2021)

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Functional and ecosystem service differences between tree species: implications for tree species replacement - R. J. Mitchell; R. L. Hewison; R. K. Haghi; A. H. J. Robertson; A. M. Main; I. J. Owen (Trees, 2021)

Building upon open-barrel corer and sectioning systems to foster the continuing legacy of John Glew - James V. Telford; Mitchell L. Kay; Harman Vander Heide; Johan A. Wiklund; Tanner J. Owca; Jelle A. Faber; Brent B. Wolfe; Roland I. Hall (Journal of Paleolimnology, 2021)

A Phase I Study to Evaluate Two Doses of Wharton’s Jelly-Derived Mesenchymal Stromal Cells for the Treatment of De Novo High-Risk or Steroid-Refractory Acute Graft Versus Host Disease - Rupal P. Soder; Buddhadeb Dawn; Mark L. Weiss; Neil Dunavin; Scott Weir; James Mitchell; Meizhang Li; Leyla Shune; Anurag K. Singh; Siddhartha Ganguly; Marc Morrison; Haitham Abdelhakim; et al. (Stem Cell Reviews and Reports, 2020)

Evaluation of implementation of risk management guidelines for carriers of pathogenic variants in mismatch repair genes: a nationwide audit of familial cancer clinics - B. Meiser; R. Kaur; J. Kirk; A. Morrow; M. Peate; W. K. T. Wong; E. McPike; E. Cops; C. Dowson; R. Austin; M. Fine; L. Thrupp; et al. (Familial Cancer, 2020)

Tree planting in organic soils does not result in net carbon sequestration on decadal timescales - Nina L. Friggens; Alison J. Hester; Ruth J. Mitchell; Thomas C. Parker; Jens‐Arne Subke; Philip A. Wookey (Global Change Biology, 2020)
Tree planting is increasingly being proposed as a strategy to combat climate change through carbon (C) sequestration in tree biomass. However, total ecosystem C storage that includes soil organic C (SOC) must be considered to determine whether planting trees for climate change mitigation results in increased C storage. We show that planting two native tree species ( Betula pubescens and Pinus sylvestris ), of widespread Eurasian distribution, onto heather ( Calluna vulgaris ) moorland with podzolic and peaty podzolic soils in Scotland, did not lead to an increase in net ecosystem C stock 12 or 39 years after planting. Plots with trees had greater soil respiration and lower SOC in organic soil horizons than heather control plots. The decline in SOC cancelled out the increment in C stocks in tree biomass on decadal timescales. At all four experimental sites sampled, there was no net gain in ecosystem C stocks 12–39 years after afforestation—indeed we found a net ecosystem C loss in one of four sites with deciduous B. pubescens stands; no net gain in ecosystem C at three sites planted with B. pubescens ; and no net gain at additional stands of P. sylvestris . We hypothesize that altered mycorrhizal communities and autotrophic C inputs have led to positive ‘priming’ of soil organic matter, resulting in SOC loss, constraining the benefits of tree planting for ecosystem C sequestration. The results are of direct relevance to current policies, which promote tree planting on the assumption that this will increase net ecosystem C storage and contribute to climate change mitigation. Ecosystem‐level biogeochemistry and C fluxes must be better quantified and understood before we can be assured that large‐scale tree planting in regions with considerable pre‐existing SOC stocks will have the intended policy and climate change mitigation outcomes.

MitoQ and CoQ10 supplementation mildly suppresses skeletal muscle mitochondrial hydrogen peroxide levels without impacting mitochondrial function in middle-aged men - Toan Pham; Caitlin L. MacRae; Sophie C. Broome; Randall F. D’souza; Ravi Narang; Hsiang W. Wang; Trevor A. Mori; Anthony J. R. Hickey; Cameron J. Mitchell; Troy L. Merry (European Journal of Applied Physiology, 2020)

Test–Retest Reliability of Functional Magnetic Resonance Imaging Activation for a Vergence Eye Movement Task - Cristian Morales; Suril Gohel; Xiaobo Li; Mitchell Scheiman; Bharat B. Biswal; Elio M. Santos; Chang Yaramothu; Tara L. Alvarez (Neuroscience Bulletin, 2020)

Tentacle Transcriptomes of the Speckled Anemone (Actiniaria: Actiniidae: Oulactis sp.): Venom-Related Components and Their Domain Structure - Michela L. Mitchell; Gerry Q. Tonkin-Hill; Rodrigo A. V. Morales; Anthony W. Purcell; Anthony T. Papenfuss; Raymond S. Norton (Marine Biotechnology, 2020)

Correction to: Bilingualism Is Associated with a Delayed Onset of Dementia but Not with a Lower Risk of Developing it: a Systematic Review with Meta-Analyses - Stefano Brini; Hamid R. Sohrabi; Jeffrey J. Hebert; Mitchell R. L. Forrest; Matti Laine; Heikki Hämäläinen; Mira Karrasch; Jeremiah J. Peiffer; Ralph N. Martins; Timothy J. Fairchild (Neuropsychology Review, 2020)
The original version of this article unfortunately contained the following mistakes.

Bilingualism Is Associated with a Delayed Onset of Dementia but Not with a Lower Risk of Developing it: a Systematic Review with Meta-Analyses - Stefano Brini; Hamid R. Sohrabi; Jeffrey J. Hebert; Mitchell R. L. Forrest; Matti Laine; Heikki Hämäläinen; Mira Karrasch; Jeremiah J. Peiffer; Ralph N. Martins; Timothy J. Fairchild (Neuropsychology Review, 2020)
Some studies have linked bilingualism with a later onset of dementia, Alzheimer’s disease (AD), and mild cognitive impairment (MCI). Not all studies have observed such relationships, however. Differences in study outcomes may be due to methodological limitations and the presence of confounding factors within studies such as immigration status and level of education. We conducted the first systematic review with meta-analysis combining cross-sectional studies to explore if bilingualism might delay symptom onset and diagnosis of dementia, AD, and MCI. Primary outcomes included the age of symptom onset, the age at diagnosis of MCI or dementia, and the risk of developing MCI or dementia. A secondary outcome included the degree of disease severity at dementia diagnosis. There was no difference in the age of MCI diagnosis between monolinguals and bilinguals [mean difference: 3.2; 95% confidence intervals (CI): −3.4, 9.7]. Bilinguals vs. monolinguals reported experiencing AD symptoms 4.7 years (95% CI: 3.3, 6.1) later. Bilinguals vs. monolinguals were diagnosed with dementia 3.3 years (95% CI: 1.7, 4.9) later. Here, 95% prediction intervals showed a large dispersion of effect sizes (−1.9 to 8.5). We investigated this dispersion with a subgroup meta-analysis comparing studies that had recruited participants with dementia to studies that had recruited participants with AD on the age of dementia and AD diagnosis between mono- and bilinguals. Results showed that bilinguals vs. monolinguals were 1.9 years (95% CI: −0.9, 4.7) and 4.2 (95% CI: 2.0, 6.4) older than monolinguals at the time of dementia and AD diagnosis, respectively. The mean difference between the two subgroups was not significant. There was no significant risk reduction (odds ratio: 0.89; 95% CI: 0.68–1.16) in developing dementia among bilinguals vs. monolinguals. Also, there was no significant difference (Hedges’ g = 0.05; 95% CI: −0.13, 0.24) in disease severity at dementia diagnosis between bilinguals and monolinguals, despite bilinguals being significantly older. The majority of studies had adjusted for level of education suggesting that education might not have played a role in the observed delay in dementia among bilinguals vs. monolinguals. Although findings indicated that bilingualism was on average related to a delayed onset of dementia, the magnitude of this relationship varied across different settings. This variation may be due to unexplained heterogeneity and different sources of bias in the included studies. Registration: PROSPERO CRD42015019100.

Nitrogen Demand Associated with Increased Biomass Yield of Switchgrass and Big Bluestem: Implications for Future Breeding Strategies - Michael D. Casler; DoKyoung Lee; Robert B. Mitchell; Paul R. Adler; R. Mark Sulc; Keith D. Johnson; Robert L. Kallenbach; Arvid R. Boe; Russell D. Mathison; Kim A. Cassida; Doohong Min; Kenneth J. Moore (BioEnergy Research, 2020)

Not a melting pot: Plant species aggregate in their non‐native range - Gisela C. Stotz; James F. Cahill; Jonathan A. Bennett; Cameron N. Carlyle; Edward W. Bork; Diana Askarizadeh; Sandor Bartha; Carl Beierkuhnlein; Bazartseren Boldgiv; Leslie Brown; Marcelo Cabido; Giandiego Campetella; et al. (Global Ecology and Biogeography, 2020)
Aim Plant species continue to be moved outside of their native range by human activities. Here, we aim to determine whether, once introduced, plants assimilate into native communities or whether they aggregate, thus forming mosaics of native‐ and alien‐rich communities. Alien species might aggregate in their non‐native range owing to shared habitat preferences, such as their tendency to establish in high‐biomass, species‐poor areas. Location Twenty‐two herbaceous grasslands in 14 countries, mainly in the temperate zone. Time period 2012–2016. Major taxa studied Plants. Methods We used a globally coordinated survey. Within this survey, we found 46 plant species, predominantly from Eurasia, for which we had co‐occurrence data in their native and non‐native ranges. We tested for differences in co‐occurrence patterns of 46 species between their native (home) and non‐native (away) range. We also tested whether species had similar habitat preferences, by testing for differences in total biomass and species richness of the patches that species occupy in their native and non‐native ranges. Results We found the same species to show different patterns of association depending on whether they were in their native or non‐native range. Alien species were negatively associated with native species; instead, they aggregated with other alien species in species‐poor, high‐biomass communities in their non‐native range compared with their native range. Main conclusions The strong differences between the native (home) and non‐native (away) range in species co‐occurrence patterns are evidence that the way in which species associate with resident communities in their non‐native range is not species dependent, but is instead a property of being away from their native range. These results thus highlight that species might undergo important ecological changes when introduced away from their native range. Overall, we show origin‐dependent associations that result in novel communities, in which alien‐rich patches exist within a mosaic of native‐dominated communities.

Use of pre-industrial baselines to monitor anthropogenic enrichment of metals concentrations in recently deposited sediment of floodplain lakes in the Peace-Athabasca Delta (Alberta, Canada) - Tanner J. Owca; Mitchell L. Kay; Jelle Faber; Casey R. Remmer; Nelson Zabel; Johan A. Wiklund; Brent B. Wolfe; Roland I. Hall (Environmental Monitoring and Assessment, 2020)
Well-designed monitoring approaches are needed to assess effects of industrial development on downstream aquatic environments and guide environmental stewardship. Here, we develop and apply a monitoring approach to detect potential enrichment of metals concentrations in surficial lake sediments of the Peace-Athabasca Delta (PAD), northern Alberta, Canada. Since the ecological integrity of the PAD is strongly tied to river floodwaters that replenish lakes in the delta, and the PAD is located downstream of the Alberta oil sands, concerns have been raised over the potential transport of industry-supplied metals to the PAD via the Athabasca River. Surface sediment samples were collected in September 2017 from 61 lakes across the delta, and again in July 2018 from 20 of the same lakes that had received river floodwaters 2 months earlier, to provide snapshots of metals concentrations (Be, Cd, Cr, Cu, Ni, Pb, V, and Zn) that have recently accumulated in these lakes. To assess for anthropogenic enrichment, surficial sediment metals concentrations were normalized to aluminum and compared to pre-industrial baseline (i.e., reference) metal-aluminum linear relations for the Athabasca and Peace sectors of the PAD developed from pre-1920 measurements in lake sediment cores. Numerical analysis demonstrates no marked enrichment of these metals concentrations above pre-1920 baselines despite strong ability (> 99% power) to detect enrichment of 10%. Measurements of river sediment collected by the Regional Aquatics- and Oil Sands-Monitoring Programs (RAMP/OSM) also did not exceed pre-1920 concentrations. Thus, results presented here show no evidence of substantial oil sands-derived metals enrichment of sediment supplied by the Athabasca River to lakes in the PAD and demonstrate the usefulness of these methods as a monitoring framework.

Correction to: Neural correlates of reward magnitude and delay during a probabilistic delay discounting task in alcohol use disorder - Laura E. Dennis; Milky Kohno; Holly D. McCready; Daniel L. Schwartz; Britta Schwartz; David Lahna; Bonnie J. Nagel; Suzanne H. Mitchell; William F. Hoffman (Psychopharmacology, 2020)

Neural correlates of reward magnitude and delay during a probabilistic delay discounting task in alcohol use disorder - Laura E. Dennis; Milky Kohno; Holly D. McCready; Daniel L. Schwartz; Britta Schwartz; David Lahna; Bonnie J. Nagel; Suzanne H. Mitchell; William F. Hoffman (Psychopharmacology, 2020)

Non-physiologic Bioreactor Processing Conditions for Heart Valve Tissue Engineering - Mitchell C. VeDepo; Eric E. Buse; Arghya Paul; Gabriel L. Converse; Richard A. Hopkins (Cardiovascular Engineering and Technology, 2019)

Contrasting scales of local persistence between monsoonal and arid biomes in closely related, low‐dispersal vertebrates - Sally Potter; Ana C. Afonso Silva; Jason G. Bragg; Sarah R. Catalano; Stephen Donnellan; Paul Doughty; Mitchell L. Scott; Craig Moritz (Journal of Biogeography, 2019)
Aim Focussing on pairs of sister species across three genera of scincid lizards, we use genomic evidence to test for larger‐scale, late‐Pleistocene changes in distributions of lizards in the Australian arid zone (AZ) than in the adjacent monsoonal tropics (MT). Location Northern and central Australia. Taxon Scincidae: Squamata. Methods We sequenced ~2000 nuclear exons and one mitochondrial gene across the distributions of species with primarily MT or AZ distributions from three genera of lizards. Using phylogenetic analysis and population structure analyses we identified major phylogeographic lineages and then compared the spatial scale of structuring and tested for recent demographic expansions. Results Two genera in particular, Proablepharus and Morethia , showed deeper and more geographically localized phylogeographic diversity in the MT than the AZ. In the MT, localized diversity was prevalent in the relatively mesic regions. By contrast, the AZ was characterized by widespread and often genetically uniform lineages and a higher proportion of these had signals of recent population expansion. Main conclusions Consistent with other recent, but mostly less genetically extensive studies, our results point to deeper and more localized diversity in MT compared to AZ. In turn, this suggests higher local persistence in more mesic and topographically diverse biome through the late Quaternary climate fluctuations. For the AZ, geographically extensive range expansions have likely contributed to the low spatial turnover of this exceptionally rich lizard fauna.

Colloid Transport in Porous Media: A Review of Classical Mechanisms and Emerging Topics - Ian L. Molnar; Erica Pensini; Md Abdullah Asad; Chven A. Mitchell; Ludwig C. Nitsche; Laura J. Pyrak-Nolte; Gastón L. Miño; Magdalena M. Krol (Transport in Porous Media, 2019)

Different as night and day: Behavioural and life history responses to varied photoperiods in Daphnia magna - Kurt A. Gust; Alan J. Kennedy; Jennifer G. Laird; Mitchell S. Wilbanks; Natalie D. Barker; Xin Guan; Nicolas L. Melby; Lyle D. Burgoon; Michael E. Kjelland; Todd M. Swannack (Molecular Ecology, 2019)
Nearly all animal species have utilized photoperiod to cue seasonal behaviours and life history traits. We investigated photoperiod responses in keystone species, Daphnia magna , to identify molecular processes underlying ecologically important behaviours and traits using functional transcriptomic analyses. Daphnia magna were photoperiod‐entrained immediately posthatch to a standard control photoperiod of 16 light/ 8 dark hours (16L:8D) relative to shorter (4L:20D, 8L:16D, 12L:12L) and longer (20L:4D) day length photoperiods. Short‐day photoperiods induced significantly increased light‐avoidance behaviours relative to controls. Correspondingly, significant differential transcript expression for genes involved in glutamate signalling was observed, a critical signalling pathway in arthropod light‐avoidance behaviour. Additionally, period circadian protein and proteins coding F‐box/LRR‐repeat domains were differentially expressed which are recognized to establish circadian rhythms in arthropods. Indicators of metabolic rate increased in short‐day photoperiods which corresponded with broadscale changes in transcriptional expression across system‐level energy metabolism pathways. The most striking observations included significantly decreased neonate production at the shortest day length photoperiod (4L:20D) and significantly increased male production across short‐day and equinox photoperiods (4L:20D, 8L:16D and 12L:12D). Transcriptional expression consistent with putative mechanisms of male production was observed including photoperiod‐dependent expression of transformer‐2 sex‐determining protein and small nuclear ribonucleoprotein particles (snRNPs) which control splice variant expression for genes like transformer. Finally, increased transcriptional expression of glutamate has also been shown to induce male production in Daphnia pulex via photoperiod‐sensitive mechanisms. Overall, photoperiod entrainment affected molecular pathways that underpin critical behavioural and life history traits in D. magna providing fundamental insights into biological responses to this primary environmental cue.

Good neighbors aplenty: fungal endophytes rarely exhibit competitive exclusion patterns across a span of woody habitats - Marissa R. Lee; Jeff R. Powell; Brad Oberle; William K. Cornwell; Mitchell Lyons; Jessica L. Rigg; Amy E. Zanne (Ecology, 2019)
Environmental forces and biotic interactions, both positive and negative, structure ecological communities, but their relative roles remain obscure despite strong theory. For instance, ecologically similar species, based on the principle of limiting similarity, are expected to be most competitive and show negative interactions. Specious communities that assemble along broad environmental gradients afford the most power to test theory, but the communities often are difficult to quantify. Microbes, specifically fungal endophytes of wood, are especially suited for testing community assembly theory because they are relatively easy to sample across a comprehensive range of environmental space with clear axes of variation. Moreover, endophytes mediate key forest carbon cycle processes, and although saprophytic fungi from dead wood typically compete, endophytic fungi in living wood may enhance success through cooperative symbioses. To classify interactions within endophyte communities, we analyzed fungal DNA barcode variation across 22 woody plant species growing in woodlands near Richmond, New South Wales , Australia. We estimated the response of endophytes to the measured wood environment (i.e., 11 anatomical and chemical wood traits) and each other using latent‐variable models and identified recurrent communities across wood environments using model‐based classification. We used this information to evaluate whether (1) co‐occurrence patterns are consistent with strong competitive exclusion, and (2) a priori classifications by trophic mode and phylum distinguish taxa that are more likely to have positive vs. negative associations under the principle of limiting similarity. Fungal endophytes were diverse (mean = 140 taxa/sample), with differences in community composition structured by wood traits. Variation in wood water content and carbon concentration were associated with especially large community shifts. Surprisingly, after accounting for wood traits, fungal species were still more than three times more likely to have positive than negative co‐occurrence patterns. That is, patterns consistent with strong competitive exclusion were rare, and positive interactions among fungal endophytes were more common than expected. Confirming the frequency of positive vs. negative interactions among fungal taxa requires experimental tests, and our findings establish clear paths for further study. Evidence to date intriguingly suggests that, across a wide range of wood traits, cooperation may outweigh combat for these fungi.

Respiratory illness and respiratory syncytial virus hospitalization in infants with a tracheostomy following prophylaxis with palivizumab - Bosco Paes; Mahwesh Saleem; Doyoung Kim; Krista L. Lanctôt; Ian Mitchell (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Bedrock nitrogen weathering stimulates biological nitrogen fixation - Katherine A. Dynarski; Scott L. Morford; Scott A. Mitchell; Benjamin Z. Houlton (Ecology, 2019)
Global ecosystem models suggest that bedrock nitrogen (N) weathering contributes 10–20% of total N inputs to the natural terrestrial biosphere and >38% of ecosystem N supplies in temperate forests specifically. Yet, the role of rock N weathering in shaping ecological processes and biogeochemical fluxes is largely unknown. Here, we show that temperate forest ecosystems underlain by N‐rich bedrock exhibit higher free‐living N fixation rates than similar forests residing on N‐poor parent materials, across sites experiencing a range of climate and tectonic regimes. This seemingly counterintuitive result can be explained by increased accumulation of soil C and P in high bedrock N sites, resulting in increased energy inputs and nutrient supplies to N fixing microorganisms. Our findings advance a novel ecosystem biogeochemical framework that recognizes long‐term plant–soil–microbe feedbacks in shaping biogeochemical processes, with potentially widespread implications given the global distribution of bedrock N across Earth's terrestrial biomes.

Time to revisit? A predator’s previous successes and failures in prey capture determine its return time to patches - S. Vijayan; J. K. Lee; J. Balaban-Feld; W. A. Mitchell; B. P. Kotler; M. L. Rosenzweig; T. T. Lotan; Z. Abramsky (Oecologia, 2019)

Correction to: The effects of invasive grass on seedling recruitment of native Atriplex polycarpa (Torr.) S. Watson (Chenopodiaceae) shrubs in the San Joaquin Valley of California - Mitchell L. Coleman; R. Brandon Pratt (Biological Invasions, 2019)

The effects of invasive grass on seedling recruitment of native Atriplex polycarpa (Torr.) S. Watson (Chenopodiaceae) shrubs in the San Joaquin Valley of California - Mitchell L. Coleman; R. Brandon Pratt (Biological Invasions, 2019)

Deeply conserved susceptibility in a multi‐host, multi‐parasite system - Lisa N. Barrow; Sabrina M. McNew; Nora Mitchell; Spencer C. Galen; Holly L. Lutz; Heather Skeen; Thomas Valqui; Jason D. Weckstein; Christopher C. Witt (Ecology Letters, 2019)
Variation in susceptibility is ubiquitous in multi‐host, multi‐parasite assemblages, and can have profound implications for ecology and evolution in these systems. The extent to which susceptibility to parasites is phylogenetically conserved among hosts can be revealed by analysing diverse regional communities. We screened for haemosporidian parasites in 3983 birds representing 40 families and 523 species, spanning ~ 4500 m elevation in the tropical Andes. To quantify the influence of host phylogeny on infection status, we applied Bayesian phylogenetic multilevel models that included a suite of environmental, spatial, temporal, life history and ecological predictors. We found evidence of deeply conserved susceptibility across the avian tree; host phylogeny explained substantial variation in infection status, and results were robust to phylogenetic uncertainty. Our study suggests that susceptibility is governed, in part, by conserved, latent aspects of anti‐parasite defence. This demonstrates the importance of deep phylogeny for understanding present‐day ecological interactions.

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Less is more: lemurs (Eulemur spp.) may benefit from loss of trichromatic vision - Rachel L. Jacobs; Carrie C. Veilleux; Edward E. Louis; James P. Herrera; Chihiro Hiramatsu; David C. Frankel; Mitchell T. Irwin; Amanda D. Melin; Brenda J. Bradley (Behavioral Ecology and Sociobiology, 2019)

Measurement of Aerodynamic Particle Size Distribution of Orally Inhaled Products by Cascade Impactor: How to Let the Product Specification Drive the Quality Requirements of the Cascade Impactor - Daryl L. Roberts; Jolyon P. Mitchell (AAPS PharmSciTech, 2019)

Planning for adaptation to climate change: exploring the climate science-to-practice disconnect - Carrie L. Mitchell; Katherine E. Laycock (Climate and Development, 2019)

Social capital and incremental transformative change: responding to climate change experts in Metro Manila - Katherine E. Laycock; Carrie L. Mitchell (Climatic Change, 2019)

Shark depredation in commercial and recreational fisheries - J. D. Mitchell; D. L. McLean; S. P. Collin; T. J. Langlois (Reviews in Fish Biology and Fisheries, 2018)

Interactions Among Abiotic Drivers, Disturbance and Gross Ecosystem Carbon Exchange on Soil Respiration from Subtropical Pine Savannas - Susanne Wiesner; Christina L. Staudhammer; Henry W. Loescher; Andres Baron-Lopez; Lindsay R. Boring; Robert J. Mitchell; Gregory Starr (Ecosystems, 2018)

Correction to: Differences in cancer survival by sex: a population-based study using cancer registry data - Nina Afshar; Dallas R. English; Vicky Thursfield; Paul L. Mitchell; Luc Te Marvelde; Helen Farrugia; Graham G. Giles; Roger L. Milne (Cancer Causes & Control, 2018)

Differences in cancer survival by sex: a population-based study using cancer registry data - Nina Afshar; Dallas R. English; Vicky Thursfield; Paul L. Mitchell; Luc Te Marvelde; Helen Farrugia; Graham G. Giles; Roger L. Milne (Cancer Causes & Control, 2018)

Heparin impairs angiogenic signaling and compensatory lung growth after left pneumonectomy - Duy T. Dao; Lorenzo Anez-Bustillos; Jared Ourieff; Amy Pan; Paul D. Mitchell; Hiroko Kishikawa; Gillian L. Fell; Meredith A. Baker; Randolph S. Watnick; Hong Chen; Thomas E. Hamilton; Michael S. Rogers; et al. (Angiogenesis, 2018)

Temperature-related mortality impacts under and beyond Paris Agreement climate change scenarios - Ana Maria Vicedo-Cabrera; Yuming Guo; Francesco Sera; Veronika Huber; Carl-Friedrich Schleussner; Dann Mitchell; Shilu Tong; Micheline de Sousa Zanotti Staglior Coelho; Paulo Hilario Nascimento Saldiva; Eric Lavigne; Patricia Matus Correa; Nicolas Valdes Ortega; et al. (Climatic Change, 2018)

Engaging stakeholders in research to address water–energy–food (WEF) nexus challenges - C. Hoolohan; A. Larkin; C. McLachlan; R. Falconer; I. Soutar; J. Suckling; L. Varga; I. Haltas; A. Druckman; D. Lumbroso; M. Scott; D. Gilmour; et al. (Sustainability Science, 2018)

Inter-Annual Precipitation Variability Decreases Switchgrass Productivity from Arid to Mesic Environments - Lara G. Reichmann; Harold P. Collins; Virginia L. Jin; Mari-Vaughn V. Johnson; Jim R. Kiniry; Robert B. Mitchell; H. Wayne Polley; Philip A. Fay (BioEnergy Research, 2018)

Characterization of isolated liver sinusoidal endothelial cells for liver bioengineering - A. M. Dingle; K. K. Yap; Y-W. Gerrand; C. J. Taylor; E. Keramidaris; Z. Lokmic; A. M. Kong; H. L. Peters; W. A. Morrison; G. M. Mitchell (Angiogenesis, 2018)

Respiratory syncytial virus prophylaxis in cystic fibrosis: the Canadian registry of palivizumab data (2005–2016) - Ian Mitchell; S. K. Wong; B. Paes; M. Ruff; C. Bjornson; A. Li; K. L. Lanctôt (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Improved detection and mapping of deepwater hydrocarbon seeps: optimizing multibeam echosounder seafloor backscatter acquisition and processing techniques - Garrett A. Mitchell; Daniel L. Orange; Jamshid J. Gharib; Paul Kennedy (Marine Geophysical Research, 2018)

The putative leucine sensor Sestrin2 is hyperphosphorylated by acute resistance exercise but not protein ingestion in human skeletal muscle - Nina Zeng; Randall F. D’Souza; Brie Sorrenson; Troy L. Merry; Matthew P. G. Barnett; Cameron J. Mitchell; David Cameron-Smith (European Journal of Applied Physiology, 2018)

Palivizumab prophylaxis for respiratory syncytial virus in infants with cystic fibrosis: is there a need? - Candice Bjornson; Parco Chan; Abby Li; Bosco Paes; Krista L. Lanctôt; Ian Mitchell (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Colletotrichum species associated with pre-and post-harvest diseases of avocado and mango in eastern Australia - F. R. Giblin; Y. P. Tan; R. Mitchell; L. M. Coates; J. A. G. Irwin; R. G. Shivas (Australasian Plant Pathology, 2018)

Integration of sudden death syndrome resistance loci in the soybean genome - Hao-Xun Chang; Mitchell G. Roth; Dechun Wang; Silvia R. Cianzio; David A. Lightfoot; Glen L. Hartman; Martin I. Chilvers (Theoretical and Applied Genetics, 2018)

Ionophore and Biometal Modulation of P-glycoprotein Expression and Function in Human Brain Microvascular Endothelial Cells - Mitchell P. McInerney; Irene Volitakis; Ashley I. Bush; William A. Banks; Jennifer L. Short; Joseph A. Nicolazzo (Pharmaceutical Research, 2018)

Global environmental change effects on plant community composition trajectories depend upon management legacies - Michael P. Perring; Markus Bernhardt‐Römermann; Lander Baeten; Gabriele Midolo; Haben Blondeel; Leen Depauw; Dries Landuyt; Sybryn L. Maes; Emiel De Lombaerde; Maria Mercedes Carón; Mark Vellend; Jörg Brunet; et al. (Global Change Biology, 2018)
The contemporary state of functional traits and species richness in plant communities depends on legacy effects of past disturbances. Whether temporal responses of community properties to current environmental changes are altered by such legacies is, however, unknown. We expect global environmental changes to interact with land‐use legacies given different community trajectories initiated by prior management, and subsequent responses to altered resources and conditions. We tested this expectation for species richness and functional traits using 1814 survey‐resurvey plot pairs of understorey communities from 40 European temperate forest datasets, syntheses of management transitions since the year 1800, and a trait database. We also examined how plant community indicators of resources and conditions changed in response to management legacies and environmental change. Community trajectories were clearly influenced by interactions between management legacies from over 200 years ago and environmental change. Importantly, higher rates of nitrogen deposition led to increased species richness and plant height in forests managed less intensively in 1800 (i.e., high forests), and to decreases in forests with a more intensive historical management in 1800 (i.e., coppiced forests). There was evidence that these declines in community variables in formerly coppiced forests were ameliorated by increased rates of temperature change between surveys. Responses were generally apparent regardless of sites’ contemporary management classifications, although sometimes the management transition itself, rather than historic or contemporary management types, better explained understorey responses. Main effects of environmental change were rare, although higher rates of precipitation change increased plant height, accompanied by increases in fertility indicator values. Analysis of indicator values suggested the importance of directly characterising resources and conditions to better understand legacy and environmental change effects. Accounting for legacies of past disturbance can reconcile contradictory literature results and appears crucial to anticipating future responses to global environmental change.

Spatiotemporal Models of an Estuarine Fish Species to Identify Patterns and Factors Impacting Their Distribution and Abundance - Leo Polansky; Ken B. Newman; Matthew L. Nobriga; Lara Mitchell (Estuaries and Coasts, 2018)

Piscine myocarditis virus detected in corkwing wrasse ( Symphodus melops ) and ballan wrasse ( Labrus bergylta ) - F Scholz; N M Ruane; T Morrissey; M Marcos‐López; S Mitchell; I O'Connor; L Mirimin; E MacCarthy; H D Rodger (Journal of Fish Diseases, 2018)

Screening of new British thraustochytrids isolates for docosahexaenoic acid (DHA) production - Loris Fossier Marchan; Kim J. Lee Chang; Peter D. Nichols; Jane L. Polglase; Wilfrid J. Mitchell; Tony Gutierrez (Journal of Applied Phycology, 2017)

Accumulation of Methylmercury in Invertebrates and Masked Shrews (Sorex cinereus) at an Upland Forest–Peatland Interface in Northern Minnesota, USA - Ilana Tavshunsky; Susan L. Eggert; Carl P. J. Mitchell (Bulletin of Environmental Contamination and Toxicology, 2017)

Conceptualizing Social Outcomes of Large Marine Protected Areas - Rebecca L. Gruby; Luke Fairbanks; Leslie Acton; Evan Artis; Lisa M. Campbell; Noella J. Gray; Lillian Mitchell; Sarah Bess Jones Zigler; Katie Wilson (Coastal Management, 2017)

Performance of microbial identification by MALDI-TOF MS and susceptibility testing by VITEK 2 from positive blood cultures after minimal incubation on solid media - S. L. Mitchell; K. Alby (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Erratum to: Structural characterization of an all-aminosugar-containing capsular polysaccharide from Colwellia psychrerythraea 34H - Angela Casillo; Jonas Ståhle; Ermenegilda Parrilli; Filomena Sannino; Daniel E. Mitchell; Giuseppina Pieretti; Matthew I. Gibson; Gennaro Marino; Rosa Lanzetta; Michelangelo Parrilli; Göran Widmalm; Maria L. Tutino; et al. (Antonie van Leeuwenhoek, 2017)

Structural characterization of an all-aminosugar-containing capsular polysaccharide from Colwellia psychrerythraea 34H - Angela Casillo; Jonas Ståhle; Ermenegilda Parrilli; Filomena Sannino; Daniel E. Mitchell; Giuseppina Pieretti; Matthew I. Gibson; Gennaro Marino; Rosa Lanzetta; Michelangelo Parrilli; Göran Widmalm; Maria L. Tutino; et al. (Antonie van Leeuwenhoek, 2017)

H2O solubility in basalt at upper mantle conditions - Alexandra L. Mitchell; Glenn A. Gaetani; Julie A. O’Leary; Erik H. Hauri (Contributions to Mineralogy and Petrology, 2017)

Development of a novel method for the strengthening and toughening of irradiation-sterilized bone allografts - Tarik Attia; Mitchell Woodside; Gagan Minhas; Xing Ze Lu; David S. Josey; Timothy Burrow; Marc Grynpas; Thomas L. Willett (Cell and Tissue Banking, 2017)

Neurovascular Alterations in Alzheimer’s Disease: Transporter Expression Profiles and CNS Drug Access - Mitchell P. McInerney; Jennifer L. Short; Joseph A. Nicolazzo (The AAPS Journal, 2017)

Psychosocial morbidity in TP53 mutation carriers: is whole-body cancer screening beneficial? - Kate A. McBride; Mandy L. Ballinger; Timothy E. Schlub; Mary-Anne Young; Martin H. N. Tattersall; Judy Kirk; Ros Eeles; Emma Killick; Leslie G. Walker; Sue Shanley; David M. Thomas; Gillian Mitchell (Familial Cancer, 2017)

Erratum to: Inhibition of pannexin1 channels alleviates acetaminophen-induced hepatotoxicity - Michaël Maes; Mitchell R. McGill; Tereza Cristina da Silva; Chloé Abels; Margitta Lebofsky; James L. Weemhoff; Taynã Tiburcio; Isabel Veloso Alves Pereira; Joost Willebrords; Sara Crespo Yanguas; Anwar Farhood; Alain Beschin; et al. (Archives of Toxicology, 2017)

Inhibition of pannexin1 channels alleviates acetaminophen-induced hepatotoxicity - Michaël Maes; Mitchell R. McGill; Tereza Cristina da Silva; Chloé Abels; Margitta Lebofsky; James L. Weemhoff; Taynã Tiburcio; Isabel Veloso Alves Pereira; Joost Willebrords; Sara Crespo Yanguas; Anwar Farhood; Alain Beschin; et al. (Archives of Toxicology, 2017)

Revealing pMDI Spray Initial Conditions: Flashing, Atomisation and the Effect of Ethanol - Nicholas Mason-Smith; Daniel J. Duke; Alan L. Kastengren; Daniela Traini; Paul M. Young; Yang Chen; David A. Lewis; Daniel Edgington-Mitchell; Damon Honnery (Pharmaceutical Research, 2017)

Understanding climate change and resilience: assessing strengths and opportunities for adaptation in the Global South - Marta Berbés-Blázquez; Carrie L. Mitchell; Sarah L. Burch; Johanna Wandel (Climatic Change, 2017)

Estimating groundwater inflow and leakage outflow for an intermontane lake with a structurally complex geology: Georgetown Lake in Montana, USA - Glenn D. Shaw; Katie L. Mitchell; Christopher H. Gammons (Hydrogeology Journal, 2017)

The phospholipid composition of the human entorhinal cortex remains relatively stable over 80 years of adult aging - Sarah E. Hancock; Michael G. Friedrich; Todd W. Mitchell; Roger J. W. Truscott; Paul L. Else (GeroScience, 2017)

Modeled ecohydrological responses to climate change at seven small watersheds in the northeastern United States - Afshin Pourmokhtarian; Charles T. Driscoll; John L. Campbell; Katharine Hayhoe; Anne M. K. Stoner; Mary Beth Adams; Douglas Burns; Ivan Fernandez; Myron J. Mitchell; James B. Shanley (Global Change Biology, 2017)
A cross‐site analysis was conducted on seven diverse, forested watersheds in the northeastern United States to evaluate hydrological responses (evapotranspiration, soil moisture, seasonal and annual streamflow, and water stress) to projections of future climate. We used output from four atmosphere–ocean general circulation models ( AOGCM s; CCSM 4, Had GEM 2‐ CC , MIROC 5, and MRI ‐ CGCM 3) included in Phase 5 of the Coupled Model Intercomparison Project, coupled with two Representative Concentration Pathways ( RCP 8.5 and 4.5). The coarse resolution AOGCM s outputs were statistically downscaled using an asynchronous regional regression model to provide finer resolution future climate projections as inputs to the deterministic dynamic ecosystem model Pn ET ‐ BGC . Simulation results indicated that projected warmer temperatures and longer growing seasons in the northeastern United States are anticipated to increase evapotranspiration across all sites, although invoking CO 2 effects on vegetation (growth enhancement and increases in water use efficiency ( WUE )) diminish this response. The model showed enhanced evapotranspiration resulted in drier growing season conditions across all sites and all scenarios in the future. Spruce‐fir conifer forests have a lower optimum temperature for photosynthesis, making them more susceptible to temperature stress than more tolerant hardwood species, potentially giving hardwoods a competitive advantage in the future. However, some hardwood forests are projected to experience seasonal water stress, despite anticipated increases in precipitation, due to the higher temperatures, earlier loss of snow packs, longer growing seasons, and associated water deficits. Considering future CO 2 effects on WUE in the model alleviated water stress across all sites. Modeled streamflow responses were highly variable, with some sites showing significant increases in annual water yield, while others showed decreases. This variability in streamflow responses poses a challenge to water resource management in the northeastern United States. Our analyses suggest that dominant vegetation type and soil type are important attributes in determining future hydrological responses to climate change.

Exploring clinicians’ attitudes about using aspirin for risk reduction in people with Lynch Syndrome with no personal diagnosis of colorectal cancer - Yanni Chen; Michelle Peate; Rajneesh Kaur; Bettina Meiser; Tim Wong; Judy Kirk; Robyn L. Ward; Annabel Goodwin; Finlay Macrae; Janet Hiller; Alison H. Trainer; Gillian Mitchell (Familial Cancer, 2017)

Experiments on melt–rock reaction in the shallow mantle wedge - Alexandra L. Mitchell; Timothy L. Grove (Contributions to Mineralogy and Petrology, 2016)

The role of boundary organizations in climate change adaptation from the perspective of municipal practitioners - Alexandra Graham; Carrie L. Mitchell (Climatic Change, 2016)

Putting indigenous conservation policy into practice delivers biodiversity and cultural benefits - Emilie Ens; Mitchell. L. Scott; Yugul Mangi Rangers; Craig Moritz; Rebecca Pirzl (Biodiversity and Conservation, 2016)

Primate genotyping via high resolution melt analysis: rapid and reliable identification of color vision status in wild lemurs - Rachel L. Jacobs; Amanda N. Spriggs; Tammie S. MacFie; Andrea L. Baden; Mitchell T. Irwin; Patricia C. Wright; Edward E. Louis; Richard R. Lawler; Nicholas I. Mundy; Brenda J. Bradley (Primates, 2016)

Biological Effects of Naturally Occurring Sphingolipids, Uncommon Variants, and Their Analogs - Mitchell K. P. Lai; Wee Siong Chew; Federico Torta; Angad Rao; Greg L. Harris; Jerold Chun; Deron R. Herr (NeuroMolecular Medicine, 2016)

Productivity and species richness in longleaf pine woodlands: resource‐disturbance influences across an edaphic gradient - L. K. Kirkman; L. M. Giencke; R. S. Taylor; L. R. Boring; C. L. Staudhammer; R. J. Mitchell (Ecology, 2016)
This study examines the complex feedback mechanisms that regulate a positive relationship between species richness and productivity in a longleaf pine‐wiregrass woodland. Across a natural soil moisture gradient spanning wet‐mesic to xeric conditions, two large scale manipulations over a 10‐yr period were used to determine how limiting resources and fire regulate plant species diversity and productivity at multiple scales. A fully factorial experiment was used to examine productivity and species richness responses to N and water additions. A separate experiment examined standing crop and richness responses to N addition in the presence and absence of fire. Specifically, these manipulations addressed the following questions: (1) How do N and water addition influence annual aboveground net primary productivity of the midstory/overstory and ground cover? (2) How do species richness responses to resource manipulations vary with scale and among functional groups of ground cover species? (3) How does standing crop (including overstory, understory/midstory, and ground cover components) differ between frequently burned and fire excluded plots after a decade without fire? (4) What is the role of fire in regulating species richness responses to N addition? This long‐term study across a soil moisture gradient provides empirical evidence that species richness and productivity in longleaf pine woodlands are strongly regulated by soil moisture. After a decade of treatment, there was an overall species richness decline with N addition, an increase in richness of some functional groups with irrigation, and a substantial decline in species richness with fire exclusion. Changes in species richness in response to treatments were scale‐dependent, occurring primarily at small scales (≤10 m 2 ). Further, with fire exclusion, standing crop of ground cover decreased with N addition and non‐pine understory/midstory increased in wet‐mesic sites. Non‐pine understory/midstory standing crop increased in xeric sites with fire exclusion, but there was no influence of N addition. This study highlights the complexity of interactions among multiple limiting resources, frequent fire, and characteristics of dominant functional groups that link species richness and productivity.

FG-3019, a Human Monoclonal Antibody Recognizing Connective Tissue Growth Factor, is Subject to Target-Mediated Drug Disposition - Mitchell C. Brenner; Wojciech Krzyzanski; James Z. Chou; Pierre E. Signore; Cyra K. Fung; David Guzman; Dongxia Li; Weihua Zhang; David R. Olsen; Viet-Tam L. Nguyen; Carolyn W. Koo; Mark D. Sternlicht; et al. (Pharmaceutical Research, 2016)

Daphnia magna’s sense of competition: intra-specific interactions (ISI) alter life history strategies and increase metals toxicity - Kurt A. Gust; Alan J. Kennedy; Nicolas L. Melby; Mitchell S. Wilbanks; Jennifer Laird; Barbara Meeks; Erik B. Muller; Roger M. Nisbet; Edward J. Perkins (Ecotoxicology, 2016)

Assessing the health effects of climate change in Alaska with community-based surveillance - David L. Driscoll; Erica Mitchell; Rebecca Barker; Janet M. Johnston; Sue Renes (Climatic Change, 2016)

Ant biodiversity and its environmental predictors in the North Kimberley region of Australia’s seasonal tropics - Adam T. Cross; Cecilia Myers; Celia N. A. Mitchell; Sophie L. Cross; Christopher Jackson; Rowan Waina; Ladislav Mucina; Kingsley W. Dixon; Alan N. Andersen (Biodiversity and Conservation, 2016)

Dedicated Herbaceous Biomass Feedstock Genetics and Development - W. F. Anderson; G. Sarath; S. Edme; M. D. Casler; R. B. Mitchell; C. M. Tobias; A. L. Hale; S. E. Sattler; J. E. Knoll (BioEnergy Research, 2016)

Insights into Spray Development from Metered-Dose Inhalers Through Quantitative X-ray Radiography - Nicholas Mason-Smith; Daniel J. Duke; Alan L. Kastengren; Peter J. Stewart; Daniela Traini; Paul M. Young; Yang Chen; David A. Lewis; Julio Soria; Daniel Edgington-Mitchell; Damon Honnery (Pharmaceutical Research, 2016)

Temporally and Spatially Resolved x-ray Fluorescence Measurements of in-situ Drug Concentration in Metered-Dose Inhaler Sprays - Daniel J. Duke; Alan L. Kastengren; Nicholas Mason-Smith; Yang Chen; Paul M. Young; Daniela Traini; David Lewis; Daniel Edgington-Mitchell; Damon Honnery (Pharmaceutical Research, 2016)

Ikaros, Helios, and Aiolos protein levels increase in human thymocytes after β selection - Julie L. Mitchell; Amara Seng; Thomas M. Yankee (Immunologic Research, 2016)

Sharing the load: a survey of parasitism in the invasive freshwater pulmonate, Physa acuta (Hygrophila: Physidae) and sympatric native snail populations - D. Rex Mitchell; Tommy L. F. Leung (Hydrobiologia, 2016)

Network analysis of human fMRI data suggests modular restructuring after simulated acquired brain injury - E. Ruiz Vargas; D. G. V. Mitchell; S. G. Greening; L. M. Wahl (Medical & Biological Engineering & Computing, 2016)

Timing and context: important considerations in the return of genetic results to research participants - Kate A. McBride; Nina Hallowell; Martin H. N. Tattersall; Judy Kirk; Mandy L. Ballinger; David M. Thomas; Gillian Mitchell; Mary-Anne Young (Journal of Community Genetics, 2016)

Mechanistic Biomarkers in Liver Diseases - Mitchell R. McGill; Benjamin L. Woolbright; James L. Weemhoff; Hartmut Jaeschke (Exposure and Health, 2016)

Rapid purging of genetic load in a metapopulation and consequences for range expansion in an invasive plant - Gina L. Marchini; Nena Cole Sherlock; Alisa P. Ramakrishnan; David M. Rosenthal; Mitchell B. Cruzan (Biological Invasions, 2016)

Erratum to: Melting the hydrous, subarc mantle: the origin of primitive andesites - Alexandra L. Mitchell; Timothy L. Grove (Contributions to Mineralogy and Petrology, 2015)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Erratum to: Lg Coda Q Variations across South America and their Relation to Crustal Evolution - J. L. de Souza; B. J. Mitchell (Pure and Applied Geophysics, 2015)

Territoriality in a snake - Jonathan K. Webb; Mitchell L. Scott; Martin J. Whiting; Richard Shine (Behavioral Ecology and Sociobiology, 2015)

Chemoreception and mating behaviour of a tropical Australian skink - Mitchell L. Scott; John Llewelyn; Megan Higgie; Conrad J. Hoskin; Kyana Pike; Ben L. Phillips (acta ethologica, 2015)

Drivers of temporal changes in temperate forest plant diversity vary across spatial scales - Markus Bernhardt‐Römermann; Lander Baeten; Dylan Craven; Pieter De Frenne; Radim Hédl; Jonathan Lenoir; Didier Bert; Jörg Brunet; Markéta Chudomelová; Guillaume Decocq; Hartmut Dierschke; Thomas Dirnböck; et al. (Global Change Biology, 2015)
Global biodiversity is affected by numerous environmental drivers. Yet, the extent to which global environmental changes contribute to changes in local diversity is poorly understood. We investigated biodiversity changes in a meta‐analysis of 39 resurvey studies in European temperate forests (3988 vegetation records in total, 17–75 years between the two surveys) by assessing the importance of (i) coarse‐resolution (i.e., among sites) vs. fine‐resolution (i.e., within sites) environmental differences and (ii) changing environmental conditions between surveys. Our results clarify the mechanisms underlying the direction and magnitude of local‐scale biodiversity changes. While not detecting any net local diversity loss, we observed considerable among‐site variation, partly explained by temporal changes in light availability (a local driver) and density of large herbivores (a regional driver). Furthermore, strong evidence was found that presurvey levels of nitrogen deposition determined subsequent diversity changes. We conclude that models forecasting future biodiversity changes should consider coarse‐resolution environmental changes, account for differences in baseline environmental conditions and for local changes in fine‐resolution environmental conditions.

Whole-exome sequencing identifies novel ECHS1 mutations in Leigh syndrome - Martine Tetreault; Somayyeh Fahiminiya; Hana Antonicka; Grant A. Mitchell; Michael T. Geraghty; Matthew Lines; Kym M. Boycott; Eric A. Shoubridge; John J. Mitchell; Jacques L. Michaud; Jacek Majewski (Human Genetics, 2015)

Measurement of Forest Above-Ground Biomass Using Active and Passive Remote Sensing at Large (Subnational to Global) Scales - Richard M. Lucas; Anthea L. Mitchell; John Armston (Current Forestry Reports, 2015)

Melting the hydrous, subarc mantle: the origin of primitive andesites - Alexandra L. Mitchell; Timothy L. Grove (Contributions to Mineralogy and Petrology, 2015)

Growth Recovery of Lemna gibba and Lemna minor Following a 7-Day Exposure to the Herbicide Diuron - Mitchell Burns; Mark L. Hanson; Ryan S. Prosser; Angus N. Crossan; Ivan R. Kennedy (Bulletin of Environmental Contamination and Toxicology, 2015)

A blood spot method for detecting fumonisin-induced changes in putative sphingolipid biomarkers in LM/Bc mice and humans - Ronald T. Riley; Jency L. Showker; Christine M. Lee; Cody E. Zipperer; Trevor R. Mitchell; Kenneth A. Voss; Nicholas C. Zitomer; Olga Torres; Jorge Matute; Simon G. Gregory; Allison E. Ashley-Koch; Joyce R. Maddox; et al. (Food Additives & Contaminants: Part A, 2015)

Health professionals’ evaluation of delivering treatment-focused genetic testing to women newly diagnosed with breast cancer - Kirsten F. L. Douma; Bettina Meiser; Judy Kirk; Gillian Mitchell; Christobel Saunders; Belinda Rahman; Mariana S. Sousa; Kristine Barlow-Stewart; Margaret Gleeson; Kathy Tucker (Familial Cancer, 2015)

Molecular structure of glycogen in diabetic liver - Bin Deng; Mitchell A. Sullivan; Jialun Li; Xinle Tan; Chengjun Zhu; Benjamin L. Schulz; Robert G. Gilbert (Glycoconjugate Journal, 2015)

Examining the genetic integrity of a rare endemic Colorado cactus (Sclerocactus glaucus) in the face of hybridization threats from a close and widespread congener (Sclerocactus parviflorus) - Anna L. Schwabe; Jennifer Ramp Neale; Mitchell E. McGlaughlin (Conservation Genetics, 2015)

PHA-Stimulated Immune-Responsiveness in Mercury-Dosed Zebra Finches Does Not Match Results from Environmentally Exposed Songbirds - Mitchell T. Caudill; Eliza L. Spear; Claire W. Varian-Ramos; Daniel A. Cristol (Bulletin of Environmental Contamination and Toxicology, 2015)

Towards an operational SAR monitoring system for monitoring environmental flows in the Macquarie Marshes - A. L. Mitchell; A. K. Milne; I. Tapley (Wetlands Ecology and Management, 2015)

Antibiotic Degradation During Thermophilic Composting - S. M. Mitchell; J. L. Ullman; A. Bary; C. G. Cogger; A. L. Teel; R. J. Watts (Water, Air, & Soil Pollution, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Pollen‐based quantitative reconstructions of Holocene regional vegetation cover (plant‐functional types and land‐cover types) in Europe suitable for climate modelling - A.‐K. Trondman; M.‐J. Gaillard; F. Mazier; S. Sugita; R. Fyfe; A. B. Nielsen; C. Twiddle; P. Barratt; H. J. B. Birks; A. E. Bjune; L. Björkman; A. Broström; et al. (Global Change Biology, 2015)
We present quantitative reconstructions of regional vegetation cover in north‐western Europe, western Europe north of the Alps, and eastern Europe for five time windows in the Holocene [around 6k, 3k, 0.5k, 0.2k, and 0.05k calendar years before present ( bp )] at a 1° × 1° spatial scale with the objective of producing vegetation descriptions suitable for climate modelling. The REVEALS model was applied on 636 pollen records from lakes and bogs to reconstruct the past cover of 25 plant taxa grouped into 10 plant‐functional types and three land‐cover types [evergreen trees, summer‐green (deciduous) trees, and open land]. The model corrects for some of the biases in pollen percentages by using pollen productivity estimates and fall speeds of pollen, and by applying simple but robust models of pollen dispersal and deposition. The emerging patterns of tree migration and deforestation between 6k bp and modern time in the REVEALS estimates agree with our general understanding of the vegetation history of Europe based on pollen percentages. However, the degree of anthropogenic deforestation (i.e. cover of cultivated and grazing land) at 3k, 0.5k, and 0.2k bp is significantly higher than deduced from pollen percentages. This is also the case at 6k in some parts of Europe, in particular Britain and Ireland. Furthermore, the relationship between summer‐green and evergreen trees, and between individual tree taxa, differs significantly when expressed as pollen percentages or as REVEALS estimates of tree cover. For instance, when Pinus is dominant over Picea as pollen percentages, Picea is dominant over Pinus as REVEALS estimates. These differences play a major role in the reconstruction of European landscapes and for the study of land cover–climate interactions, biodiversity and human resources.

Corrigendum to Wagner et al .: Natural soil microbes alter flowering phenology and the intensity of selection on flowering time in a wild Arabidopsis relative - Maggie R. Wagner; Derek S. Lundberg; Devin Coleman‐Derr; Susannah Green Tringe; Jeffery L. Dangl; Thomas Mitchell‐Olds (Ecology Letters, 2015)

Time series analysis of forest carbon dynamics: recovery of Pinus palustris physiology following a prescribed fire - G. Starr; C. L. Staudhammer; H. W. Loescher; R. Mitchell; A. Whelan; J. K. Hiers; J. J. O’Brien (New Forests, 2015)

Conclusions of the Worldwide Integrated Assessment on the risks of neonicotinoids and fipronil to biodiversity and ecosystem functioning - J. P. van der Sluijs; V. Amaral-Rogers; L. P. Belzunces; M. F. I. J. Bijleveld van Lexmond; J-M. Bonmatin; M. Chagnon; C. A. Downs; L. Furlan; D. W. Gibbons; C. Giorio; V. Girolami; D. Goulson; et al. (Environmental Science and Pollution Research, 2015)

Systemic insecticides (neonicotinoids and fipronil): trends, uses, mode of action and metabolites - N. Simon-Delso; V. Amaral-Rogers; L. P. Belzunces; J. M. Bonmatin; M. Chagnon; C. Downs; L. Furlan; D. W. Gibbons; C. Giorio; V. Girolami; D. Goulson; D. P. Kreutzweiser; et al. (Environmental Science and Pollution Research, 2015)

Plant diversity predicts beta but not alpha diversity of soil microbes across grasslands worldwide - Suzanne M. Prober; Jonathan W. Leff; Scott T. Bates; Elizabeth T. Borer; Jennifer Firn; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Elsa E. Cleland; Nicole M. DeCrappeo; et al. (Ecology Letters, 2015)
Aboveground–belowground interactions exert critical controls on the composition and function of terrestrial ecosystems, yet the fundamental relationships between plant diversity and soil microbial diversity remain elusive. Theory predicts predominantly positive associations but tests within single sites have shown variable relationships, and associations between plant and microbial diversity across broad spatial scales remain largely unexplored. We compared the diversity of plant, bacterial, archaeal and fungal communities in one hundred and forty‐five 1 m 2 plots across 25 temperate grassland sites from four continents. Across sites, the plant alpha diversity patterns were poorly related to those observed for any soil microbial group. However, plant beta diversity (compositional dissimilarity between sites) was significantly correlated with the beta diversity of bacterial and fungal communities, even after controlling for environmental factors. Thus, across a global range of temperate grasslands, plant diversity can predict patterns in the composition of soil microbial communities, but not patterns in alpha diversity.

Winter climate change affects growing‐season soil microbial biomass and activity in northern hardwood forests - Jorge Durán; Jennifer L. Morse; Peter M. Groffman; John L. Campbell; Lynn M. Christenson; Charles T. Driscoll; Timothy J. Fahey; Melany C. Fisk; Myron J. Mitchell; Pamela H. Templer (Global Change Biology, 2014)
Understanding the responses of terrestrial ecosystems to global change remains a major challenge of ecological research. We exploited a natural elevation gradient in a northern hardwood forest to determine how reductions in snow accumulation, expected with climate change, directly affect dynamics of soil winter frost, and indirectly soil microbial biomass and activity during the growing season. Soils from lower elevation plots, which accumulated less snow and experienced more soil temperature variability during the winter (and likely more freeze/thaw events), had less extractable inorganic nitrogen (N), lower rates of microbial N production via potential net N mineralization and nitrification, and higher potential microbial respiration during the growing season. Potential nitrate production rates during the growing season were particularly sensitive to changes in winter snow pack accumulation and winter soil temperature variability, especially in spring. Effects of elevation and winter conditions on N transformation rates differed from those on potential microbial respiration, suggesting that N‐related processes might respond differently to winter climate change in northern hardwood forests than C‐related processes.

Characterization of T gene sequence variants and germline duplications in familial and sporadic chordoma - Michael J. Kelley; Jianxin Shi; Bari Ballew; Paula L. Hyland; Wen-Qing Li; Melissa Rotunno; David A. Alcorta; Norbert J. Liebsch; Jason Mitchell; Sara Bass; David Roberson; Joseph Boland; et al. (Human Genetics, 2014)

Investigation of Dry Powder Inhaler (DPI) Resistance and Aerosol Dispersion Timing on Emitted Aerosol Aerodynamic Particle Sizing by Multistage Cascade Impactor when Sampled Volume Is Reduced from Compendial Value of 4 L - Hlack Mohammed; Jan Arp; Frank Chambers; Mark Copley; Volker Glaab; Mark Hammond; Derek Solomon; Kerry Bradford; Theresa Russell; Yvonne Sizer; Steven C. Nichols; Daryl L. Roberts; et al. (AAPS PharmSciTech, 2014)

From egg to hatchling: preferential retention of fatty acid biomarkers in young‐of‐the‐year Port Jackson sharks Heterodontus portusjacksoni - C. L. Beckmann; J. G. Mitchell; L. Seuront; D.A.J. Stone; C. Huveneers (Journal of Fish Biology, 2014)
The muscle and liver fatty acid composition of young‐of‐the‐year ( YOY ) Port Jackson sharks Heterodontus portusjacksoni were investigated to determine the effects of a known dietary lipid source v . maternal input as demonstrated by egg yolk fatty acid profiles. Ten Heterodontus portusjacksoni egg yolks were collected in situ and compared with four hatched H. portusjacksoni fed a known diet in a controlled feeding experiment of 185 days. This study demonstrated that fatty acids are probably conservatively transferred from egg yolks to YOY H. portusjacksoni , while diet did not have a large effect on the fatty acid composition of the liver or muscle.

Quantifying the impact of environmental variables upon catch per unit effort of the blue shark Prionace glauca in the western English Channel - J. D. Mitchell; K. J. Collins; P. I. Miller; L. A. Suberg (Journal of Fish Biology, 2014)
The effect of environmental variables on blue shark Prionace glauca catch per unit effort ( CPUE ) in a recreational fishery in the western English Channel, between June and September 1998–2011, was quantified using generalized additive models ( GAMs ). Sea surface temperature ( SST ) explained 1·4% of GAM deviance, and highest CPUE occurred at 16·7° C, reflecting the optimal thermal preferences of this species. Surface chlorophyll a concentration ( CHL ) significantly affected CPUE and caused 27·5% of GAM deviance. Additionally, increasing CHL led to rising CPUE , probably due to higher productivity supporting greater prey biomass. The density of shelf‐sea tidal mixing fronts explained 5% of GAM deviance, but was non‐significant, with increasing front density negatively affecting CPUE. Time‐lagged frontal density significantly affected CPUE, however, causing 12·6% of the deviance in a second GAM and displayed a positive correlation. This outcome suggested a delay between the evolution of frontal features and the subsequent accumulation of productivity and attraction of higher trophic level predators, such as P. glauca .

Characterization of mitochondrial haplogroups in a large population-based sample from the United States - Sabrina L. Mitchell; Robert Goodloe; Kristin Brown-Gentry; Sarah A. Pendergrass; Deborah G. Murdock; Dana C. Crawford (Human Genetics, 2014)

Land cover changes in the Lachuá region, Guatemala: patterns, proximate causes, and underlying driving forces over the last 50 years - Maura L. Quezada; Víctor Arroyo-Rodríguez; Evangelina Pérez-Silva; T. Mitchell Aide (Regional Environmental Change, 2014)

Facial Emotion Processing in Borderline Personality Disorder: A Systematic Review and Meta-Analysis - Amy E. Mitchell; Geoffrey L. Dickens; Marco M. Picchioni (Neuropsychology Review, 2014)

The significance of the D ewar valence photoisomer as a UV radiation‐induced DNA photoproduct in marine microbial communities - Jarah A. Meador; Amy J. Baldwin; J. Dean Pakulski; Wade H. Jeffrey; David L. Mitchell; Thierry Douki (Environmental Microbiology, 2014)
Summary Induction of pyrimidine dimers in DNA by solar UV radiation has drastic effects on microorganisms. To better define the nature of these DNA photoproducts in marine bacterioplankton and eukaryotes, a study was performed during a cruise along a latitudinal transect in the P acific Ocean. The frequency of all possible cyclobutane pyrimidine dimers, pyrimidine (6‐4) pyrimidone photoproducts (64 PPs ) and their related D ewar valence isomers ( DEWs ) was determined by high‐performance liquid chromatography–mass spectrometry. Studied samples were bacterioplankton and eukaryotic fractions isolated from sea water either collected before sunrise or exposed to ambient sunlight from sunrise to sunset. Isolated DNA dosimeters were also exposed to daily sunlight for comparison purposes. A first major result was the observation in all samples of large amounts of DEWs , a class of photoproducts rarely considered outside photochemical studies. Evidence was obtained for a major role of UVA in the formation of these photoisomerization products of 64 PPs . Considerations on the ratio between the different classes of photoproducts in basal and induced DNA damage suggests that photoenzymatic repair ( PER ) is an important DNA repair mechanism used by marine microorganisms occupying surface seawater in the open ocean. This result emphasizes the biological role of DEWs which are very poor substrate for PER .

Natural soil microbes alter flowering phenology and the intensity of selection on flowering time in a wild Arabidopsis relative - Maggie R. Wagner; Derek S. Lundberg; Devin Coleman‐Derr; Susannah G. Tringe; Jeffery L. Dangl; Thomas Mitchell‐Olds (Ecology Letters, 2014)
Plant phenology is known to depend on many different environmental variables, but soil microbial communities have rarely been acknowledged as possible drivers of flowering time. Here, we tested separately the effects of four naturally occurring soil microbiomes and their constituent soil chemistries on flowering phenology and reproductive fitness of Boechera stricta , a wild relative of Arabidopsis. Flowering time was sensitive to both microbes and the abiotic properties of different soils; varying soil microbiota also altered patterns of selection on flowering time. Thus, soil microbes potentially contribute to phenotypic plasticity of flowering time and to differential selection observed between habitats. We also describe a method to dissect the microbiome into single axes of variation that can help identify candidate organisms whose abundance in soil correlates with flowering time. This approach is broadly applicable to search for microbial community members that alter biological characteristics of interest.

Wnt5a, TLR2 and TLR4 are elevated in advanced human atherosclerotic lesions - Ramiro Malgor; Pooja M. Bhatt; Beth A. Connolly; Denise L. Jacoby; Kyle J. Feldmann; Mitchell J. Silver; Masato Nakazawa; Kelly D. McCall; Douglas J. Goetz (Inflammation Research, 2014)

Cascading Effects of Climate Change on Forest Ecosystems: Biogeochemical Links Between Trees and Moose in the Northeast USA - L. M. Christenson; M. J. Mitchell; P. M. Groffman; G. M. Lovett (Ecosystems, 2014)

The value of plantation forests for plant, invertebrate and bird diversity and the potential for cross-taxon surrogacy - Sandra Irwin; Scott M. Pedley; Linda Coote; Anke C. Dietzsch; Mark W. Wilson; Anne Oxbrough; Oisín Sweeney; Karen M. Moore; Rebecca Martin; Daniel L. Kelly; Fraser J. G. Mitchell; Thomas C. Kelly; et al. (Biodiversity and Conservation, 2014)

Impaired learning of predators and lower prey survival under elevated CO 2 : a consequence of neurotransmitter interference - Douglas P. Chivers; Mark I. McCormick; Göran E. Nilsson; Philip L. Munday; Sue‐Ann Watson; Mark G. Meekan; Matthew D. Mitchell; Katherine C. Corkill; Maud C. O. Ferrari (Global Change Biology, 2014)
Ocean acidification is one of the most pressing environmental concerns of our time, and not surprisingly, we have seen a recent explosion of research into the physiological impacts and ecological consequences of changes in ocean chemistry. We are gaining considerable insights from this work, but further advances require greater integration across disciplines. Here, we showed that projected near‐future CO 2 levels impaired the ability of damselfish to learn the identity of predators. These effects stem from impaired neurotransmitter function; impaired learning under elevated CO 2 was reversed when fish were treated with gabazine, an antagonist of the GABA ‐A receptor – a major inhibitory neurotransmitter receptor in the brain of vertebrates. The effects of CO 2 on learning and the link to neurotransmitter interference were manifested as major differences in survival for fish released into the wild. Lower survival under elevated CO 2 , as a result of impaired learning, could have a major influence on population recruitment.

Temperature impacts on anaerobic biotransformation of LNAPL and concurrent shifts in microbial community structure - Natalie R. Zeman; Maria Irianni Renno; Mitchell R. Olson; L. Paige Wilson; Thomas C. Sale; Susan K. De Long (Biodegradation, 2014)

Land‐sharing versus land‐sparing logging: reconciling timber extraction with biodiversity conservation - David P. Edwards; James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; David J. R. Andrews; Mia A. Derhé; Teegan D. S. Docherty; Wayne W. Hsu; Simon L. Mitchell; Takahiro Ota; Leah J. Williams; et al. (Global Change Biology, 2014)
Selective logging is a major driver of rainforest degradation across the tropics. Two competing logging strategies are proposed to meet timber demands with the least impact on biodiversity: land sharing, which combines timber extraction with biodiversity protection across the concession; and land sparing, in which higher intensity logging is combined with the protection of intact primary forest reserves. We evaluate these strategies by comparing the abundances and species richness of birds, dung beetles and ants in Borneo, using a protocol that allows us to control for both timber yield and net profit across strategies. Within each taxonomic group, more species had higher abundances with land‐sparing than land‐sharing logging, and this translated into significantly higher species richness within land‐sparing concessions. Our results are similar when focusing only on species found in primary forest and restricted in range to Sundaland, and they are independent of the scale of sampling. For each taxonomic group, land‐sparing logging was the most promising strategy for maximizing the biological value of logging operations.

The incidence of PALB2 c.3113G>A in women with a strong family history of breast and ovarian cancer attending familial cancer centres in Australia - Zhi L. Teo; Sarah D. Sawyer; Paul A. James; Gillian Mitchell; Alison H. Trainer; Geoffrey J. Lindeman; Kylie Shackleton; Linda Cicciarelli; Melissa C. Southey (Familial Cancer, 2013)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Light and nutrient control of photosynthesis in natural phytoplankton populations from the Chukchi and Beaufort seas, Arctic Ocean - Molly A. Palmer; Gert L. van Dijken; B. Greg Mitchell; Brian J. Seegers; Kate E. Lowry; Matthew M. Mills; Kevin R. Arrigo (Limnology and Oceanography, 2013)
During the 2010–2011 ‘Impacts of Climate Change on the EcoSystems and Chemistry of the Arctic Pacific Environment’ project, we measured photosynthetic parameters in natural Arctic phytoplankton assemblages from the Chukchi and Beaufort seas. Water‐column samples were taken from the near surface (3.1 ± 0.9 m) and subsurface (28 ± 10.3 m) at ∼ 85 stations each year representing a wide range of ecological conditions, including under sea ice (UI) and in open water (OW). The physiological response of phytoplankton to light was used to assess photo‐acclimation, photosynthetic efficiency, and maximum chlorophyll a (Chl a ) normalized rates of carbon fixation. Phytoplankton from the subsurface were acclimated to lower irradiance, as evidenced by higher photosynthetic efficiencies ( α * ), reduced mean absorption spectra ( ā * ) associated with heavy pigment packaging, higher maximum quantum yields of photosynthesis (Φ m ), increased Chl a content (Chl a : POC), and higher potential growth rates ( μ m ) than surface samples. In addition, phytoplankton growing in the UI subsurface had higher μ m , increased Φ m , and higher Chl a content, as well as reduced ā * compared with those found in OW. P * m did not vary between habitats despite vastly different nutrient and light conditions (averaging ∼ 1 mg C mg −1 Chl a h −1 ), except where nitrate exceeded > 10 mg m −3 , in which case P * m averaged 5–6 mg C mg −1 Chl a h −1 . Results from a stepwise regression analysis of photosynthetic parameters vs. environmental factors indicate that the concentration of inorganic nitrogen (significant relationships with P * m , α * , Φ m , μ m , and Chl a : POC) and temperature at sample depth (a strong indicator of habitat type; significant relationship with β * , ā * , Φ m , μ m , and Chl a : POC) are the best predictors of photosynthetic variables. In addition, the amount of light available at sample depth significantly predicted both E k and Chl a : POC. Our results suggest that it is the balance between light and nutrient availability in the various environments encountered in the seasonal sea ice zone that result in the pattern of photo‐physiological data presented here. A significant proportion of primary production has now been observed to occur under the sea ice; therefore, our results may be a change from prior conditions in the region.

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Trophic Flexibility and the Persistence of Understory Birds in Intensively Logged Rainforest - DAVID P. EDWARDS; PAUL WOODCOCK; ROB J. NEWTON; FELICITY A. EDWARDS; DAVID J. R. ANDREWS; TEEGAN D. S. DOCHERTY; SIMON L. MITCHELL; TAKAHIRO OTA; SUZAN BENEDICK; SIMON H. BOTTRELL; KEITH C. HAMER (Conservation Biology, 2013)
Effects of logging on species composition in tropical rainforests are well known but may fail to reveal key changes in species interactions. We used nitrogen stable‐isotope analysis of 73 species of understory birds to quantify trophic responses to repeated intensive logging of rainforest in northern Borneo and to test 4 hypotheses: logging has significant effects on trophic positions and trophic‐niche widths of species, and the persistence of species in degraded forest is related to their trophic positions and trophic‐niche widths in primary forest. Species fed from higher up the food chain and had narrower trophic‐niche widths in degraded forest. Species with narrow trophic‐niche widths in primary forest were less likely to persist after logging, a result that indicates a higher vulnerability of dietary specialists to local extinction following habitat disturbance. Persistence of species in degraded forest was not related to a species’ trophic position. These results indicate changes in trophic organization that were not apparent from changes in species composition and highlight the importance of focusing on trophic flexibility over the prevailing emphasis on membership of static feeding guilds. Our results thus support the notion that alterations to trophic organization and interactions within tropical forests may be a pervasive and functionally important hidden effect of forest degradation. Flexibilidad Trófica y la Persistencia de Aves de Sotobosque en un Bosque Lluvioso Talado Intensivamente

Efficacy of novel sampling approaches for surveying specialised recreational fisheries - Shane P. Griffiths; Mitchell T. Zischke; Mark L. Tonks; Julian G. Pepperell; Sharon Tickell (Reviews in Fish Biology and Fisheries, 2013)

Using fisheries by‐catch data to predict octocoral habitat suitability around South Georgia - Michelle L. Taylor; Chris Yesson; David J. Agnew; Rebecca E. Mitchell; Alex D. Rogers (Journal of Biogeography, 2013)
Aim For many deep‐sea fisheries, there is an urgent management requirement for information on the presence of vulnerable marine ecosystems ( VME s). Gathering deep‐sea data using conventional techniques can be expensive and time‐consuming. One way to provide a relatively rapid assessment of VME presence is to use data from fisheries by‐catch and historical scientific observations. Our aim was to predict suitable habitat for octocorals around South Georgia and to estimate the extent to which octocoral habitat is currently protected by fisheries management measures. In addition, we attempted to determine the types of terrain in which octocorals and fishing activities occur. Location South Georgia, sub‐Antarctic. Methods A terrain map of South Georgia was created using Benthic Terrain Modeler ( BTM ). Georeferenced octocoral data were combined with environmental layers to create an octocoral habitat suitability map using ecological niche factor analysis ( ENFA ). Results Most octocoral by‐catch samples originated from narrow crest (an area representing shelf break and moraines) and steep (continental) slope terrains. Calcite saturation state and apparent oxygen utilization ( AOU ) were the most influential environmental parameters in determining highly suitable octocoral habitat. The ENFA model highlighted shelf‐break areas to be highly suitable habitat for octocorals and that 38% of this habitat around South Georgia lies within areas currently protected by fisheries management; a further 20% is below the 2000‐m fishing depth, meaning effectively that 58% of predicted highly suitable octocoral habitat is currently protected. Although these results indicate protection levels for octocoral habitat well above international standards/targets, the fishery remains active within a relatively concentrated shelf area at 700–2000 m, potentially having a large impact on the 42% of highly suitable octocoral habitat predicted to lie at these depths. Main conclusions This research demonstrates the potential for using fisheries by‐catch data to create habitat suitability maps that can inform fisheries management and future research.

Methamphetamine and core temperature in the rat: Ambient temperature, dose, and the effect of a D2 receptor blocker - Karen E. Sabol; Danielle M. Yancey; H. Anton Speaker; Scott L. Mitchell (Psychopharmacology, 2013)

Sewage reflects the distribution of human faecal L achnospiraceae - Sandra L. McLellan; Ryan J. Newton; Jessica L. Vandewalle; Orin C. Shanks; Susan M. Huse; A. Murat Eren; Mitchell L. Sogin (Environmental Microbiology, 2013)
Summary Faecal pollution contains a rich and diverse community of bacteria derived from animals and humans, many of which might serve as alternatives to the traditional enterococci and E scherichia coli faecal indicators. We used massively parallel sequencing ( MPS ) of the 16 S rRNA gene to characterize microbial communities from wastewater treatment plant ( WWTP ) influent sewage from 12 cities geographically distributed across the USA . We examined members of the C lostridiales , which included the families C lostridiaceae , L achnospiraceae and R uminococcaceae for their potential as sewage indicators. L achnospiraceae was one of the most abundant groups of faecal bacteria in sewage, and several L achnospiraceae high‐abundance sewage pyrotags occurred in at least 46 of 48 human faecal samples. Clone libraries targeting C lostridium coccoides ( C . coccoides ) in sewage samples demonstrated that Lachnospiraceae ‐annotated V 6 pyrotags encompassed the previously reported C . coccoides group. We used oligotyping to profile the genus B lautia within L achnospiraceae and found oligotypes comprised of 24 entropy components that showed patterns of host specificity. These findings suggest that indicators based on B lautia might have the capacity to discriminate between different faecal pollution sources. Development of source‐specific alternative indicators would enhance water quality assessments, which leads to improved ecosystem health and reduced human health risk due to waterborne disease.

From Patient to Participant: Enhancing the Validity and Ethics of Cancer Research through Participatory Research - Connie G. Chiu; Terry L. Mitchell; Margaret I. Fitch (Journal of Cancer Education, 2013)

Chemistry and Microbial Functional Diversity Differences in Biofuel Crop and Grassland Soils in Multiple Geographies - Lidia S. Watrud; Jay R. Reichman; Michael A. Bollman; Bonnie M. Smith; E. Henry Lee; Julie D. Jastrow; Michael D. Casler; Harold P. Collins; Steven Fransen; Robert B. Mitchell; Vance N. Owens; Brent Bean; et al. (BioEnergy Research, 2013)

The Effect of Nonideal Cascade Impactor Stage Collection Efficiency Curves on the Interpretation of the Size of Inhaler-Generated Aerosols - D. L. Roberts; J. P. Mitchell (AAPS PharmSciTech, 2013)

Macroecological patterns of marine bacteria on a global scale - Anthony S. Amend; Tom A. Oliver; Linda A. Amaral‐Zettler; Antje Boetius; Jed A. Fuhrman; M. Claire Horner‐Devine; Susan M. Huse; David B. Mark Welch; Adam C. Martiny; Alban Ramette; Lucie Zinger; Mitchell L. Sogin; et al. (Journal of Biogeography, 2013)
Aim To test whether within‐species and among‐species patterns of abundance and latitudinal range in marine bacteria resemble those found for macro‐organisms, and whether these patterns differ along latitudinal clines. Location Global pelagic marine environments. Methods Taxon‐specific sequence abundance and location were retrieved from the open‐access V6‐ rRNA pyrotag sequence data base VAMPS ( http://vamps.mbl.edu/ ), which holds a massive collection of marine bacterial community data sets from the I nternational C ensus of M arine M icrobes sampling effort of global ocean water masses. Data were randomly subsampled to correct for spatial bias and for differences in sampling effort. Results We show that bacterial latitudinal ranges are narrower than expected by chance. When present in both N orthern and S outhern hemispheres, taxa occupy restricted ranges at similar latitudes on both sides of the equator. A significant and positive relationship exists between sequence abundance and latitudinal range, although this pattern contains a large amount of variance. Abundant taxa in the tropics and in the N orthern H emisphere generally have smaller ranges than those in the S outhern H emisphere. We show that the mean latitudinal range of bacterial taxa increases with latitude, supporting the existence of a R apoport effect in marine bacterioplankton. Finally, we show that bacterioplankton communities contain a higher proportion of abundant taxa as they approach the poles. Main conclusions Macroecological patterns such as the abundance–range relationship, in general, extend to marine bacteria. However, differences in the shape of these relationships between bacteria and macro‐organisms call into question whether the processes and their relative importance in shaping global marine bacteria and macro‐organism distributions are the same.

Microsatellite loci development for rare Colorado Sclerocactus (Cactaceae) - Anna L. Schwabe; Ashley R. Hubbard; Jennifer Ramp Neale; Mitchell E. McGlaughlin (Conservation Genetics Resources, 2013)

Good Cascade Impactor Practice (GCIP) and Considerations for “In-Use” Specifications - S. C. Nichols; J. P. Mitchell; C. M. Shelton; D. L. Roberts (AAPS PharmSciTech, 2013)

Contrasting Patterns of Urban Expansion in Colombia, Ecuador, Peru, and Bolivia Between 1992 and 2009 - Nora L. Álvarez-Berríos; Isabel K. Parés-Ramos; T. Mitchell Aide (Ambio, 2013)

Confirmatory factor analysis of the ADNI neuropsychological battery - Lovingly Quitania Park; Alden L. Gross; Donald G. McLaren; Judy Pa; Julene K. Johnson; Meghan Mitchell; Jennifer J. Manly (Brain Imaging and Behavior, 2012)

Cortical signatures of cognition and their relationship to Alzheimer’s disease - Alden L. Gross; Jennifer J. Manly; Judy Pa; Julene K. Johnson; Lovingly Quitania Park; Meghan B. Mitchell; Rebecca J. Melrose; Sharon K. Inouye; Donald G. McLaren (Brain Imaging and Behavior, 2012)

Varenicline decreases alcohol consumption in heavy-drinking smokers - Jennifer M. Mitchell; Candice H. Teague; Andrew S. Kayser; Selena E. Bartlett; Howard L. Fields (Psychopharmacology, 2012)

A weight-of-evidence review of colorectal cancer in pesticide applicators: the agricultural health study and other epidemiologic studies - Dominik D. Alexander; Douglas L. Weed; Pamela J. Mink; Meghan E. Mitchell (International Archives of Occupational and Environmental Health, 2012)

A comparative study of respiratory syncytial virus (RSV) prophylaxis in premature infants within the Canadian Registry of Palivizumab (CARESS) - B. Paes; I. Mitchell; A. Li; K. L. Lanctôt (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

The influence of socioeconomic, environmental, and demographic factors on municipality-scale land-cover change in Mexico - Martha Bonilla-Moheno; T. Mitchell Aide; Matthew L. Clark (Regional Environmental Change, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Evaluation of a digital microfluidic real-time PCR platform to detect DNA of Candida albicans in blood - W. A. Schell; J. L. Benton; P. B. Smith; M. Poore; J. L. Rouse; D. J. Boles; M. D. Johnson; B. D. Alexander; V. K. Pamula; A. E. Eckhardt; M. G. Pollack; D. K. Benjamin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

2,3-Hexanediols as Sex Attractants and a Female-produced Sex Pheromone for Cerambycid Beetles in the Prionine Genus Tragosoma - Ann M. Ray; James D. Barbour; J. Steven McElfresh; Jardel A. Moreira; Ian Swift; Ian M. Wright; Alenka Žunič; Robert F. Mitchell; Elizabeth E. Graham; Ronald L. Alten; Jocelyn G. Millar; Lawrence M. Hanks (Journal of Chemical Ecology, 2012)

Effect of Sampling Volume on Dry Powder Inhaler (DPI)-Emitted Aerosol Aerodynamic Particle Size Distributions (APSDs) Measured by the Next-Generation Pharmaceutical Impactor (NGI) and the Andersen Eight-Stage Cascade Impactor (ACI) - Hlack Mohammed; Daryl L. Roberts; Mark Copley; Mark Hammond; Steven C. Nichols; Jolyon P. Mitchell (AAPS PharmSciTech, 2012)

Mortality in the California Farmer Health Study Cohort - Tracey L. Armitage; Diane Mitchell; Marc Schenker (Journal of Agromedicine, 2012)

Peracetic acid is effective for controlling fungus on channel catfish eggs - D L Straus; T Meinelt; B D Farmer; A J Mitchell (Journal of Fish Diseases, 2012)
Peracetic acid (PAA) is a relatively new compound suggested for use to treat pathogens in aquaculture. It is approved for use in Europe, but not in the United States. This study determined the effectiveness of PAA for fungus control on channel catfish, Ictalurus punctatus (Rafinesque), eggs. The study consisted of five PAA concentrations (2.5, 5, 10, 15 and 20 mg L −1 ) and an untreated control in a flow‐through system. A single spawn was used for each replication ( N = 4). Eggs were treated twice daily until the embryos developed eyes. When hatching was complete for all viable eggs, fry were counted to determine the percent survival in each treatment. Fungal growth was severe in the untreated controls resulting in 11% survival. Treatments of 2.5, 5 and 10 mg L −1 PAA were significantly different from the controls ( P 0.05). The highest percent survival of hatched fry was with 5 mg L −1 PAA administered twice daily; the 2.5 mg L −1 PAA treatment had slightly less survival, but gives a higher margin of safety in case of treatment error. Very little fungus was present in treatments receiving 2.5 mg L −1 PAA or higher, and concentrations of 15 and 20 mg L −1 PAA were toxic to the eggs. The mean survivals in the 0, 2.5, 5, 10, 15 and 20 mg L −1 PAA treatments were 11%, 60%, 63%, 62%, 32% and 0%, respectively. Therefore, PAA may be a compound that merits further investigations regarding its use in U.S. aquaculture.

Explaining the variation in the soil microbial community: do vegetation composition and soil chemistry explain the same or different parts of the microbial variation? - Ruth Joy Mitchell; Alison J. Hester; Colin D. Campbell; Stephen J. Chapman; Clare M. Cameron; Richard L. Hewison; Jackie M. Potts (Plant and Soil, 2012)

Characterisation of MHC haplotypes in a breeding colony of Indonesian cynomolgus macaques reveals a high level of diversity - Jane L. Mitchell; Edward T. Mee; Neil M. Almond; Keith Cutler; Nicola J. Rose (Immunogenetics, 2012)

Effects of acute administration of nicotine, amphetamine, diazepam, morphine, and ethanol on risky decision-making in rats - Marci R. Mitchell; Colin M. Vokes; Amy L. Blankenship; Nicholas W. Simon; Barry Setlow (Psychopharmacology, 2011)

Shoot pruning of a hedgerow perennial legume alters the availability and temporal dynamics of root-derived nitrogen in a subtropical setting - Yolima Carrillo; Carl F. Jordan; Krista L. Jacobsen; Kathryn G. Mitchell; Patrick Raber (Plant and Soil, 2011)

Structured decision making as a proactive approach to dealing with sea level rise in Florida - Julien Martin; Paul L. Fackler; James D. Nichols; Bruce C. Lubow; Mitchell J. Eaton; Michael C. Runge; Bradley M. Stith; Catherine A. Langtimm (Climatic Change, 2011)

Effects of morphine on pain-elicited and pain-suppressed behavior in CB1 knockout and wildtype mice - Laurence L. Miller; Mitchell J. Picker; Karl T. Schmidt; Linda A. Dykstra (Psychopharmacology, 2011)

Synthesis and biological evaluation of a novel anti-malarial lead - Nicholas L. Hammond; Seoung-ryoung Choi; Paulo Carvalho; Hua Liu; Shabana Khan; Mitchell A. Avery (Medicinal Chemistry Research, 2011)

Postdiagnosis diet quality, the combination of diet quality and recreational physical activity, and prognosis after early-stage breast cancer - Stephanie M. George; Melinda L. Irwin; Ashley W. Smith; Marian L. Neuhouser; Jill Reedy; Anne McTiernan; Catherine M. Alfano; Leslie Bernstein; Cornelia M. Ulrich; Kathy B. Baumgartner; Steven C. Moore; Demetrius Albanes; et al. (Cancer Causes & Control, 2011)

Role of the atmospheric mean state on the initiation of the Madden-Julian oscillation in a tropical channel model - Pallav Ray; Chidong Zhang; Mitchell W. Moncrieff; Jim Dudhia; Julie M. Caron; L. Ruby Leung; Cindy Bruyere (Climate Dynamics, 2011)

Seroprevalence of seasonal and pandemic influenza A viruses in domestic cats - Jonathan A. McCullers; Lee-Ann Van De Velde; Ronald D. Schultz; Cristen G. Mitchell; C. R. Halford; Kelli L. Boyd; Stacey Schultz-Cherry (Archives of Virology, 2011)

Minimally invasive assessment of tumor angiogenesis by fine needle aspiration and flow cytometry - Joseph L. Sottnik; Amanda M. Guth; Leah A. Mitchell; Steven W. Dow (Angiogenesis, 2010)

Effects of chronic and intermittent cocaine treatment on dominance, aggression, and oxytocin levels in post-lactational rats - Josephine M. Johns; Matthew S. McMurray; Paul W. Joyner; Thomas M. Jarrett; Sarah K. Williams; Elizabeth T. Cox; Mitchell A. Black; Christopher L. Middleton; Cheryl H. Walker (Psychopharmacology, 2010)

Temporal and spatial changes in cell wall composition in developing grains of wheat cv. Hereward - G. A. Toole; G. Le Gall; I. J. Colquhoun; C. Nemeth; L. Saulnier; A. Lovegrove; T. Pellny; M. D. Wilkinson; J. Freeman; R. A. C. Mitchell; E. N. C. Mills; P. R. Shewry (Planta, 2010)

Is vegetation composition or soil chemistry the best predictor of the soil microbial community? - Ruth J. Mitchell; Alison J. Hester; Colin D. Campbell; Stephen J. Chapman; Clare M. Cameron; Richard L. Hewison; Jackie M. Potts (Plant and Soil, 2010)

Hurricane Katrina storm surge delineation: implications for future storm surge forecasts and warnings - Ginni Melton; Melanie Gall; Jerry T. Mitchell; Susan L. Cutter (Natural Hazards, 2010)

Body mass index, effect modifiers, and risk of pancreatic cancer: a pooled study of seven prospective cohorts - Li Jiao; Amy Berrington de Gonzalez; Patricia Hartge; Ruth M. Pfeiffer; Yikyung Park; D. Michal Freedman; Mitchell H. Gail; Michael C. R. Alavanja; Demetrius Albanes; Laura E. Beane Freeman; Wong-Ho Chow; Wen-Yi Huang; et al. (Cancer Causes & Control, 2010)

Interannual variability and controls of the Sydney wave climate - Mitchell D. Harley; Ian L. Turner; Andrew D. Short; Roshanka Ranasinghe (International Journal of Climatology, 2010)
A multi‐decadal beach survey dataset at a coastal embayment in Sydney, Australia, identifies erosion/accretion cycles coinciding with phase shifts in the El Niño/Southern Oscillation (ENSO). In an attempt to explain the processes governing these cycles, this study explores the interannual variability and controls of the Sydney wave climate using ECMWF ERA‐40 and corrected ERA‐40 (C‐ERA‐40) reanalysis data. Comparisons with wave measurements collected by the Sydney waverider buoy show that these datasets represent the Sydney wave climate reasonably well, although westerly waves are significantly over‐predicted. Removing these values strengthens correlations between predicted and measured wave heights. A summary of the Sydney wave climate from 1957 to 2002 is presented, which highlights the high degree of variability in storm events. Controls of interannual variability are investigated by comparing values in Sydney with regional mean sea level pressure anomalies, the Southern Oscillation Index (SOI) and the Southern Annular Mode (SAM). Austral summer wave heights over this 45‐year period increase/decrease with positive/negative phases of the SOI and the SAM. An inverse relationship is found between wave directions and the SOI for the austral autumn and spring; and between wave directions and the SAM for the austral winter. Variability of storm events in Sydney is significantly correlated with the SOI, but not the SAM. In particular, La Niña phases are generally associated with longer duration, higher‐energy events from a more easterly direction when compared to those during El Niño phases. Copyright © 2009 Royal Meteorological Society

Ironing out the wrinkles in the rare biosphere through improved OTU clustering - Susan M. Huse; David Mark Welch; Hilary G. Morrison; Mitchell L. Sogin (Environmental Microbiology, 2010)
Summary Deep sequencing of PCR amplicon libraries facilitates the detection of low‐abundance populations in environmental DNA surveys of complex microbial communities. At the same time, deep sequencing can lead to overestimates of microbial diversity through the generation of low‐frequency, error‐prone reads. Even with sequencing error rates below 0.005 per nucleotide position, the common method of generating operational taxonomic units (OTUs) by multiple sequence alignment and complete‐linkage clustering significantly increases the number of predicted OTUs and inflates richness estimates. We show that a 2% single‐linkage preclustering methodology followed by an average‐linkage clustering based on pairwise alignments more accurately predicts expected OTUs in both single and pooled template preparations of known taxonomic composition. This new clustering method can reduce the OTU richness in environmental samples by as much as 30–60% but does not reduce the fraction of OTUs in long‐tailed rank abundance curves that defines the rare biosphere.

Factors Influencing Fish Distributions in Shallow Lakes in Prairie and Prairie-Parkland Regions of Minnesota, USA - Brian R. Herwig; Kyle D. Zimmer; Mark A. Hanson; Melissa L. Konsti; Jerry A. Younk; Robert W. Wright; Sean R. Vaughn; Mitchell D. Haustein (Wetlands, 2010)

Characterisation of white line degeneration in sheep and evidence for genetic influences on its occurrence - Joanne Conington; Laura Nicoll; Stephen Mitchell; L. Bünger (Veterinary Research Communications, 2010)

Barcoding bushmeat: molecular identification of Central African and South American harvested vertebrates - Mitchell J. Eaton; Greta L. Meyers; Sergios-Orestis Kolokotronis; Matthew S. Leslie; Andrew P. Martin; George Amato (Conservation Genetics, 2010)

Linear increases in BOLD response associated with increasing proportion of incongruent trials across time in a colour Stroop task - Rachel L. C. Mitchell (Experimental Brain Research, 2010)

Short-term endurance training does not alter the oxidative capacity of human subcutaneous adipose tissue - Donny M. Camera; Mitchell J. Anderson; John A. Hawley; Andrew L. Carey (European Journal of Applied Physiology, 2010)

Second Harmonic Generation Imaging and Fourier Transform Spectral Analysis Reveal Damage in Fatigue-Loaded Tendons - David T. Fung; Jedd B. Sereysky; Jelena Basta-Pljakic; Damien M. Laudier; Rumana Huq; Karl J. Jepsen; Mitchell B. Schaffler; Evan L. Flatow (Annals of Biomedical Engineering, 2010)

The cag PAI is intact and functional but HP0521 varies significantly in Helicobacter pylori isolates from Malaysia and Singapore - H.-M. A. Schmidt; S. Andres; C. Nilsson; Z. Kovach; N. O. Kaakoush; L. Engstrand; K.-L. Goh; K. M. Fock; D. Forman; H. Mitchell (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Testing Hypotheses of Bird Extinctions at Rio Palenque, Ecuador, with Informal Species Lists - DAVID L. PEARSON; COREY DEVIN ANDERSON; BRIAN R. MITCHELL; MICHAEL S. ROSENBERG; RONALD NAVARRETE; PAUL COOPMANS (Conservation Biology, 2010)
Informally gathered species lists are a potential source of data for conservation biology, but most remain unused because of questions of reliability and statistical issues. We applied two alternative analytical methods (contingency tests and occupancy modeling) to a 35‐year data set (1973–2007) to test hypotheses about local bird extinction. We compiled data from bird lists collected by expert amateurs and professional scientists in a 2‐km 2 fragment of lowland tropical forest in coastal Ecuador. We tested the effects of the following on local extinction: trophic level, sociality, foraging specialization, light tolerance, geographical range area, and biogeographic source. First we assessed extinction on the basis of the number of years in which a species was not detected on the site and used contingency tests with each factor to compare the frequency of expected and observed extinction events among different species categories. Then we defined four multiyear periods that reflected different stages of deforestation and isolation of the study site and used occupancy modeling to test extinction hypotheses singly and in combination. Both types of analyses supported the biogeographic source hypothesis and the species‐range hypothesis as causes of extinction; however, occupancy modeling indicated the model incorporating all factors except foraging specialization best fit the data.

Ultraviolet radiation affects invasibility of lake ecosystems by warm‐water fish - Andrew J. Tucker; Craig E. Williamson; Kevin C. Rose; James T. Oris; Sandra J. Connelly; Mark H. Olson; David L. Mitchell (Ecology, 2010)
Predicting where species invasions will occur remains a substantial challenge in ecology, but identifying factors that ultimately constrain the distribution of potential invaders could facilitate successful prediction. Whereas ultraviolet radiation (UVR) is recognized as an important factor controlling species distribution and community composition, the role of UVR in a habitat invasibility context has not been explored. Here we examine how underwater UVR can regulate warm‐water fish invasion. In Lake Tahoe, California and Nevada, USA, established populations of exotic bluegill sunfish ( Lepomis macrochirus ) are currently limited to turbid, low‐UVR embayments. An in situ incubation experiment that manipulated incident UVR exposure of larval bluegill, combined with an assessment of UVR exposure levels in nearshore habitats around Lake Tahoe, demonstrates that UVR can mediate habitat invasibility. Our findings suggest that the susceptibility to invasion by UVR sensitive species may increase in transparent aquatic systems threatened by declining water quality, and they highlight the importance of abiotic factors as regulators of invasion risk in ecosystems.

Genetic diversity and population structure analysis of accessions in the US historic sweet sorghum collection - Ming L. Wang; Chengsong Zhu; Noelle A. Barkley; Zhenbang Chen; John E. Erpelding; Seth C. Murray; Mitchell R. Tuinstra; Tesfaye Tesso; Gary A. Pederson; Jianming Yu (Theoretical and Applied Genetics, 2009)

Balancing Risk and Costs to Optimize the Clinical Supply Chain—A Step Beyond Simulation - Chedia Abdelkafi; Benoît H. L. Beck; Benoit David; Cédric Druck; Mitchell Horoho (Journal of Pharmaceutical Innovation, 2009)

The curse of taxonomic uncertainty in biogeographical studies of free‐living terrestrial protists: a case study of testate amoebae from Amsterdam Island - T. J. Heger; E. A. D. Mitchell; P. Ledeganck; S. Vincke; B. Van de Vijver; L. Beyens (Journal of Biogeography, 2009)
Aim A current debate in microbial biogeography contrasts two views concerning the distribution of free‐living microorganisms. The first view assumes a ubiquitous distribution, while the second assumes that at least some species have limited geographical distributions. We tested for limited geographical distributions by identifying testate amoebae morphospecies from an extremely remote oceanic island where the potential for endemism is high. Location Amsterdam Island, Indian Ocean. Methods Sixty moss and water samples collected from the top of the volcano to the lowland were investigated for their testate amoeba content. Due to taxonomic uncertainties among the Argynnia ( Nebela ) dentistoma species complex (including A. antarctica ), we also performed light and scanning electron microscopy investigations on the shell ultrastructure and biometric analyses on several specimens of this taxon. Results We identified a total of 43 testate amoeba taxa belonging to 15 genera. Only four testate amoeba taxa had previously been recorded on this island. Testate amoeba communities of Amsterdam Island are dominated by cosmopolitan ubiquitous euglyphid taxa such as Trinema lineare , Assulina muscorum and Corythion dubium . The length and width ranges for Argynnia dentistoma on Amsterdam Island overlap with other records of this species and of A. antarctica , suggesting that A. antarctica is not a distinct taxon. Main conclusions Although Amsterdam Island is among the most remote islands in the world, an extensive inventory of testate amoeba morphospecies provided no clear evidence for endemism. On the one hand, our detailed morphometric analysis of the A. dentistoma complex revealed that A. antarctica , a morphospecies previously suggested to display endemism, cannot be confidently distinguished from the cosmopolitan morphospecies A. dentistoma . On the other hand, five morphotaxa could not be identified with certainty and might represent new species, potentially with limited distribution. These examples illustrate how taxonomic uncertainties undermine biogeographical studies of testate amoebae. In order to allow better interpretation of morphology‐based testate amoeba distribution data, an assessment of genetic diversity among and within morphotaxa in relation to geographical distance for some common testate amoebae should be given high priority.

Comparison of distinct protein isoforms of the receptor for advanced glycation end-products expressed in murine tissues and cell lines - Julia V. Gefter; Angel L. Shaufl; Mitchell P. Fink; Russell L. Delude (Cell and Tissue Research, 2009)

Attraction of New Zealand Flower Thrips, Thrips obscuratus, to cis-Jasmone, a Volatile Identified from Japanese Honeysuckle Flowers - A. M. El-Sayed; V. J. Mitchell; G. F. McLaren; L. M. Manning; B. Bunn; D. M. Suckling (Journal of Chemical Ecology, 2009)

Non-native fishes and native species diversity in freshwater fish assemblages across the United States - Alison L. Mitchell; Jason H. Knouft (Biological Invasions, 2009)

Analysis of quaternary structure of a [LDH-like] malate dehydrogenase of Plasmodium falciparum with oligomeric mutants - Anupam Pradhan; Prasenjit Mukherjee; Abhai K. Tripathi; Mitchell A. Avery; Larry A. Walker; Babu L. Tekwani (Molecular and Cellular Biochemistry, 2009)

Effect of PCR amplicon size on assessments of clone library microbial diversity and community structure - Julie A. Huber; Hilary G. Morrison; Susan M. Huse; Phillip R. Neal; Mitchell L. Sogin; David B. Mark Welch (Environmental Microbiology, 2009)
Summary PCR‐based surveys of microbial communities commonly use regions of the small‐subunit ribosomal RNA (SSU rRNA) gene to determine taxonomic membership and estimate total diversity. Here we show that the length of the target amplicon has a significant effect on assessments of microbial richness and community membership. Using operational taxonomic unit (OTU)‐ and taxonomy‐based tools, we compared the V6 hypervariable region of the bacterial SSU rRNA gene of three amplicon libraries of c. 100, 400 and 1000 base pairs (bp) from each of two hydrothermal vent fluid samples. We found that the smallest amplicon libraries contained more unique sequences, higher diversity estimates and a different community structure than the other two libraries from each sample. We hypothesize that a combination of polymerase dissociation, cloning bias and mispriming due to secondary structure accounts for the differences. While this relationship is not linear, it is clear that the smallest amplicon libraries contained more different types of sequences, and accordingly, more diverse members of the community. Because divergent and lower abundant taxa can be more readily detected with smaller amplicons, they may provide better assessments of total community diversity and taxonomic membership than longer amplicons in molecular studies of microbial communities.

Biosynthesis of avenanthramides in suspension cultures of oat (Avena sativa) - Mitchell L. Wise; Hassan K. Sreenath; Ronald W. Skadsen; Heidi F. Kaeppler (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Possible impacts of anthropogenic and natural aerosols on Australian climate: a review - Leon D. Rotstayn; Melita D. Keywood; Bruce W. Forgan; Albert J. Gabric; Ian E. Galbally; John L. Gras; Ashok K. Luhar; Grant H. McTainsh; Ross M. Mitchell; Stuart A. Young (International Journal of Climatology, 2009)
A review is presented of the aerosol–climate interaction with specific focus on the Australian region. The uncertainties associated with this interaction are much larger than those associated with greenhouse gases or other forcing agents, and are currently a major obstacle in climate‐change research. However, new research suggests that aerosol effects are of comparable importance to greenhouse gases as a driver of recent climate trends in the Southern Hemisphere, including Australia. A significant new result from climate modelling is that anthropogenic aerosol over Asia affects meridional temperature gradients and atmospheric circulation, and may have caused an increase in rainfall over north‐western Australia. Global ocean circulation provides another mechanism whereby aerosol changes in the Northern Hemisphere can affect climate in the Southern Hemisphere, suggesting an urgent need for further targeted studies using coupled ocean‐atmosphere global climate models. To better model climate variability and climate change in the Australian region, more research is needed into the sources of aerosol and their precursors, their atmospheric distributions and transformations, and how to incorporate these processes robustly in global climate models (GCMs). The following priorities are suggested for further research in Australia linking aerosol observations and modelling: natural aerosol over the Southern Ocean, tropical biomass‐burning aerosol in Indonesia and Australia, secondary organic aerosol (SOA) from volatile organic compounds (VOCs), wind‐blown dust and modulation of rainfall by anthropogenic aerosol. Copyright © 2008 Royal Meteorological Society

Effects of nutrients and dissolved organic matter on the response of phytoplankton to ultraviolet radiation: experimental comparison in spring versus summer - Caren E. Scott; Jasmine E. Saros; Craig E. Williamson; Courtney R. Salm; Stephen C. Peters; David L. Mitchell (Hydrobiologia, 2009)

Evaluation of potassium permanganate against an experimental subacute infection of Flavobacterium columnare in channel catfish, Ictalurus punctatus (Rafinesque) - A M Darwish; A J Mitchell; D L Straus (Journal of Fish Diseases, 2009)
An experiment was performed to evaluate the efficacy of potassium permanganate (KMnO 4 ) as a prophylactic and therapeutic treatment of an experimental subacute infection of Flavobacterium columnare in channel catfish, Ictalurus punctatus . Fish were cutaneously abraded and divided into five treatment groups: (i) challenged by waterborne exposure to F. columnare and not treated with KMnO 4 (positive control), (ii) challenged and simultaneously treated with KMnO 4, (iii) challenged and treated with KMnO 4 at 1, 6 and 9 days post‐challenge, (iv) not challenged and treated with KMnO 4 at 1, 6 and 9 days post‐challenge (first negative control) and (v) not challenged and not treated (second negative control). The dosing of KMnO 4 was 2.0 mg L −1 above the potassium permanganate demand for 2 h duration. The survival of the group challenged and simultaneously treated with KMnO 4 (99%) was significantly higher than the positive control (78%) and was not significantly different from the negative control groups. The challenged fish treated with KMnO 4 post‐challenge had 7% higher survival than the positive control (85% compared with 78%), but that difference was not statistically significant. The results demonstrate that KMnO 4 has a clear prophylactic value but probably a marginal therapeutic value once the infection has established.

Cortical activation during delay discounting in abstinent methamphetamine dependent individuals - William F. Hoffman; Daniel L. Schwartz; Marilyn S. Huckans; Bentson H. McFarland; Gal Meiri; Alexander A. Stevens; Suzanne H. Mitchell (Psychopharmacology, 2008)

Risk Management in the Pharmaceutical Product Development Process - Matthew H. Hulbert; Liam C. Feely; Eugene L. Inman; Alton D. Johnson; Albert S. Kearney; James Michaels; Michael Mitchell; Elena Zour (Journal of Pharmaceutical Innovation, 2008)

The influence of diet composition on phase I and II biotransformation enzyme induction - Jaime L. Rudolf; Kathryn A. Bauerly; Eskouhie Tchaparian; Robert B. Rucker; Alyson E. Mitchell (Archives of Toxicology, 2008)

Prevalence of virus-like particles within a staghorn scleractinian coral (Acropora muricata) from the Great Barrier Reef - N. L. Patten; P. L. Harrison; J. G. Mitchell (Coral Reefs, 2008)

Regional-scale models for relating land cover to basin surface-water quality using remotely sensed data in a GIS - V. L. Versace; D. Ierodiaconou; F. Stagnitti; A. J. Hamilton; M. T. Walter; B. Mitchell; A.-M. Boland (Environmental Monitoring and Assessment, 2008)

Increased efficacy of μ-opioid agonist-induced antinociception by metabotropic glutamate receptor antagonists in C57BL/6 mice: comparison with (−)-6-phosphonomethyl-deca-hydroisoquinoline-3-carboxylic acid (LY235959) - Bradford D. Fischer; Laurence L. Miller; Fredrick E. Henry; Mitchell J. Picker; Linda A. Dykstra (Psychopharmacology, 2008)

The Use of Routine Process Capability for the Determination of Process Parameter Criticality in Small-molecule API Synthesis - Kevin D. Seibert; Shanthi Sethuraman; Jerry D. Mitchell; Kristi L. Griffiths; Bernard McGarvey (Journal of Pharmaceutical Innovation, 2008)

The early effects of afforestation on biodiversity of grasslands in Ireland - Erika Buscardo; George F. Smith; Daniel L. Kelly; Helena Freitas; Susan Iremonger; Fraser J. G. Mitchell; Saoirse O’Donoghue; Anne-Marie McKee (Biodiversity and Conservation, 2008)

Epiphytes of Sitka spruce (Picea sitchensis) plantations in Ireland and the effects of open spaces - Linda Coote; George F. Smith; Daniel L. Kelly; Saoirse O’Donoghue; Paul Dowding; Susan Iremonger; Fraser J. G. Mitchell (Biodiversity and Conservation, 2008)

Identifying practical indicators of biodiversity for stand-level management of plantation forests - George F. Smith; Tom Gittings; Mark Wilson; Laura French; Anne Oxbrough; Saoirse O’Donoghue; John O’Halloran; Daniel L. Kelly; Fraser J. G. Mitchell; Tom Kelly; Susan Iremonger; Anne-Marie McKee; et al. (Biodiversity and Conservation, 2008)

Biosynthesis of Dibenzyl Trisulfide (DTS) from somatic embryos and rhizogenous/embryogenic callus derived from Guinea hen weed (Petiveria alliacea L.) leaf explants - S. A. Webster; S. A. Mitchell; W. A. Gallimore; L. A. D. Williams; M. H. Ahmad (In Vitro Cellular & Developmental Biology - Plant, 2008)

Gene-environment interactions in a mutant mouse kindred with native airway constrictor hyperresponsiveness - Lawrence H. Pinto; Emily Eaton; Bohao Chen; Jonah Fleisher; Dmitry Shuster; Joel McCauley; Dalius Kedainis; Sandra M. Siepka; Kazuhiro Shimomura; Eun-Joo Song; Aliya Husain; Oren J. Lakser; et al. (Mammalian Genome, 2008)

Epiphytes of Sitka spruce (Picea sitchensis) plantations in Ireland and the effects of open spaces - Linda Coote; George F. Smith; Daniel L. Kelly; Saoirse O’Donoghue; Paul Dowding; Susan Iremonger; Fraser J. G. Mitchell (Biodiversity and Conservation, 2007)

Three-dimensional simulations and wind-tunnel experiments on airflow over isolated forest stands - Terry L. Clark; Stephen J. Mitchell; Michael Novak (Boundary-Layer Meteorology, 2007)

Three-dimensional simulations of air flow and momentum transfer in partially harvested forests - Terry L. Clark; Stephen J. Mitchell (Boundary-Layer Meteorology, 2007)

Isozyme- and gender-specific induction of glutathione S-transferases by flavonoids - Alyson E. Mitchell; Stephanie A. Burns; Jaime L. Rudolf (Archives of Toxicology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Antidepressant-like effects of the novel, selective, 5-HT2C receptor agonist WAY-163909 in rodents - Sharon Rosenzweig-Lipson; Annmarie Sabb; Gary Stack; Paul Mitchell; Irwin Lucki; Jessica E. Malberg; Steve Grauer; Julie Brennan; John F. Cryan; Stacey J. Sukoff Rizzo; John Dunlop; James E. Barrett; et al. (Psychopharmacology, 2007)

Productivity of Three Young Mixed-Species Plantations Containing N2-Fixing Acacia and Non-N2-Fixing Eucalyptus and Pinus Trees in Southeastern Australia - David I. Forrester; Jürgen Bauhus; Annette L. Cowie; Peter A. Mitchell; John Brockwell (Forest Science, 2007)
Mixed species plantations have the potential to exceed the biomass production of monocultures. This study examined the productivity of three mixed species plantations in southeastern Australia. Two of these trials contained a Eucalyptus sp. (E. saligna Smith or E. nitens [Deane & Maiden] Maiden) planted with Acacia mearnsii De Wild., and the other contained Pinus radiata D. Don with A. mearnsii, A. decurrens Willd., E. benthamii Maiden & Cambage, or E. smithii R. Baker. Each trial contained both monocultures and mixtures, and was replicated three or four times. Tree diameters or heights were smaller in mixture than monocultures for some species (P. radiata diameters of 5.9 cm and 7.0 cm in 2:1 mixtures with A. mearnsii and monocultures, respectively) but tended to increase (not significantly) for other species (E. nitens diameters of 10.6 cm and 8.5 cm and A. mearnsii diameters of 9.2 cm and 8.8 cm in 1:1 mixtures and monocultures, respectively). As a result, mixtures were intermediate in aboveground biomass production between monocultures of the mixed species in each trial, or they were not significantly different from the monocultures. Competition for resources other than nitrogen (N), such as light, soil moisture, or other nutrients, appeared to balance any positive effects that might have occurred, such as through increased N availability. For example, foliar N concentrations of E. saligna were higher in mixture (23.1 mg g−1) than monoculture (17.7 mg g−1); however, this did not result in greater aboveground tree biomass. The range of different growth responses from mixing different species in this study and in other studies shows that a fundamental understanding of the underlying processes is required to enable a greater predictive capacity of the circumstances under which mixtures can be successful.

Comparison between ATSR‐2 stereo, MOS O 2 ‐A band and ground‐based cloud top heights - C. Naud; K. L. Mitchell; J.‐P. Muller; E. E. Clothiaux; P. Albert; R. Preusker; J. Fischer; R. J. Hogan (International Journal of Remote Sensing, 2007)

Stereo cloud‐top heights and cloud fraction retrieval from ATSR‐2 - J.‐P. Muller; M.‐A. Denis; R. D. Dundas; K. L. Mitchell; C. Naud; H. Mannstein (International Journal of Remote Sensing, 2007)

A case of true hermaphroditism reveals an unusual mechanism of twinning - Vivienne L. Souter; Melissa A. Parisi; Dale R. Nyholt; Raj P. Kapur; Anjali K. Henders; Kent E. Opheim; Daniel F. Gunther; Michael E. Mitchell; Ian A. Glass; Grant W. Montgomery (Human Genetics, 2007)

Molecular Evolution of the Transferrin Receptor/Glutamate Carboxypeptidase II Family - Lisa Ann Lambert; Stacey L. Mitchell (Journal of Molecular Evolution, 2007)

Quantifying anthropogenic influence on recent near-surface temperature change - M. R. Allen; N. P. Gillett; J. A. Kettleborough; G. Hegerl; R. Schnur; P. A. Stott; G. Boer; C. Covey; T. L. Delworth; G. S. Jones; J. F. B. Mitchell; T. P. Barnett (Surveys in Geophysics, 2006)

Plastid genome characterisation in Brassica and Brassicaceae using a new set of nine SSRs - M. L. Flannery; F. J. G. Mitchell; S. Coyne; T. A. Kavanagh; J. I. Burke; N. Salamin; P. Dowding; T. R. Hodkinson (Theoretical and Applied Genetics, 2006)

Mapping the central effects of ketamine in the rat using pharmacological MRI - Clare L. Littlewood; Nicholas Jones; Michael J. O’Neill; Stephen N. Mitchell; Mark Tricklebank; Steven C. R. Williams (Psychopharmacology, 2006)

Interaction of hydrology and nutrient limitation in the Ridge and Slough landscape of the southern Everglades - Michael S. Ross; Sherry Mitchell-Bruker; Jay P. Sah; Stuart Stothoff; Pablo L. Ruiz; David L. Reed; Kris Jayachandran; Charles L. Coultas (Hydrobiologia, 2006)

Association of a polymorphism in the betacellulin gene with type 1 diabetes mellitus in two populations - Kristi D. Silver; Victoria L. Magnuson; Magdalena Tolea; Jian Wang; William A. Hagopian; Braxton D. Mitchell (Journal of Molecular Medicine, 2006)

Biotic interactions and plant invasions - Charles E. Mitchell; Anurag A. Agrawal; James D. Bever; Gregory S. Gilbert; Ruth A. Hufbauer; John N. Klironomos; John L. Maron; William F. Morris; Ingrid M. Parker; Alison G. Power; Eric W. Seabloom; Mark E. Torchin; et al. (Ecology Letters, 2006)
Introduced plant populations lose interactions with enemies, mutualists and competitors from their native ranges, and gain interactions with new species, under new abiotic conditions. From a biogeographical perspective, differences in the assemblage of interacting species, as well as in abiotic conditions, may explain the demographic success of the introduced plant populations relative to conspecifics in their native range. Within invaded communities, the new interactions and conditions experienced by the invader may influence both its demographic success and its effects on native biodiversity. Here, we examine indirect effects involving enemies, mutualists and competitors of introduced plants, and effects of abiotic conditions on biotic interactions. We then synthesize ideas building on Darwin's idea that the kinds of new interactions gained by an introduced population will depend on its relatedness to native populations. This yields a heuristic framework to explain how biotic interactions and abiotic conditions influence invader success. We conclude that species introductions generally alter plants’ interactions with enemies, mutualists and competitors, and that there is increasing evidence that these altered interactions jointly influence the success of introduced populations.

Mapping the central effects of ketamine in the rat using pharmacological MRI - Clare L. Littlewood; Nicholas Jones; Michael J. O’Neill; Stephen N. Mitchell; Mark Tricklebank; Steven C. R. Williams (Psychopharmacology, 2006)

Evaluation of a component of the cloud response to climate change in an intercomparison of climate models - K. D. Williams; M. A. Ringer; C. A. Senior; M. J. Webb; B. J. McAvaney; N. Andronova; S. Bony; J. -L. Dufresne; S. Emori; R. Gudgel; T. Knutson; B. Li; et al. (Climate Dynamics, 2006)

Contrasting stream water NO 3 − and Ca 2+ in two nearly adjacent catchments: the role of soil Ca and forest vegetation - SHEILA F. CHRISTOPHER; BLAIR D. PAGE; JOHN L. CAMPBELL; MYRON J. MITCHELL (Global Change Biology, 2006)
Two nearly adjacent subcatchments, located in the Adirondack Mountains of New York State, US, with similar atmospheric inputs of N (0.6 kmol ha −1 yr −1 ), but markedly different stream water solute concentrations, provided a unique opportunity to evaluate the mechanisms causing this variation. Subcatchment 14 (S14) had much greater stream water Ca 2+ and NO 3 − concentrations (851 and 73 μmol c L −1 , respectively) than Subcatchment 15 (S15) (427 and 26 μmol c L −1 , respectively). To elucidate factors affecting the variability in stream water concentrations, soil and forest floor samples from each subcatchment were analyzed for total elemental cations and extractable N species. Mineral soil samples were also analyzed for exchangeable cations. Tree species composition was characterized in each subcatchment and potential differences in land use history and hydrology were also assessed. Compared with S15, soils in S14 had significantly higher total elemental Ca 2+ in the forest floor (380 vs. 84 μmol g −1 ), Bs horizon (e.g. 1361 vs. 576 μmol g −1 ) and C horizon (1340 vs. 717 μmol g −1 ). Exchangeable Ca 2+ was also significantly higher in the mineral soil (64 μmol g −1 in S14 vs. 8 μmol g −1 in S15). Extractable NO 3 − was higher in S14 compared with S15 in both the forest floor (0.1 vs. 0.01 μmol g −1 ) and Bs horizon (0.2 vs. 0.07 μmol g −1 ) while extractable NH 4 + was higher in S14 vs. S15 in the forest floor (7 vs. 5 μmol g −1 ). The total basal area of ‘base‐rich indicator’ tree species (e.g. sugar maple, American basswood, eastern hophornbeam) was significantly greater in S14 compared with S15, which had species characteristic of sites with lower base concentrations (e.g. American beech and eastern white pine). The disparity in stream water Ca 2+ and NO 3 − , concentrations and fluxes between S14 and S15 were explained by differences in tree species composition and soil properties rather than differences in land use or hydrology. The marked difference in soil Ca 2+ concentrations in S14 vs. S15 corresponded to the higher stream water Ca 2+ and the larger contribution of base‐rich tree species to the overstory biomass in S14. Soil under such species is associated with higher net mineralization and nitrification and likely contributed to the higher NO 3 − concentrations in the drainage waters of S14 vs. S15. Studies investigating differences in spatial and temporal patterns of the effects of chronic N deposition on surface water chemistry need to account for changes in tree species composition and how vegetation composition is influenced by soil properties, as well as climatic and biotic changes.

A single injection of the kappa opioid antagonist norbinaltorphimine increases ethanol consumption in rats - Jennifer M. Mitchell; Marisa T. Liang; Howard L. Fields (Psychopharmacology, 2005)

A single injection of the kappa opioid antagonist norbinaltorphimine increases ethanol consumption in rats - Jennifer M. Mitchell; Marisa T. Liang; Howard L. Fields (Psychopharmacology, 2005)

Solid-Supported Parallel Synthesis of Hydroxybenzylamine Libraries Possessing Antileishmial Activity - Guillermo R. Labadie; Paolo B. Carvalho; Sanjay Batra; Seoung-Ryoung Choi; Sabana I. Khan; Babu L. Tekwani; Mitchell A. Avery (Medicinal Chemistry Research, 2005)

Underwater Locomotion in the Desert Locust: Behavioural Choice When Confronted with an Aquatic Barrier - W. J. Heitler; J. L. Mitchell; L. Dinwiddie (Journal of Insect Behavior, 2005)

Identification of mutations from phenotype-driven ENU mutagenesis in mouse Chromosome 7 - Cymbeline T. Culiat; Mitchell L. Klebig; Zhaowei Liu; Heidi Monroe; Beverly Stanford; Jayashree Desai; Samvit Tandan; Lori Hughes; Marilyn K. Kerley; Donald A. Carpenter; Dabney K. Johnson; Eugene M. Rinchik; et al. (Mammalian Genome, 2005)

Molecular characterization of sulfate‐reducing bacteria in a New England salt marsh - Michele Bahr; Byron C. Crump; Vanja Klepac‐Ceraj; Andreas Teske; Mitchell L. Sogin; John E. Hobbie (Environmental Microbiology, 2005)
Summary Sulfate reduction, mediated by sulfate‐reducing bacteria (SRB), is the dominant remineralization pathway in sediments of New England salt marshes. High sulfate reduction rates are associated with the rhizosphere of Spartina alterniflora when plants elongate aboveground. The growth process concurrently produces significant amounts of new rhizome material belowground and the plants leak dissolved organic compounds. This study investigated the diversity of SRB in a salt marsh over an annual growth cycle of S. alterniflora by exploring the diversity of a functional gene, dissimilatory sulfite reductase ( dsrAB ). Because the dsrAB gene is a key gene in the anaerobic sulfate‐respiration pathway, it allows the identification of microorganisms responsible for sulfate reduction. Conserved dsrAB primers in polymerase chain reaction (PCR) generated full‐length dsrAB amplicons for cloning and DNA sequence analysis. Nearly 80% of 380 clone sequences were similar to genes from Desulfosarcina and Desulfobacterium species within Desulfobacteraceae. This reinforces the hypothesis that complete oxidizers with high substrate versatility dominate the marsh . However, the phylotypes formed several clades that were distinct from cultured representatives, indicating a greater diversity of SRB than previously appreciated. Several dsrAB sequences were related to homologues from Gram‐positive, thermophilic and non‐thermophilic Desulfotomaculum species. One dsrAB lineage formed a sister group to cultured members of the delta‐proteobacterial group Syntrophobacteraceae . A deeply branching dsrAB lineage was not affiliated with genes from any cultured SRB. The sequence data from this study will allow for the design of probes or primers that can quantitatively assess the diverse range of sulfate reducers present in the environment.

Host Blood Proteins and Peptides in the Midgut of the Tick Dermacentor variabilis Contributeto Bacterial Control - Daniel E. Sonenshine; Wayne L. Hynes; Shane M. Ceraul; Robert Mitchell; Tiffany Benzine (Experimental and Applied Acarology, 2005)

Coyote movements and social structure along a cryptic population genetic subdivision - BENJAMIN N. SACKS; BRIAN R. MITCHELL; CHRISTEN L. WILLIAMS; HOLLY B. ERNEST (Molecular Ecology, 2005)
A recent region‐wide study determined that the central California coyote ( Canis latrans ) population was genetically subdivided according to habitat bioregions, supporting the hypothesis that coyotes exhibit a dispersal bias toward their natal habitat type. Here, we further investigated this hypothesis using radio‐collared coyotes captured on a 150‐km 2 study site on the border of (i.e. overlapping) two bioregions (Great Valley and Cascade Mountains). As predicted, most coyotes were assigned (based on a priori genetic criteria) to genetic clusters corresponding to one of these two bioregions. All of those assigned to the Great Valley genetic cluster were caught in (and for the most part, remained in) the Great Valley bioregion. However, contrary to expectations, the coyotes assigned to the Cascades genetic cluster occurred commonly in both bioregions. Nearly all resident individuals on the study site, regardless of the particular bioregion, were assigned to the Cascades genetic cluster, whereas a sizable fraction of nonresident (transient or dispersing) coyotes caught in the Great Valley bioregion were assigned to the Great Valley cluster. Even among resident coyotes, interrelatedness of packs was greater within than between bioregions, and packs with territories overlapping both bioregions were more closely related to those with territories completely within the Cascades bioregion than territories completely within the Great Valley bioregion. Finally, direct estimates indicated that gene flow was twice as high from the Cascades bioregion to the Great Valley bioregion than in the reverse direction. Collectively, these findings reveal the anatomy of the genetic subdivision as beginning abruptly at the bioregion boundary and ending diffusely within the Great Valley bioregion.

Serial analysis of V6 ribosomal sequence tags (SARST‐V6): a method for efficient, high‐throughput analysis of microbial community composition - David T. Kysela; Carmen Palacios; Mitchell L. Sogin (Environmental Microbiology, 2005)
Summary Serial analysis of ribosomal sequence tags (SARST) is a novel technique for characterizing microbial community composition. The SARST method captures sequence information from concatemers of short 16S rDNA polymerase chain reaction (PCR) amplicons from complex populations of DNA. Here, we describe a similar method, serial analysis of V6 ribosomal sequence tags (SARST‐V6), which targets the V6 hypervariable region of bacterial 16S rRNA genes. The SARST‐V6 technique exploits internal primer sequences to generate compatible restriction digest overhangs, thereby improving upon the efficiency of SARST. Serial analysis of V6 ribosomal sequence tags of bacterial community composition in hydrothermal marine sediments from Guaymas Basin resembled results of cloning and sequencing of single, full‐length PCR products from ribosomal RNA genes of the same microbial community. Both methods identified the same major bacterial groups, but only SARST‐V6 recovered thermodesulfobacteria and γ‐proteobacteria sequences, while only full‐length PCR product cloning recovered candidate division OP11 se‐quences. There were differences in the relative frequencies of some phylotypes. The disparities reflect differences in the amplicon pool obtained during initial amplification that may result from different primer affinities or DNA degradation. These results demonstrate the utility of SARST‐V6 in collecting taxonomically informative data for high‐throughput analysis of microbial communities.

Frequency-dependent Shear-wave Q Models for the Crust of China and Surrounding Regions - Alemayehu L. Jemberie; Brian J. Mitchell (Pure and Applied Geophysics, 2005)

Depositional and post‐depositional history of warm stage deposits at Knocknacran, Co. Monaghan, Ireland: implications for preservation of Irish last interglacial deposits - A. P. M. Vaughan; L. A. Dowling; F. J. G. Mitchell; S.‐E. Lauritzen; A. M. McCabe; P. Coxon (Journal of Quaternary Science, 2004)
Organic‐rich deposits, uncovered during overburden removal from mantled gypsum karst at Knocknacran opencast gypsum mine, Co. Monaghan, are the best candidate to date for a last interglacial record in Ireland. The two till and organic‐rich deposits (preserved at different quarry elevations) were emplaced on to a Tertiary dolerite surface during high‐energy flood events and subsequently folded and faulted by movement towards sinkholes in underlying gypsum. Uranium–thorium disequilibrium dating suggests that the organic‐rich deposits in the upper section were hydrologically isolated at ca. 41 ka and those in the lower section at ca. 86 ka. Interpretation of the pollen content, although tentative because of the depositional and post‐depositional history of the material, suggests that the organic material originated in a warm stage possibly warmer than the post‐Eemian interstadials. The unusual setting of preservation may indicate that in situ , last interglacial deposits have generally been removed by erosion in Ireland. Copyright © 2004 John Wiley & Sons, Ltd.

Fine root branch orders respond differentially to carbon source-sink manipulations in a longleaf pine forest - Dali L. Guo; Robert J. Mitchell; Joseph J. Hendricks (Oecologia, 2004)

TSPY, the Candidate Gonadoblastoma Gene on the Human Y Chromosome, has a Widely Expressed Homologue on the X - Implications for Y Chromosome Evolution - Margaret L. Delbridge; Guy Longepied; Danielle Depetris; Marie-Genevieve Mattei; Christine M. Disteche; Jennifer A. Marshall Graves; Michael J. Mitchell (Chromosome Research, 2004)

Molecular response to climate change: temperature dependence of UV‐induced DNA damage and repair in the freshwater crustacean Daphnia pulicaria - Emily J. MacFadyen; Craig E. Williamson; Gabriella Grad; Megan Lowery; Wade H. Jeffrey; David L. Mitchell (Global Change Biology, 2004)
In temperate lakes, asynchronous cycles in surface water temperatures and incident ultraviolet (UV) radiation expose aquatic organisms to damaging UV radiation at different temperatures. The enzyme systems that repair UV‐induced DNA damage are temperature dependent, and thus potentially less effective at repairing DNA damage at lower temperatures. This hypothesis was tested by examining the levels of UV‐induced DNA damage in the freshwater crustacean Daphnia pulicaria in the presence and absence of longer‐wavelength photoreactivating radiation (PRR) that induces photoenzymatic repair (PER) of DNA damage. By exposing both live and dead (freeze‐killed) Daphnia as well as raw DNA to UV‐B in the presence and absence of PRR, we were able to estimate the relative importance and temperature dependence of PER (light repair), nucleotide excision repair (NER, dark repair), and photoprotection (PP). Total DNA damage increased with increasing temperature. However, the even greater increase in DNA repair rates at higher temperatures led net DNA damage (total DNA damage minus repair) to be greater at lower temperatures. Photoprotection accounted for a much greater proportion of the reduction in DNA damage than did repair. Experiments that looked at survival rates following UV exposure demonstrated that PER increased survival rates. The important implication is that aquatic organisms that depend heavily on DNA repair processes may be less able to survive high UV exposure in low temperature environments. Photoprotection may be more effective under the low temperature, high UV conditions such as are found in early spring or at high elevations.

Input-Output Budgets of Inorganic Nitrogen for 24 Forest Watersheds in the Northeastern United States: A Review - John L. Campbell; James W. Hornbeck; Myron J. Mitchell; Mary Beth Adams; Mark S. Castro; Charles T. Driscoll; Jeffrey S. Kahl; James N. Kochenderfer; Gene E. Likens; James A. Lynch; Peter S. Murdoch; Sarah J. Nelson; et al. (Water, Air, & Soil Pollution, 2004)

Linear interpolation error in measured surfaces in a dental erosion study - H. L. Mitchell; I. Koch; R. G. Chadwick (Medical & Biological Engineering & Computing, 2004)

Genome mosaicism is conserved but not unique in Pseudomonas aeruginosa isolates from the airways of young children with cystic fibrosis - Robert K. Ernst; David A. D′Argenio; Jeffrey K. Ichikawa; M. Gita Bangera; Sara Selgrade; Jane L. Burns; Peter Hiatt; Karen McCoy; Mitchell Brittnacher; Arnold Kas; David H. Spencer; Maynard V. Olson; et al. (Environmental Microbiology, 2003)
Summary Pseudomonas aeruginosa strains from the chronic lung infections of cystic fibrosis (CF) patients are phenotypically and genotypically diverse. Using strain PAO1 whole genome DNA microarrays, we assessed the genomic variation in P. aeruginosa strains isolated from young children with CF (6 months to 8 years of age) as well as from the environment. Eighty‐nine to 97% of the PAO1 open reading frames were detected in 20 strains by microarray analysis, while subsets of 38 gene islands were absent or divergent. No specific pattern of genome mosaicism defined strains associated with CF. Many mosaic regions were distinguished by their low G + C content; their inclusion of phage related or pyocin genes; or by their linkage to a vgr gene or a tRNA gene. Microarray and phenotypic analysis of sequential isolates from individual patients revealed two deletions of greater than 100 kbp formed during evolution in the lung. The gene loss in these sequential isolates raises the possibility that acquisition of pyomelanin production and loss of pyoverdin uptake each may be of adaptive significance. Further characterization of P. aeruginosa diversity within the airways of individual CF patients may reveal common adaptations, perhaps mediated by gene loss, that suggest new opportunities for therapy.

New records of Australian Myxomycota - R. McHugh; S. L. Stephenson; D. W. Mitchell; M. H. Brims (New Zealand Journal of Botany, 2003)
Twenty‐eight species of myxomycetes and other related organisms not previously known to occur in Australia are reported along with 78 new state records. Records were obtained from collections made in the field and from moist chamber cultures prepared with samples of various types of organic material known to support the growth of myxomycetes. The majority of these samples consisted of bark from living trees and shrubs but some samples of litter, both ground and aerial, and dung also were collected. Physarum crateriforme var. columellatum comb. et stat. nov. is proposed as a new name. The number of species recorded from the continent now stands at 177, which represents approximately 20% of the total number of world species.

Assessment of a procedure for detecting minute levels of tooth erosion - H. L. Mitchell; R. G. Chadwick; S. Ward; S. L. Manton (Medical & Biological Engineering & Computing, 2003)

Radiation hybrid mapping of the canine type I and type IV collagen gene subfamilies - Jennifer K. Lowe; Richard Guyon; Melissa L. Cox; Dianne C. Mitchell; Amy L. Lonkar; Frode Lingaas; Catherine Andr; Francis Galibert; Elaine A. Ostrander; Keith E. Murphy (Functional & Integrative Genomics, 2003)

Anthropogenic climate change for 1860 to 2100 simulated with the HadCM3 model under updated emissions scenarios - T. C. Johns; J. M. Gregory; W. J. Ingram; C. E. Johnson; A. Jones; J. A. Lowe; J. F. B. Mitchell; D. L. Roberts; D. M. H. Sexton; D. S. Stevenson; S. F. B. Tett; M. J. Woodage (Climate Dynamics, 2003)

Sub-fossils of cladocerans in the surface sediment of 135 lakes as proxies for community structure of zooplankton, fish abundance and lake temperature - Erik Jeppesen; Jens Peder Jensen; Torben L. Lauridsen; Susanne L. Amsinck; Kirsten Christoffersen; Martin Søndergaard; Stuart F. Mitchell (Hydrobiologia, 2003)

The Consequences of CO2 Stabilisation for the Impacts of Climate Change - N. W. Arnell; M. G. R. Cannell; M. Hulme; R. S. Kovats; J. F. B. Mitchell; R. J. Nicholls; M. L. Parry; M. T. J. Livermore; A. White (Climatic Change, 2002)

Production of Australian freshwater crayfish in earthen-based systems using pelleted diets and forage crops as food - Paul L. Jones; Jose R. Chavez; Brad D. Mitchell (Aquaculture International, 2002)

Molecular characterization of a novel recombinant strain of human astrovirus associated with gastroenteritis in children - J. E. Walter; J. Briggs; M. L. Guerrero; D. O. Matson; L. K. Pickering; G. Ruiz-Palacios; T. Berke; D. K. Mitchell (Archives of Virology, 2001)

Relative Base Excision Repair in Xiphophorus Fish Tissue Extracts - Ronald B. Walter; Huang-Mo Sung; Rebecca D. Obermoeller; David L. Mitchell; Gabriel W. Intano; Christi A. Walter (Marine Biotechnology, 2001)

The Effect of Soil Moisture and Cabbage Amendment on the Thermoinactivation of Phytophthora nicotianae - L. Coelho; D.J. Mitchell; D.O. Chellemi (European Journal of Plant Pathology, 2001)

Agent‐Based Modeling and Industrial Ecology - Robert L. Axtell; Clinton J. Andrews; Mitchell J. Small (Journal of Industrial Ecology, 2001)

How are climate and marine biological outbreaks functionally linked? - Marshall L. Hayes; Joseph Bonaventura; Todd P. Mitchell; Joseph M. Prospero; Eugene A. Shinn; Frances Van Dolah; Richard T. Barber (Hydrobiologia, 2001)

Expression and conservation of processed copies of the RBMX gene - Patricia A. Lingenfelter; Margaret L. Delbridge; Sushma Thomas; Hopi E. Hoekstra; Michael J. Mitchell; Jennifer A. Marshall Graves; Christine M. Disteche (Mammalian Genome, 2001)

DNA markers for Fusarium head blight resistance QTLs in two wheat populations - J. A. Anderson; R. W. Stack; S. Liu; B. L. Waldron; A. D. Fjeld; C. Coyne; B. Moreno-Sevilla; J. Mitchell Fetch; Q. J. Song; P. B. Cregan; R. C. Frohberg (Theoretical and Applied Genetics, 2001)

Mouse eosinophil-associated ribonucleases: a unique subfamily expressed during hematopoiesis - Stephania A. Cormier; Kirsten A. Larson; Shubing Yuan; Trella L. Mitchell; Kari Lindenberger; Patricia Carrigan; Nancy A. Lee; James J. Lee (Mammalian Genome, 2001)

Factors regulating the downstream migration of mature eels ( Anguilla spp.) at Aniwhenua Dam, Bay of Plenty, New Zealand - Jacques A. Boubée; Charles P. Mitchell; Benjamin L. Chisnall; Dave W. West; Eddie J. Bowman; Alex Haro (New Zealand Journal of Marine and Freshwater Research, 2001)
The downstream migrations of mature longfinned eels ( Anguilla dieffenbachii Gray, 1842) and shortfinned eels ( Anguilla australis Richardson, 1848) were investigated at Aniwhenua Dam on the Rangitaiki River between 1992 and 1998. Migrants were mostly females over 1000 mm total length (TL) with otoliths indicating rapid growth rates. Migrations, which occurred on a few nights each autumn, generally began once water temperatures began to decline and ended when temperatures dropped below c. 11 °C. Rainfall and flow increases were found to be key factors triggering migration events. Rainfall exceeding a cumulative total of 40 mm over 3 days accounted for 60% of migrant eels arriving at Aniwhenua. It is proposed that such rainfall triggers could be used as predictors to instigate mitigation activities that would allow mature eels to proceed uninjured past barriers such as hydro‐electric dams.

Phylogenetic characterization of epibiotic bacteria in the accessory nidamental gland and egg capsules of the squid Loligo pealei (Cephalopoda: Loliginidae) - Elena Barbieri; Bruce J. Paster; Deborah Hughes; Ludek Zurek; Duane P. Moser; Andreas Teske; Mitchell L. Sogin (Environmental Microbiology, 2001)
Sexually mature female squid Loligo pealei harbour dense bacterial communities in their accessory nidamental glands (ANGs) and in their egg capsules (ECs). This study describes a molecular approach using the 16S rRNA gene (rDNA) to identify bacterial populations within the ANG and the ECs of the North Atlantic squid species L. pealei . Fluorescent in situ hybridization (FISH) and 16S rDNA analysis showed that predominantly alpha‐ and, to a lesser extent, gamma‐proteobacteria were the predominant components of the ANG and EC bacterial communities. Sequencing results showed the presence of alpha‐proteobacterial populations affiliated with the Roseobacter group and additional deep‐branching alphaproteobacterial lineages. In contrast, isolates from the ANG and ECs contained only a few alpha‐proteobacteria of the Roseobacter group compared with several gamma‐proteobacterial isolates, mostly Shewanella and Pseudoalteromonas species. Most of the ANG‐associated bacterial populations were also found within the ECs of L. pealei . The molecular approach allowed the visualization of alpha‐proteobacteria as major constituents of a bacterial symbiosis within the reproductive system of the Loliginidae.

A meta-analysis of the response of soil respiration, net nitrogen mineralization, and aboveground plant growth to experimental ecosystem warming - L. Rustad; J. Campbell; G. Marion; R. Norby; M. Mitchell; A. Hartley; J. Cornelissen; J. Gurevitch (Oecologia, 2001)

The relationship between Y chromosome DNA haplotypes and Y chromosome deletions leading to male infertility - L. Quintana-Murci; C. Krausz; E. Heyer; J. Gromoll; I. Seifer; D.E. Barton; T. Barrett; N.E. Skakkebaek; E. Rajpert-De Meyts; M. Mitchell; A.C. Lee; M.A. Jobling; et al. (Human Genetics, 2001)

Chemical scoring and ranking assessment model - Erin M. Snyder; Shane A. Snyder; John Paul Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2001)

Phylogenomic Analysis of the α Proteasome Gene Family from Early-Diverging Eukaryotes - Juan L. Bouzatrid="*"rid="†"; Leslie K. McNeilrid="*"; Hugh M. Robertson; Leellen F. Solter; Julie E. Nixon; Jonathan E. Beever; H. Rex Gaskins; Gary Olsen; Shankar Subramaniam; Mitchell L. Sogin; Harris A. Lewin (Journal of Molecular Evolution, 2000)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

Damage to grass shrimp ( Palaemonetes pugio ) embryo DNA by summer sunlight followed by DNA repair in the dark - G. B. Kim; R. F. Lee; D. L. Mitchell (Marine Biology, 2000)

Global processing of spectrally complex sounds in macaques ( Macaca mullata ) and humans - Kevin N. O'Connor; Phillip Barruel; Mitchell L. Sutter (Journal of Comparative Physiology A, 2000)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

Sex-related differences in the antinociceptive effects of opioids: importance of rat genotype, nociceptive stimulus intensity, and efficacy at the µ opioid receptor - Charles D. Cook; Andrew C. Barrett; Emily L. Roach; Joseph R. Bowman; Mitchell J. Picker (Psychopharmacology, 2000)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

Modelling the recent historical impacts of atmospheric CO 2 and climate change on Mediterranean vegetation - C. P. Osborne; P. L. Mitchell; J. E. Sheehy; F. I. Woodward (Global Change Biology, 2000)
Summary During the past century, annual mean temperature has increased by 0.75°C and precipitation has shown marked variation throughout the Mediterranean basin. These historical climate changes may have had significant, but presently undefined, impacts on the productivity and structure of sclerophyllous shrubland, an important vegetation type in the region. We used a vegetation model for this functional type to examine climate change impacts, and their interaction with the concurrent historical rise in atmospheric CO 2 . Using only climate and soil texture as data inputs, model predictions showed good agreement with observations of seasonal and regional variation in leaf and canopy physiology, net primary productivity (NPP), leaf area index (LAI) and soil water. Model simulations for shrubland sites indicated that potential NPP has risen by 25% and LAI by 7% during the past century, although the absolute increase in LAI was small. Sensitivity analysis suggested that the increase in atmospheric CO 2 since 1900 was the primary cause of these changes, and that simulated climate change alone had negative impacts on both NPP and LAI. Effects of rising CO 2 were mediated by significant increases in the efficiency of water‐use in NPP throughout the region, as a consequence of the direct effect of CO 2 on leaf gas exchange. This increase in efficiency compensated for limitation of NPP by drought, except in areas where drought was most severe. However, while water was used more efficiently, total canopy water loss rose slightly or remained unaffected in model simulations, because increases in LAI with CO 2 counteracted the effects of reduced stomatal conductance on transpiration. Model simulations for the Mediterranean region indicate that the recent rise in atmospheric CO 2 may already have had significant impacts on productivity, structure and water relations of sclerophyllous shrub vegetation, which tended to offset the detrimental effects of climate change in the region.

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the North American Great Lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

SCRAM: A scoring and ranking system for persistent, bioaccumulative, and toxic substances for the north american great lakes - Erin M. Snyder; Shane A. Snyder; John P. Giesy; Shari A. Blonde; Gary K. Hurlburt; Cheryl L. Summer; Rachel R. Mitchell; Dennis M. Bush (Environmental Science and Pollution Research, 2000)

ESTABLISHMENT AND CHARACTERIZATION OF A CAPRINE MAMMARY MYOEPITHELIAL CELL LINE (CMMyoEC) - A. G. PANTSCHENKO; M. R. BARBER; J. WOODCOCK-MITCHELL; S. L. BUSHMICH; T. J. YANG (In Vitro Cellular & Developmental Biology - Animal, 2000)

ESTABLISHMENT AND CHARACTERIZATION OF A CAPRINE MAMMARY EPITHELIAL CELL LINE (CMEC) - A. G. PANTSCHENKO; J. WOODCOCK-MITCHELL; S. L. BUSHMICH; T. J. YANG (In Vitro Cellular & Developmental Biology - Animal, 2000)

Pathogenesis of Cryptococcus neoformans is Associated with Quantitative Differences in Multiple Virulence Factors - Rebecca Blackstock; Kent L. Buchanan; Robert Cherniak; Thomas G. Mitchell; Brian Wong; Ann Bartiss; Lydgia Jackson; Juneann W. Murphy (Mycopathologia, 1999)

Diel variation in horizontal distribution of Daphnia and Ceriodaphnia in oligotrophic and mesotrophic lakes with contrasting fish densities - Torben L. Lauridsen; Erik Jeppesen; Stuart F. Mitchell; David M. Lodge; Romi L. Burks (Hydrobiologia, 1999)

Uncertainty Analysis of Regional Mercury Exposure - C. Seigneur; K. Lohman; P. Pai; K. Heim; D. Mitchell; L. Levin (Water, Air, & Soil Pollution, 1999)

New Insights into Disintegrin Metalloproteases - T. J. Carty; L. L. LoPresti-Morrow; P. G. Mitchell; P. A. McNiff; K. F. McClure (Inflammation Research, 1999)

Differential induction of cinnamyl alcohol dehydrogenase during defensive lignification in wheat ( Triticum aestivum L.): characterisation of the major inducible form - Heidi J. Mitchell; Sharon A. Hall; Rebecca Stratford; John L. Hall; Mark S. Barber (Planta, 1999)

Mineral Soil and Solution Responses to Experimental N and S Enrichment at the Bear Brook Watershed in Maine (BBWM) - I. Fernandez; L. Rustad; M. David; K. Nadelhoffer; M. Mitchell (Environmental Monitoring and Assessment, 1999)

Lg Coda Q in Australia and its Relation to Crustal Structure and Evolution - B. J. Mitchell; S. Baqer; A. Akinci; L. Cong (Pure and Applied Geophysics, 1998)

Lg Coda Q Variations across South America and their Relation to Crustal Evolution - J. L. de Souza; B. J. Mitchell (Pure and Applied Geophysics, 1998)

Variant in sulfonylurea receptor-1 gene is associated with high insulin concentrations in non-diabetic Mexican Americans: SUR-1 gene variant and hyperinsulinemia - Denise L. Goksel; Kathryn Fischbach; Ravindranath Duggirala; Braxton D. Mitchell; Lydia Aguilar-Bryan; John Blangero; M. P. Stern; Peter O’Connell (Human Genetics, 1998)

DNA damage induced by ultraviolet radiation in coral-reef microbial communities - M. M. Lyons; P. Aas; J. D. Pakulski; L. Van Waasbergen; R. V. Miller; D. L. Mitchell; W. H. Jeffrey (Marine Biology, 1998)

Intensive aggregate formation with low vertical flux during an upwelling‐induced diatom bloom - Thomas Kiørboe; Peter Tiselius; Betty Mitchell‐Innes; Jørgen L. S. Hansen; Andre W. Visser; Xavier Mari (Limnology and Oceanography, 1998)
The surfaces of most pelagic diatoms are sticky at times and may therefore form rapidly settling aggregates by physical coagulation. Stickiness and aggregate formation may be particularly adaptive in upwelling systems by allowing the retention of diatom populations in the vicinity of the upwelling center. We therefore hypothesized that upwelling diatom blooms are terminated by aggregate formation and rapid sedimentation. We monitored the development of a maturing diatom (mainly Chaetoceros spp.) bloom in the Benguela upwelling current during 7 d in February. Chlorophyll concentrations remained consistently high during the observation period (~500 mg Chl m −2 ) and phytoplankton grew at an average specific rate of 0.25 d −1 . The diatoms were extraordinarily sticky, with stickiness coefficients of up to 0.40, which is the highest ever recorded for field populations. Combined with estimates of turbulent shear in the ocean such stickiness coefficients predict very high specific coagulation rates (0.3 d −1 ). In situ video observation demonstrated the occurrence of abundant diatom aggregates with surface water concentrations between 1,000 and 3,000 ppm. Despite the very high concentration of aggregates, vertical fluxes of phytoplankton were very low, with fractional losses −1 , and the aggregates thus seemed to be near neutrally buoyant. Losses due to copepod grazing were also low (~0.025 d −1 ). Most of the aggregates were colonized by the heterotrophic dinoflagellate Noctiluca scintillans that feed upon diatoms in the aggregates. The system appeared to be in near steady state; specific diatom growth rate, coagulation rate, and loss rate due to N. scintillans feeding were all of the same magnitude (0.25–0.3 d −1 ) and the latter two varied in concert. Our observations provide only partial support for the population retention hypothesis because aggregate buoyancy and N. scintillans grazing efficiently reduced the vertical flux of aggregates in this system.

Chuck Vocalizations of Wild Female Squirrel Monkeys (Saimiri sciureus) Contain Information on Caller Identity and Foraging Activity - Sue Boinski; Carol L. Mitchell (International Journal of Primatology, 1997)

Detection of chromosomal aneuploidy in endometriosis by multi-color fluorescence in situ hybridization (FISH) - Jong-Chul Shin; Helen L. Ross; Sherman Elias; Dianne D. Nguyen; Dorothy Mitchell-Leef; Joe Leigh Simpson; F. Z. Bischoff (Human Genetics, 1997)

A Large-Conductance Chloride Channel in Pigmented Ciliary Epithelial Cells Activated by GTPγS - C.H. Mitchell; L. Wang; T.J.C. Jacob (The Journal of Membrane Biology, 1997)

An evaluation of the utility of SSR loci as molecular markers in maize (Zea mays L.): comparisons with data from RFLPS and pedigree - J. S. C. Smith; E. C. L. Chin; H. Shu; O. S. Smith; S. J. Wall; M. L. Senior; S. E. Mitchell; S. Kresovich; J. Ziegle (Theoretical and Applied Genetics, 1997)

Influence of a proton pump inhibitor-based therapy onHelicobacter pylori strain selection - S. L. Hazell; H. M. Mitchell; G. Hanna; G. Daskalopoulos (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Probabilistic assessment of regional mercury exposure - C. Seigneur; P. Pai; M. Gerath; D. Mitchell; G. Hamby; G. Gong; C. Whipple; L. Levin (Water, Air, & Soil Pollution, 1997)

Probabilistic Assessment of Regional Mercury Exposure - C. Seigneur; P. Pai; M. Gerath; D. Mitchell; G. Hamby; G. Gong; C. Whipple; L. Levin (Water, Air, & Soil Pollution, 1997)

Reproductive Success Increases with Local Density of Conspecif ics in a Desert Mustard (Lesquerella fendleri). El Exito Reproductivo Incrementa con la Densidad Local de Coespecificos en la Mostaza del Desierto (Lesquerella fendleri) - Julia Roll; Randall J. Mitchell; Robert J. Cabin; Diane L. Marshall (Conservation Biology, 1997)

Depression, Cognitive Impairment, and Understanding of Medication Directions in Hospitalized Elderly Patients - Shelly L. Gray; Mark A. Sager; Mitchell R. Lestico; M. Jalaluddin (Pharmaceutical Research, 1997)

The effect of dietary protein source on growth and carcass composition in juvenile Australian freshwater crayfish - Paul L. Jones; Sena S. De Silva; Brad D. Mitchell (Aquaculture International, 1996)

Effects of replacement of animal protein by soybean meal on growth and carcass composition in juvenile Australian freshwater crayfish - Paul L. Jones; Sena S. De Silva; Brad D. Mitchell (Aquaculture International, 1996)

Characterization of a new thermophilic sulfate-reducing bacterium - E. A. Henry; R. Devereux; J. S. Maki; C. C. Gilmour; C. R. Woese; L. Mandelco; R. Schauder; C. C. Remsen; R. Mitchell (Archives of Microbiology, 1994)

Characterization of a new thermophilic sulfate-reducing bacterium. Thermodesulfovibrio yellowstonii , gen. nov. and sp. nov.: its phylogenetic relationship to Thermodesulfobacterium commune and their origins deep within the bacterial domain - E. A. Henry; R. Devereux; J. S. Maki; C. C. Gilmour; L. Mandelco; R. Schauder; C. C. Remsen; C. R. Woese; R. Mitchell (Archives of Microbiology, 1994)

Anaerobic O-demethylation of chlorinated guaiacols byAcetobacterium woodii andEubacterium limosum - Max M. Hggblom; Mitchell H. Berman; Anne Cornish Frazer; L. Y. Young (Biodegradation, 1993)

Molecular and biochemical elucidation of a cellular phenotype characterized by adenine analogue resistance in the presence of high levels of adenine phosphoribosyltransferase activity - Nada H. Khattar; Gregory E. Cooper; Debra L. DiMartino; Peggy L. Bishop; Mitchell S. Turker (Biochemical Genetics, 1992)

Molecular and biochemical elucidation of a cellular phenotype characterized by adenine analogue resistance in the presence of high levels of adenine phosphoribosyltransferase activity - Nada H. Khattar; Gregory E. Cooper; Debra L. DiMartino; Peggy L. Bishop; Mitchell S. Turker (Biochemical Genetics, 1992)

Competitive regimes and female bonding in two species of squirrel monkeys (Saimiri oerstedi and S. sciureus) - Carol L. Mitchell; Sue Boinski; Carel P. van Schaik (Behavioral Ecology and Sociobiology, 1991)

Resistance ofSpodoptera frugiperda [Lep.: Noctuidae] to a nuclear polyhedrosis virus in the field and laboratory - J. R. Fuxa; F. L. Mitchell; A. R. Richter (BioControl, 1988)

Mutagenicity of potential effluents from an experimental low btu coal gasifier - J. M. Benson; C. E. Mitchell; R. E. Royer; C. R. Clark; R. L. Carpenter; G. J. Newton (Archives of Environmental Contamination and Toxicology, 1982)

Toxicological characterization of the process stream from an experimental low Btu coal gasifier - J. M. Benson; J. O. Hill; C. E. Mitchell; G. J. Newton; R. L. Carpenter (Archives of Environmental Contamination and Toxicology, 1982)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Sectional notes - L. M. Ware; M. A. Lindsay; W. B. Ward; H. A. Reiley; A. G. Tolaas; Marx Koehnke; John C. Campbell; Robert Schmidt; Earl B. Tussing; K. W. Lauer; Mitchell Jenkins; John Noonan; et al. (American Journal of Potato Research, 1941)

Sectional notes - L. M. Ware; Geo D. Ruehle; J. G. Richard; J. C. Campbell; E. V. Hardenbueg; C. A. Henderson; Robert Schmidt; J. Mitchell Jenkins; John Noonan (American Journal of Potato Research, 1941)

Sectional notes - M. A. Lindsay; E. Marx; E. R. Bennett; C. L. Fitch; A. A. Henderson; Mitchell Jenkins; G. S. Ralston (American Journal of Potato Research, 1941)

Sectional notes - E. Marx; B. A. Brown; Frank W. Hussey; Marx Koehnke; E. V. Hardenburg; Robert Schmidt; Earl B. Tussing; Mitchell Jenkins; John Noonan; H. L. Bailey; Chas D. Gaines (American Journal of Potato Research, 1940)

Sectional notes - J. G. Richard; E. L. Newdick; E. V. Hardenburg; Mitchell Jenkins; John Noonan; H. H. Zimmerley (American Journal of Potato Research, 1939)

Sectional notes - L. M. Ware; E. Marx; A. H. Eddins; J. G. Richard; Robert Schmidt; Mitchell Jenkins (American Journal of Potato Research, 1939)

Sectional notes - L. M. Ware; W. M. Fifield; J. G. Richards; J. V. Pace; Mitchell Jenkins; G. S. Ralston (American Journal of Potato Research, 1939)